A deep learning framework for non-invasive quantification of wing and foot phenotypes in live broiler chickens - Yakun Yang; Xuehai Ge; Wei Wu; Qiancheng Shen; Xupeng Kou; Xu Hu; Longhe Wang; Hongcheng Xue; Lin Li (Computers and Electronics in Agriculture, 2026)

Enhanced carbon capture and storage in the green microalga Chlamydomonas by heterologous expression of an engineered carbonic anhydrase - Yunlong Ge; Wanyi Zhang; Shuo Lin; Xinyu Mao; Keqing Liu; Wei Ma; Songlin Ma; Yanbo Liu; Zhanyou Chi; Fantao Kong (Bioresource Technology, 2026)

Human YTHDC2 mutations disturb RNA homeostasis of oocytes and early embryos - Wei Su; Yang Wang; Jiaqi Sun; Changlong Zhang; Changjian Yin; Ying Cui; Xiaolei Chen; Bohan Yang; Shigang Zhao; Keliang Wu; Ge Lin; Zi-Jiang Chen; et al. (Human Genetics, 2026)

Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

Holocene environmental changes recorded by magnetic parameters of sediments in the Yangtze River Delta and implications for prehistoric cultural development - Guiye Zhang; Longsheng Wang; Shouyun Hu; Mingming Ma; Jiawen Zhao; Yanjun Ge; Lin Zeng; Xianbin Liu (Estuarine, Coastal and Shelf Science, 2026)

Toward tailoring vortex synergy for predictive vortex-induced vibrations suppression in bridge girders - Shuaikuang Chen; Chuanxin Hu; Lin Zhao; Wei Cui; Qiang Zhou; Yaojun Ge (Engineering Structures, 2026)

Defect-engineered Cu-TCPP/ZIF-L nanosheet-modified PVDF membrane with enhanced water purification and dye removal performance - Yiming Zhao; Jingyuan Zhang; Junmei Liu; Jiatong Han; Dan Xu; Jing Wang; Fengzhi Lyu; Lin Qin; Donghui Xu; Ge Chen; Guangyang Liu (Chemical Engineering Journal, 2026)

Unlocking the potential in municipal reclaimed water electrolysis for hydrogen production: Identification of the primary water matrix - Zongping Wang; Haoran Chen; Zhenbin Chen; Yunfei Li; Ang Lu; Yujie Cheng; Guosen Zhang; Ge Li; Shunjie Zhu; Lin Li; Lizhi Huang; Jiakun Fang; et al. (Water Research, 2026)

Exosomal TGFBI promotes malignant progression of melanoma by regulating the FN1 signaling pathway - Yongliang Ge; Jingya Qiao; Lingling Ju; Lin Chen; Songnian Gao (Tissue and Cell, 2026)

Targeted inhibition of JAK2 phosphorylation by GenX disrupts the JAK2-STAT3 pathway and induces cardiovascular toxicity in zebrafish: Insights from network toxicology and molecular dynamics - Yuzhi Zhao; Xiaoqiang Ge; Gaoyuan Wang; Qiaoling Zhang; Chengyu Geng; Zhongxiu Deng; Siyu Chen; Siyue Tan; Yifan Shi; Meng Zhao; Xinyi Wu; Shou-Lin Wang; et al. (Toxicology and Applied Pharmacology, 2026)

BlOFP1 is associated with reduced secondary cell wall formation and interacts with BlKNOX9 and BlBLH9 in Betula luminifera - Fei Ni; Xian-Ge Hu; Hebi Zhuang; Fuqiang Cui; Yousry A. El-Kassaby; Erpei Lin; Huahong Huang (Plant Science, 2026)

Achieving sustainable resettlement governance in urban water supply systems: Policy optimization of China's hydropower resettlement framework - Daran Cai; Lin Ji; Qian Li; Xiaocao Ge; Yi Xu; Yuanyuan Gao (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Connectivity and function determine whether ponds act as sources or sinks of nonpoint-source phosphorus - Xiaofen Bai; Chen Lin; Ke Song; Wenlan Feng; Junfeng Xiong; Siyu Ge; Wanqian Yu; Jianchun Chen; Yijun Tong (Journal of Hydrology, 2026)

Recoverable millimeter-sized poly(ether-ether-ketone)-based adsorbent beads with multisite complexation for Co2+/Ni2+ removal from radioactive wastewater - Peng-De Yu; Yan-Lin Ren; Wen-Juan Wang; Ya-Juan Cai; Ting Yue; Ke-Xiao Sang; Yi-Xing Sun; Dan Wu; Zi-Hao Yang; Chuan-Zhe Zhao; Ying-Kang Li; Ya-Ge Wu; et al. (Journal of Environmental Chemical Engineering, 2026)

Unraveling the core microbial succession during the moromi fermentation of cantonese soy sauce: An amplicon sequencing approach - Hongbiao Tang; Mouyong Zou; Xingui Zhu; Ge Tan; Liqiong Guo; Junfang Lin (Food Research International, 2026)

High thermoelectric performance in Sm and Bi dual-doped GeTe with nuanced recrystallization annealing - Ge Fu; Shangchao Lin; Yixuan Liu; Yang Liu; Qilin Zhang; Jie Xiao; Changying Zhao (Chemical Engineering Journal, 2026)

Synergistic multi-electron/proton transfer in Cu4POM@MOF composite boosts ammonia generation - Ning Gong; Shuyu Li; Linhua Wang; Xiaotian Wu; Ge Chen; Guangyang Liu; Luming Yang; Yi Niu; Liao-Yuan Yao; Donghui Xu; Lin Qin (Chemical Engineering Journal, 2026)

Straw pyrolysis reverses forest soil N2O emissions from stimulation to suppression by altering organic C quality and N cycling pathways - Yanfei Dong; Dafeng Hui; Jiashu Zhou; Tida Ge; Junjie Lin; Yu Luo; Yuxue Liu; Bing Yu; Yanjiang Cai; Jason C. White; Yongfu Li (Chemical Engineering Journal, 2026)

Endogenously water-driven self-powered bioelectrical engineering scaffold mediates peripheral nerve regeneration - Guanhong Liu; Yazhou Lin; Haocheng Yang; Chengbai Dai; Rongze Tang; Kezhen Ge; Feng Yuan; Fenglei Gao; Bin Pan; Minghao Chao (Chemical Engineering Journal, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

Neurotoxicological Concerns: Azole Fungicides as Mixed/Noncompetitive Inhibitors of Human and Rat 5α-Reductase 1 - Jiachen Lin; Yinghao Huang; Yilin Xu; Zhiqiang Yu; Chentao Ding; Mengru Li; Yingfen Ying; Ren-shan Ge; Yiluan Wang (Journal of Hazardous Materials, 2026)

Urinary biomarkers of emerging contaminants in relation to prevalent Parkinson's disease: An exploratory mixture and network toxicology study - Chiqun Shan; Yiming Ge; Junye Bian; Yuli Lin; Bo Fu; Qinru Xiao; Aihua Guo; Mengyan Li; Pan Xu; Yi Chen; Haobo Chen; Shaoyou Lu (Journal of Hazardous Materials, 2026)

Long-term outdoor artificial light at night and psychological symptoms among Chinese adolescents: Findings from a national school-based survey - Wenxin Ge; Jun Hong; Liqing Yao; Qiqi Lai; Jingyang Fang; Lixin Hu; Zhengge Jin; Wanxin Wu; Sichun Lin; Yinhuan Guo; Chang Qi; Xiaojian Yin; et al. (Environmental Research, 2026)

Associations of Placental Oxidative Stress with Exposure to Gestational Air Pollution: Evidence from the UPSIDE Cohort - Emily A. Craig; Yan Lin; Yihui Ge; Xiangtian Wang; Otgondelger Enkhtaivan; Don K. Harrington; Richard K. Miller; Susan K. Murphy; Sally W. Thurston; Philip K. Hopke; Emily S. Barrett; Thomas G. O'Connor; et al. (Environmental Research, 2026)

Retraction notice to ‘Association between prenatal exposure to ambient particulate matter and risk of hypospadias in offspring: A systematic review and meta-analysis’ [Environ. Res. 192 (2021) 110190] - Hua-Chuan Lin; Jing-Min Guo; Pin Ge; Ping Ou (Environmental Research, 2026)

Green synthesis of N-doped hierarchical porous biochar from Artemisia leaf for enhanced peroxydisulfate activation: Synergistic roles of edge nitrogen and carbonyl group - Lin Ge; Zhan Chen; Yuan Pan; Xiansheng Zhang; Teng Li; Xinyi Huang; Binbin Shao; Sheng Liu; Yunze Wang; Yu Zhang; Zhifeng Liu (Environmental Research, 2026)

The oxidative potential of PM2.5 outperforms its mass concentration in association with childhood sleep disorders: Evidence from a large-scale study in China - Yun-Hui Shao; Dan Cai; Qian Yao; Xi-Hua Lin; Jin-Shan Ge; Lu-Yin Wu; Yun-Jiang Yu; Guang-Hui Dong; She-Xia Ma (Environmental Pollution, 2026)

Integrated plasma proteomics and metabolomes reveal potential biomolecules linking PM2.5 to depression - Lan Chen; Dashan Zheng; Shengtao Wei; Ge Chen; Yang Shen; Leiyuan Liu; Hualiang Lin (Environmental Toxicology and Pharmacology, 2026)

Photo-crosslinking strategy to lock π-π-assembled ion channels in polymer membranes for enhanced monovalent anion selectivity - Yachun Ma; Simian Fei; Jie Fang; Qiuhua Li; Lin Zhang; Huchuan Wang; Liang Ge; Chuanrun Li (Desalination, 2026)

Bismuth-embedded hard carbon derived from Solidago canadensis toward sodium-ion batteries - Jiacheng Shen; Liang Liu; Hong Cui; Yiting Dai; Ge Lin; Yuanzhe Wang; Ziyao Zhang; Jiantie Xu (Chemical Engineering Journal, 2026)

ER stress promoted MAMs formation and ER-Mito Ca2+ transfer: implication for fluoride-induced hippocampal neuronal injury and cognitive deficits in mice - Siman Lin; LuYang Cao; Yuzhe Zhou; Shengdan Liu; Yue Yan; Qiwei Zhang; Quan Yuan; Yufei Gao; Ge Du; Jun Hu; Dongmei Wang; Hua Fan (Chemico-Biological Interactions, 2026)

Fine-scale mapping of built-environment carbon emissions: A multi-source data fusion and explainable machine learning framework for high-density urban regions - Ge Shi; Haoran Tang; Wei Wang; Chuang Chen; Jiantao Shi; Bo Wang; Lin Sun (Building and Environment, 2026)

Ambient O3 exposure Associated with Progression of Different Metabolic Dysfunction States to Cardiovascular Diseases: the GOLD-Health Cohort - Yiting Wei; Xiangyi Liu; Zitong Zhuang; Liying Luo; Ge Chen; Peng Hu; Hui Liu; Weiquan Lin; Hualiang Lin (Atmospheric Environment, 2026)

PTPRO Governs Synaptic Density, Long-Term Potentiation and Cognitive Function In Vivo - Xiangdong Wang; Jiaguo Wu; Mengna Liu; Kun Zhang; Xinping Yuan; Fangting Xing; Wenjie Xu; Yulin Zheng; Yifei Wu; Lin Luo; Xinyi Ding; Ge Gao; et al. (Neuroscience Bulletin, 2026)

The JAK/STAT pathway: a pivotal therapeutic target in disease and advances in natural product modulation - Ming-Yue Li; Yu-Yang Lin; Chun-Ying Wang; Yu-Shan Qi; Jun-Sheng Zhang; Di Ge; Hai-Na Yu; Hua Zhang; Jie Bao (Molecular Diversity, 2026)

Genomic landscape of idiopathic male infertility and the pregnancy outcomes following assisted reproductive technology - Chen Tan; Tongyao Hu; Lanlan Meng; King Kin Lam; Qing Zhang; Xilin Xu; Shimin Yuan; Yurong Wang; Zilan Huang; Keren Zhou; Yong Li; Chunbo Xie; et al. (Science Bulletin, 2026)

A synergistic strategy combining passive insulation and active discharge for mitigating thermal runaway propagation in lithium-ion batteries - Peng Liu; Xingyu Long; Tao Cao; Jiayi Ge; Wenhao Zhu; Gang Wu; Lin Hu (Process Safety and Environmental Protection, 2026)

A stochastic multi-physics framework integrating thermo-electrochemical-microbial dynamics for lifecycle corrosion prediction and risk quantification of subsea pipelines - Yungen He; Ge Song; Shuang Ma; Yajing Liu; Yanhui Hu; Rongsheng Lin; Jiangen Tao (Ocean Engineering, 2026)

Corrigendum to “Long-term exposure to fine particulate matter constituents and the prognosis of oral cancer patients: A prospective study in Southeastern China” [J Hazard Mater 487 (2025) 137304] - Peng Hu; Liling Shen; Ge Chen; Weiyi Yang; Yanmei Ji; Baochang He; Hualiang Lin (Journal of Hazardous Materials, 2026)

Trace volatile sulfur compounds in biogases from sanitary landfill site: emission level, toxicity, and mitigation measure - Tong Gao; Jinlong Li; Lin Li; Yanjie Wang; Jingyun Ge; Yunping Han (Journal of Cleaner Production, 2026)

Exploring the endogenous and exogenous key aroma-active components in three aroma types of black teas from different cultivars - Weixuan Li; Zhouling Zhong; Han Yan; Longyu Guo; Ge Chen; Zhi Lin; Haipeng Lv; Yue Zhang; Yin Zhu (Food Research International, 2026)

Travelling wave mode decomposition: Methodology and a case study on vortex-induced vibration of a closed-box girder - Chuanxin Hu; Shuaikuang Chen; Xianglong Wang; Lin Zhao; Yaojun Ge (Engineering Structures, 2026)

Reaction-generated secondary phase advances electronic-phonon decoupling and boosted mechanical performance in Bi0.42Sb1.58Te3 alloys - Yi-lin Liu; Hao Liang; Chong-Yu Wang; Jiang-Hu Yu; Kang Yue; Qian Deng; Ju Rong; Jing Feng; Zhen-Hua Ge (Chemical Engineering Journal, 2026)

Differences between human and rat 5α-Reductase 1 inhibition by phenolic disinfectants: Comparative kinetics and binding modes for neurosteroid synthesis - Xinyu Han; Wanyu Li; Yinghao Huang; Lisha Wang; Tianchi Zhao; Xishi Chen; Hao Lin; Yiyan Wang; Ren-shan Ge; Jianfeng Ma (Chemico-Biological Interactions, 2026)

Integrated UPLC-MS/MS profiling and network pharmacology-based analysis of the anti-hyperglycemic potential of Baihu Jia Renshen Decoction combined with Sanghuangporus vaninii extract in mice - Jia Zhang; Ying Chen; Yanfa Lin; Zifeng Huang; Xiaodong Ge; Bin Liu; Zirui Huang (Journal of Molecular Histology, 2026)

Quercetin exerts radioprotective effects against radiation-induced intestinal injury with involvement of the PI3K-AKT/Caspase-3 axis - Qing Guo; Zhibing Tang; Zhenyu Hou; Ge Yan; Jiaxuan Wang; Man Zhang; Ruige Ma; Juan Wang; Qiong Feng; Zhen Wang; Chunlei Wang; Lin Zhao (Molecular and Cellular Biochemistry, 2026)

Urban heat exposure patterns and domain-specific executive function in adolescents - Lixin Hu; Wenwen Bao; Zhengge Jin; Jun Hong; Wenxin Ge; Yawen Tan; Liqing Yao; Wanxin Wu; Jiaqi Chen; Xiuzhi Yang; Zhuowen Wu; Sichun Lin; et al. (Environmental Research, 2026)

Associations between non-methane volatile organic compounds and cause-specific mortality across 14 major categories - Shengtao Wei; Ge Chen; Lan Chen; Zijun Yang; Fei Tian; Peng Hu; Kin Fai Ho; Shanshan Ran; Dashan Zheng; Hualiang Lin (Environmental Pollution, 2026)

Microfluidic-based magnetic microspheres for targeted delivery of curcumin nanoparticles in gastroesophageal reflux disease therapy - Haoyao Jiang; Zhonglin Fang; Han Lin; Di Xu; Wanqian Xu; Mengqi Han; Luoran Shang; Ye Zhao; Teng Ma; Di Ge (Chemical Engineering Journal, 2026)

Synergistic Mo2C/MoO2 hybridization in sucrose-derived hard carbon spheres for sodium-ion batteries - Hong Cui; Liang Liu; Jiacheng Shen; Ge Lin; Yiting Dai; Yuanzhe Wang; Yue Tang; Jiantie Xu (Chemical Engineering Journal, 2026)

Lipophilicity and alkyl chain length govern pyridine quaternary ammonium disinfectants as gonadal 3β-hydroxysteroid dehydrogenase inhibitors: Implications for endocrine disruption - Lingfei Wang; Chaochao Gong; Xiya Ren; Hao Lin; Ren-shan Ge; Congde Chen (Chemico-Biological Interactions, 2026)

Effect of high ammonium stress on microalgae cultivation: An integrated analysis of research trends, mechanistic insights, and mitigation strategies - Jingyuan Xia; Jialu Liu; Jing Li; Ye Lin; Shijian Ge; Shuang Qiu (Bioresource Technology, 2026)

A label-free fluorescent/electrochemical dual-mode zinc complex biosensor for highly selective and sensitive detection of tetracycline - Zhi-Lin Mu; Zeyu Zhu; Jiale Cheng; Xingyu Zhan; Chen He; Zhongyan Chen; Hong-Ping Xiao; Jing-Yuan Ge (Analytica Chimica Acta, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Precise perception of surface tackiness enabled by a soft single-sensing-element tactile sensor - Ying Yang; Mingwei Gu; Jia-Sen Xie; Xingyu Ma; Yan-Na Lu; Lin Zheng; Jinhui Gu; Junshuai Chen; Yunjie Lu; Denys Makarov; Jin Ge (Science Bulletin, 2026)

Engineering Mn-confined Fe0-carbon with isolated oxygen-containing groups breaks the bottleneck for concurrent self-driven Fenton degradation of antibiotics and heavy metals immobilization - Yujiang Huang; Dan Liu; Zhouyang Shi; Tong Hu; Huiwang Dai; Sicheng Pan; Wenjun Zhou; Fei Ge; Daohui Lin; Lizhong Zhu (Journal of Hazardous Materials, 2026)

Switchable thermo-triggered and 3D-printable soy protein soft emulsion gels as fat analogs for plant-based meat - Ge Qiao; Xiao-Wei Chen; Xiao-Yang Luo; Lin-Shang Zhang; Xiao Liu (Food Hydrocolloids, 2026)

Multi-measure ecological restoration drives phytoplankton succession and shifts community assembly in an urban eutrophic lake - Xiaowen Lin; Xiaodong Wu; Xuguang Ge; Fan Xun; Weixiang Ren; Mengdie Zhou; Chenxin Zhong; Chunyan Xiao; Linlin Lei (Ecological Engineering, 2026)

An interlayer-engineered faradaic electrosorption system for co-removal of amikacin and heavy metal ions: Fe/Mo dual activation, energy storage, and adsorption selectivity - Pan Gong; Changhai Ji; Chang Liu; Xiaoshuang Yin; Wenzhong Yang; Lin Zhang; Shaojun Jiao; Feng Ge; Kegui Zhang (Chemical Engineering Journal, 2026)

Co NPs@N-Doped Peanut Shell-derived Biochar As an Efficient Catalyst for Peroxymonosulfate Activation in Acetaminophen Degradation - Xiaoxin Chen; Xingzi Zhu; Caiyan Ge; Jinxin Wang; Manli Guo; Yujuan Cao; Bixia Lin (Water, Air, & Soil Pollution, 2026)

Molting disruption in fall armyworm by an ankyrin-based Bracovirus factor from the parasitoid wasp Microplitis prodeniae Rao and Chandry - Yaru Wang; Farman Ullah; Liuying Lin; Xiangyun Cai; Ge Gao; Limin Chen; Zhiming Chen; Raul Narciso C. Guedes; Yaobin Lu; Jinda Wang; Youming Hou (Journal of Pest Science, 2026)

Flexible SERS tape: A plasmonic hybrid of AuNPs and layered K2Ti8O17 nanowire network for on-site detection of pesticide residues - Lin Xu; Mingru Cui; Zhongqi Ge; Ruikang Zou; Cong Wang; Pengfei Ni; Xi Huang; Bo Zhong; Lijuan Wang (Analytica Chimica Acta, 2026)

Exposure to second-generation flame retardants and risk of metabolic diseases: a systematic review and meta-analysis - Li Shi; Wei Du; Xi-Yuan Peng; Juan Miao; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Zhi-Ren Mu; Hong-Lin Chen (Archives of Toxicology, 2026)

Atmospheric Boundary Layer Eco-Environment Shanghuang Observatory: An Integrated Multiscale Research Platform in Southeastern China for Understanding Boundary Layer Processes, Atmospheric Chemistry Feedback, and Extreme Weather–Climate Linkages - Zifa Wang; Xiaole Pan; Yele Sun; Jinyuan Xin; Hang Su; Junji Cao; Jie Li; Ting Yang; Hang Liu; Weijie Yao; Weiqi Xu; Xueshun Chen; et al. (Advances in Atmospheric Sciences, 2026)

Association Between Lead Exposure and Anthropometric Indicators in School-aged Children: A Longitudinal Study - Xiangju Wu; Yang Zhou; Linhong Li; Jieying Gao; Rongchang Xiao; Qian Yang; Meng Wu; Siyan Ye; Chengpeng Cui; Peng Lin; Ruifeng Luo; Ge Yan; et al. (Biological Trace Element Research, 2026)

Advances and Perspectives in Atmospheric Environment Modeling in China - Zifa Wang; Xinwei Li; Meng Gao; Baozhu Ge; Xiao Tang; Xueshun Chen; Qizhong Wu; Lin Wu; Zhe Wang; Ting Yang; Xiaole Pan; Huansheng Chen; et al. (Advances in Atmospheric Sciences, 2026)

Genetic analysis and reproductive interventions in families affected by congenital cataracts: a study of 107 cases - Yun-hao Li; Qi Wang; Yao Peng; Juan Du; Liang Hu; Zhen-hua Tan; Feng Gu; Hao Hu; Qian-jun Zhang; Ge Lin; Guang-xiu Lu; Yue-Qiu Tan; et al. (Journal of Applied Genetics, 2026)

Comparative evaluation of urine, whole blood, and serum as biological matrices for human biomonitoring of neonicotinoid insecticides and metabolites - Yuli Lin; Junye Bian; Kai Lin; Yiming Ge; Chiqun Shan; Bo Fu; Weizhong Chen; Tao Chen; Qinru Xiao; Bingjun Lu; Qunlin Xiao; Shaoyou Lu (Journal of Hazardous Materials, 2026)

Deficiency of TEX264-mediated reticulophagy is linked to ER stress-induced neuronal necroptosis: Implication of fluoride-associated hippocampal injury and cognitive dysfunction - Ge Du; Quan Yuan; Rui Liu; Jiaming Liang; Milan Yang; Yufei Gao; Xiaoli Liu; Siman Lin; Rui Zhang; Binbin Wang; Dongmei Wang; Hua Fan (Journal of Environmental Sciences, 2026)

Mechanism of impinging-edge-vortex-dominated vortex-induced vibrations: Insights from simplified-vortex model framework - Chuanxin Hu; Xianglong Wang; Wenbo Li; Lin Zhao; Yaojun Ge (Engineering Structures, 2026)

Mechanical behavior and design of an eight-bolt extended stiffened end-plate connection with oversized holes: Experimental and numerical studies - Bin Jiang; Liping Duan; Siwei Lin; Jiming Liu; Ge Qu; Jincheng Zhao (Engineering Structures, 2026)

Genetic deletion of miR-200a/200b increases growth and feed conversion efficiency in yellow catfish - Xu Wang; Yan Xie; Qiaohong Lin; Yang Xiong; Ying Liu; Si Ge; Qiuen Tan; Zhipeng He; Youbo Jiang; Qingqing Han; Shuang Jin; Peipei Huang; et al. (Science China Life Sciences, 2026)

Correction to: Methyl jasmonate enhances carotenoid accumulation and lignin deposition in carrot taproot - Guang-Long Wang; Jia-Qi Wu; Yan-Xin Ge; Lin-Yan Jia; Cheng-Ling Zhou; Xu-Qin Ren; Ai-Sheng Xiong (Protoplasma, 2026)

Methyl jasmonate enhances carotenoid accumulation and lignin deposition in carrot taproot - Guang-Long Wang; Jia-Qi Wu; Yan-Xin Ge; Lin-Yan Jia; Cheng-Ling Zhou; Xu-Qin Ren; Ai-Sheng Xiong (Protoplasma, 2026)

Global inland waters trophic status from space observation: scientific advances and future challenges - Lili Lyu; Pierre-Andre Jacinthe; Nan Lin; Dongmei Lyu; Ge Liu; Sijia Li; Chong Fang; Hui Tao; Hao Yu; Zuchuan Li; Kaishan Song (Water Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Development of high-efficient CuFeZnAl-based hydrotalcite catalyst for glycerol hydrogenolysis to 1,2-propanediol - Yuanyuan Ge; Yifan Ma; Zhikuan Lin; Zhihang Lai; Haijun Guo; Bo Chen; Hairong Zhang; Lian Xiong; Xinde Chen; Zhili Li (Journal of Environmental Chemical Engineering, 2026)

A cellulosic waste-upcycled 1T/2H-MoS2/biochar heterostructure for efficient cationic dye adsorption via a multi-anchor chemisorption mechanism - Yifan Lu; Min He; Mingna Ge; Luning Chen; Lin Han; Cong Tu; Bang Yuan; Jie Huang (Journal of Environmental Chemical Engineering, 2026)

Fe(III)-enhanced degradation of para-nitrophenol in a UV/monochloramine system: Mechanism and toxicity analysis - Niu Ge; Yuyang Mao; Lin Deng; Changbo Zhang; Rajendra Prasad Singh (Journal of Environmental Management, 2026)

Unraveling geographical heterogeneity and spatial distribution of Long pepper fruits: An integrative analytical perspective - Shuwen Geng; Conghui Duan; Ying Ye; Yuye Gao; Yujia Zhai; Fangyuan Gao; Yuewei Ge; Yang Chen; Yunxia Li; Rongping Zhang; Xinglong Chen; Jian-lin Wu; et al. (Food Chemistry, 2026)

Structural characterization and neuroprotective effect of coix seed polysaccharides - Yini Lin; Xiaohan Ge; Meiru Mao; Jiawen Liu; Zixin Jin; Yi Wang (Food Bioscience, 2026)

4-hydroxybenzoic acid-assisted formic acid preserves lignin structure during efficient hemicellulose removal in bamboo biorefinery - Weidong Li; Hanwen Ge; Sen Ma; Lei Liu; Lin Luo; Zihao Qin; Aiyong He; Chao Wang; Xianhai Zeng (Chemical Engineering Journal, 2026)

Synergistic control of LixV2O5 with ordered-disordered hybrid rock-salt structure via chemical lithiation: Enhanced Li-ion battery performance - Wei He; Bei-Lei Yan; Wei-Wei Meng; Guang-Qiang Ma; Xue-Jun Zhu; Xue Hua-Mao; Lin Deng; Hong-Wei Ge; Tao Yang; Jun Wang (Chemical Engineering Journal, 2026)

Functional reorganization of microbial ecological clusters is associated with citrus soil health enhancement under greenhouse cultivation - Chenhong Liu; Qi Zhao; Lin Zhang; Fuzhi Ke; Xuebin Xu; Senxiang Yu; Jiaping Lang; Tida Ge; Cong Wang; Haoqing Zhang (Plant and Soil, 2026)

Synthesis of antioxidant 2-alkynylarylmethyl selenides via three-component assembly of arynes, alkynes and PhSO2SeCH3 - Jiayi Liang; Lijing Wang; Yujie Chen; Jie Hu; Weiqiang Lin; Ge Wu; Wenxi Zhang (Molecular Diversity, 2026)

Multi-omics analysis investigates the effects of replacing fishmeal with intestinal mucosal protein on growth performance and intestinal health in hybrid sturgeon - Yuanfa He; Jun Wen; Hang Chen; Guangjun Lv; Yongjun Chen; Shimei Lin; Haiping Liu; Zhijian Wang; Hailong Ge (Aquaculture, 2026)

Reactive species-mediated stepwise photoaging mechanisms of microplastics transferred from freshwater to seawater - Qiong Wen; Na Liu; Daohui Lin; Yang Zhou; Ge Zhang; Fei Ge (Water Research, 2026)

Metagenomic and cytotoxicity insights into the migration behavior and pathogenic potential of multi-medium microorganisms in a wastewater treatment plant - Wenwen Wang; Song Zhang; Yanjie Wang; Jingyun Ge; Lin Li (Water Research, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

Spiral-fluorene-integrated sterically shielded multi-resonance TADF emitter: simultaneously achieving narrowband emission and restraining Dexter energy transfer - Jiasen Zhang; Hao Liu; Lin Wu; Kaibo Fang; Deli Li; Denghui Liu; Xuewei Nie; Letian Xu; Zujin Zhao; Wei Li; Ziyi Ge (Science Bulletin, 2026)

A novel bZIP transcription factor VvbZIP026 induces anthocyanin biosynthesis and acylation modification in response to abscisic acid in ‘Summer Black’ grape - Zouchumo Ge; Mengwen Yao; Ting Chen; Yao Yao; Jiahui Lin; Jingtian Huo; Guiren Qi; Zhaosen Xie; Xianan Zhang; Lei Wang; Feng Leng (Plant Science, 2026)

Endoplasmic reticulum stress-induced CHOP activation mediates NLRP3 inflammasome-dependent pyroptosis in BDE-47-induced cognitive dysfunction - Quan Yuan; Rui Zhang; Jun Hu; Siman Lin; Ying Zhu; Junhong Geng; Ge Du; Xiao Yang; Yipin Zhao; Dongmei Wang; Binbin Wang; Hua Fan (NeuroToxicology, 2026)

Sex-specific associations between exposure to metal mixtures and mitochondrial DNA copy number: A repeated-measures study - Junxiu He; Xiaoting Ge; Sencai Lin; Yu Bao; Hong Cheng; Sihan Hu; Xiuming Feng; Qinghua Fan; Ying Yang; Xiaobo Yang (Journal of Environmental Sciences, 2026)

Enhancing electrochemical CO2 reduction with monoamino-functionalized cobalt tetraphenylporphyrin catalysts - Li-Yuan Zhao; Hui Wang; Hao Tan; Jie Chao; Zhi-Hang Lin; Ge-Chuan-Qi Pan; Xiao-Ji Wang; Qiang Sun (Fuel, 2026)

Cytoplasmic-nuclear remote suppression of c-MYC induces cell cycle arrest and enhances radiotherapy sensitivity in liver cancer via biohybrid platelets - Lin Xiao; Fei Ge; Qinyu Ji; Rui Ji; Yan Wang; Shaoqing Ju; Ming Cui; Donglin Xia; Rongrong Jing (Chemical Engineering Journal, 2026)

Periosteum-inspired lightweight aerogel composite for ultrahigh energy dissipation and dynamic impact perception - Qiankun Chen; Jianpeng Wu; Shuai Liu; Xinyi Wang; Shiyu Lin; Purun Wang; Xinglong Gong; Shaolin Ge; Ken Cham-Fai Leung; Shouhu Xuan (Chemical Engineering Journal, 2026)

Environmental pyridinium disinfectants impair cortisol metabolism via 11β-hydroxysteroid dehydrogenase 2 inhibition: A cross-species risk evaluation - Chaochao Gong; Xiuzhi Zhang; Yu Zhang; Xishi Chen; Hao Lin; Ren-shan Ge; Youming Zhao (Chemico-Biological Interactions, 2026)

PPIL1 promotes hepatocellular carcinoma progression and associates with poor prognosis - Yunyu Wu; Shuqing Jiang; Junming Yu; Hechun Lin; Saihua Zhang; Yizi Jin; Yang Su; Wenjiao Jin; Chao Ge; Qin Geng; Taoyang Chen; Jinjun Li; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Effects of silver nanoparticles and nitrile fungicides on soil microbial community structure, metabolic functions, and resistance genes - Yiwang Wang; Ting Gao; Jiajia Liu; Shaoheng Bao; Fuli Wang; Ge Yao; Xiaoyan Lin; Shijie Jiang; Jinlong Lai; Penggang Han; Jiang Hui (Applied Soil Ecology, 2026)

Disruption of sphingolipid metabolism triggers lung vascular inflammation and aging-like changes under hypoxia through VDAC1-mediated mitochondrial DNA release - Jin Xu; YiLing Ge; Bin Zhang; SiYuan He; QingLin Cao; PeiJie Li; YingRui Bu; YunGang Bai; Lin Zhang; GuoDong Tan; Jin Ma; ManJiang Xie (Apoptosis, 2026)

Photo-responsive polyprodrug supramolecular assemblies with self-accelerated subcellular delivery for synergistic photochemotherapy - Ming Liu; Zhenduo Zhao; Ming Li; Yitian Chen; Yicheng Wang; Xuehua Lin; Xinyu Wang; Qinghao Zhou; Zhishen Ge; Yongan Tang; Yibin Deng; Yuliang Zhao; et al. (Science Bulletin, 2026)

Isolation and identification of Desmodesmus sp. HDMA-07: Nutrient removal and biodiesel production potential in flax fiber wastewater - Han Wang; Xinyi Wang; Boqi Wang; Yimeng Lin; Jingping Ge; Wenxiang Ping (Process Safety and Environmental Protection, 2026)

From brewing dynamics to population health: A Nationwide investigation of bisphenol analogues contamination and exposure risk in tea from China - Xinjie Li; Kai Lin; Zhihong Huang; Yiming Ge; Xinxin Tang; Bingjun Lu; Xulong Chen; Yiran Chen; Xiangxuan Kong; Yi Chen; Shaoyou Lu (Food Chemistry, 2026)

Urban-scale seismic simulation and resilience assessment for building clusters incorporating self-centering structures - Zhichao Lin; Longhe Xu; Xingsi Xie; Zhang Ge (Engineering Structures, 2026)

Phytochemicals and health-promoting evaluations of Ophiorrhiza puffii , a chinese endemic plant - Qing Bu; Qi-Bin Yang; Zeng-Yue Ge; Ze-Xiong Shi; Lin-Fu Liang (Natural Product Research, 2026)

Immunotherapy checkpoint inhibitor-combination therapy versus chemotherapy alone among Chinese population in cholangiocarcinoma treatment: a systematic review and meta-analysis - Li Shi; Wei Du; Juan Miao; Xi-Yuan Peng; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Si-Qi Gao; Hong-Lin Chen (European Journal of Clinical Pharmacology, 2026)

Effects of Straw Returning on Physicochemical Properties and Microbial Characteristics of Agricultural Soil - Tantan Zhang; Shiqiang Ge; Rong Gan; Siyuan He; Fuyuan Duan; Lin Li (Current Microbiology, 2026)

The correlation between social support and hopelessness among cancer survivors: a meta-analysis - Lu-Ting Shen; Jian-Zeng Lan; Attiq-Ur-Rehman; Wei Li; Meng-Wei Ge; Rui Feng; Kang Zhong; Si-qi Gao; Hong-Lin Chen (Cancer Causes & Control, 2026)

Characteristics of inter-frequency clock bias for new GLONASS-M+/K1B/K2 satellites and its contribution to uncombined PPP - Baoqi Lin; Xinyun Cao; Yulong Ge; Fei Shen (GPS Solutions, 2026)

Extreme drought amplifies the dominant role of Secchi depth on the underwater light environment: evidence from Poyang Lake - Jianying Chao; Xiaowen Lin; Xiaodong Wu; Jian Li; Xuguang Ge; Zhenni Gao; Chenxin Zhong; Zian Xiang; Lishuai Zhang (Environmental Monitoring and Assessment, 2026)

Attached microalgae-simulated plants enhanced multiple-pollutant removal in a tidal flow constructed wetland: quantified efficiencies, pathways, and biological mechanisms - Shu-Han Ge; Mei-Zi Yang; Wei-Yi Qian; Lin-Lan Zhuang; Hai-Ming Wu; Zhuo Chen; Xiao-Xiong Wang; Jian Zhang (Water Research, 2026)

Aerosol-cloud layer detection algorithm of the DQ-1/ACDL - Feiyue Mao; Weiwei Xu; Zengxin Pan; Lin Zang; Ge Han; Linxin Dai; Xiuqing Hu; Weibiao Chen; Wei Gong (Remote Sensing of Environment, 2026)

Highly oxidized germacrane-type sesquiterpenoid dimers from Elephantopus tomentosus L.: Structural characterization, DFT calculation and anti-hepatoma potential - Zi-Hao Ge; Si-Hui Mi; Wen-Long Kou; Guo-Dong Yao; Bin Lin; Jian Wang; Ming Bai; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2026)

Investigation on the FCNN-based propeller optimization constrained by cavitation performance - Junyu Ge; Haipeng Guo; Guangnian Li; Lin Du (Ocean Engineering, 2026)

Transboundary dispersion and deposition of gaseous radioactive iodine revealed by anthropogenic 129I in mountainous regions - Yanyun Wang; Jie Zhou; Mu Lin; Yukun Fan; Peng Cheng; Luyuan Zhang; Huan Jiang; Ning Chen; Qi Liu; Ge Xu; Xiaolin Hou (Journal of Hazardous Materials, 2026)

Bioaerosols from outdoor wastewater treatment facilities: dispersal behavior, exposure risks and protection strategies - Jingyun Ge; Tong Gao; Huili Li; Zhongcai Lun; Changren Yan; Caixia Li; Yanjie Wang; Lin Li (International Journal of Hygiene and Environmental Health, 2026)

Heatwaves exacerbate the effects of early-season drought on peak vegetation growth in the Northern Hemisphere - Shaozhi Lin; Huanjiong Wang; Wenrui Bai; Chengxi Gao; Quansheng Ge (Global and Planetary Change, 2026)

Intelligent food preservation systems based on MOFs-AI integration: technological breakthroughs and developmental trends - Xin Ding; Nasi Ai; Yiming Zhao; Lingyun Li; Ge Chen; Donghui Xu; Xiaomin Xu; Lin Qin; Jing Chen; Guangyang Liu (Food Chemistry, 2026)

Covalent organic framework-mediated Nafion superhydrophobic coating for stabilizing the anode of aqueous zinc-ion batteries - Ling Zhong; Yimeng Yan; Zhixuan Ye; Xinxiang Zhang; Wenbin Yang; Jiaxian Zheng; Xiangfeng Lin; Linxin Zhang; Ge Zhou; Huiping Lin; Zhanhui Yuan (Chemical Engineering Journal, 2026)

Structural diversity of aldehydes determines covalent versus non-covalent inhibition mechanisms against steroid 5α-reductase type 1: Species-specific differences and preliminary structure-activity relationships - Junying Chen; Shufang Qi; Zijian Lin; Haonan Fang; Putian Zhang; Wanyu Li; Ren-shan Ge; Yiyan Wang (Chemico-Biological Interactions, 2026)

Screening and In Vivo Validation of Key Genes Involved in Myelin Damage in Alzheimer’s Disease - Hai-Tao Li; Ji-Wei Zhang; Bo-Wen Li; Hong-Yun Wu; Jin-Wen Ge; Da-Hua Wu; Quan-Lin Zhao; Ya-Han Wang (Molecular Neurobiology, 2026)

Quasi-individual-level analysis of urban green space accessibility: Disparities, determinants, and equity across neighborhoods - Chenyu Fang; Mei-Po Kwan; Lin Zhou; Ran Chen; Xing Liu; Shidong Ge (Urban Forestry & Urban Greening, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Deciphering the impacts of main inflowing rivers on dissolved organic matter in Lake Daye using isotopes, optical spectroscopy, and FT-ICR MS during non-flood season - Xiaowen Lin; Xiaodong Wu; Bingfa Chen; Xuguang Ge; Chao Wu; Xincai Gu; Shunmei Zhu; Zhenni Gao (Journal of Hydrology, 2025)

Mapping plasma metabolic profiles reflecting air pollution and their association with kidney failure: A prospective cohort study - Peng Hu; Shengtao Wei; Ge Chen; Lan Chen; Fei Tian; Zitong Zhuang; Manting Rao; Zhenhe Huang; Hualiang Lin (Journal of Hazardous Materials, 2025)

6PPD-Q driven rare and abundant taxa functional partitioning shapes soil ecological response - Xinwei Shi; Weitao Liu; Ruiying Shi; Yichen Ge; Xiang Li; Chuan Yin; Jinzheng Liu; Yuexing Zhao; Dasong Lin; Yuebing Sun (Journal of Hazardous Materials, 2025)

Performance and mechanism of polymorphic phosphorus removal by Fe/Al complexes with extracellular polymers derived from residual sludge - Jingyun Ge; Yasong Chen; Yunpeng Zhao; Benyi Xiao; Lin Li (Journal of Environmental Management, 2025)

Ag/AgCl@NH2-MIL-88B functionalized pH-responsive aerogel for enhanced organic pollutant removal via adsorption and photo-Fenton-like degradation synergy - Anrong Yao; Yafang Wang; Kai Wang; Haoyi Hu; Siyao Tian; Yeqian Ge; Lin Yang; Jiaojiao Shang; Jianwu Lan; Shaojian Lin (Journal of Environmental Chemical Engineering, 2025)

The stability of grassland spring phenology to extreme drought is modulated by radiation and biodiversity on the Tibetan Plateau - Wendu Rina; Yangjian Zhang; Xianzhou Zhang; Yunlong He; Ge Hou; Wenchao Wu; Wenyu Li; Lin Jiang; Juntao Zhu (Global and Planetary Change, 2025)

Machine learning intelligently selects feature values to construct a sensor array based on tri-functional Mn-doped covalent organic polymer nanozymes for identifying flavonoid compounds - Guo-Qi Zhang; Wen-Cai Jiang; Xiao-Mei Li; Ren-Jie Li; Yi Feng; Ri-Ge Li Nai; Hui-Lin Cheng; Zhi-Bo Hou; Xiao-Jun Luo; Yan Zhao (Food Chemistry, 2025)

Prenatal air pollution exposure and placental vasculature development among participants of the UPSIDE cohort study - Shivram Kumar; Carolyn M. Salafia; Ruchit Shah; Theresa Girardi; Richard K. Miller; Sally W. Thurston; Philip K. Hopke; David Skrill; Jessica Brunner; Donald Harrington; Yihui Ge; Yan Lin; et al. (Environmental Research, 2025)

Valorization of blueberry pomace and red mud to zero valent iron biochar for antibiotic degradation with diminishment of toxic reagents - Xu Su; Jie Han; Yuwei Huang; Xuanming Wang; Siyu Wang; Ziyi Ge; Hechong Yuan; Juying Liu; Xuerong Xiang; Fan Xia; Li Lin; Yu Lan; et al. (Bioresource Technology, 2025)

Pregnant PM2.5 exposure promotes uterine contractility via miR-200a-PGR-oxytocin signaling pathway leading to preterm birth - Jingyi Zhang; Shanshan Ran; Shengtao Wei; Zijun Yang; Huaicai Zeng; Guang Jia; Zhangjian Chen; Lan Chen; Fei Tian; Ge Chen; Zilong Zhang; Hualiang Lin (Atmospheric Environment, 2025)

Characterizing the mediating role of metabolic signatures in the associations between air pollution exposure and inflammatory bowel disease - Jiayue Zhang; Chengwei Chai; Lan Chen; Fei Tian; Ge Chen; Xiaojie Wang; Yin Yang; Hualiang Lin; Zilong Zhang (Atmospheric Environment, 2025)

Metabolomics Reveals Reasons for the Efficacy of Acupuncture in Migraine Patients: The Role of Anaerobic Glycolysis and Mitochondrial Citrate in Migraine Relief - Zishan Gao; Xianzhong Yan; Rui Wang-Sattler; Marcela Covic; Guang Yu; Feifei Ge; Jia Lin; Qin Chen; Juan Liu; Sapna Sharma; Sophie Molnos; Brigitte Kuehnel; et al. (Phenomics, 2025)
Acupuncture is used worldwide to treat migraine, but its scientific mechanism remains unclear. Here, we report a 1 H NMR metabolomics study involving 40 migraine patients and 10 healthy individuals randomly receiving acupuncture or sham acupuncture, followed by machine learning techniques and functional analysis. We found that acupuncture at acupoints particularly enhanced anaerobic glycolysis and modified mitochondrial function by adjusting the levels of plasma pyruvic acid ( p = 0.012), lactic acid ( p = 0.031) and citrate ( p = 0.00079) at a Bonferroni-corrected level of significance compared to the pre-treatment level of these three metabolites in migraine patients. Therefore, acupuncture supplies energy to migraine patients and relieves migraine attacks. In contrast, we observed that sham acupuncture may partially supply energy to migraine patients through lipid metabolism by changing the levels of plasma lipid ( p = 0.0012), glycerine ( p = 0.021), and pyruvic acid ( p = 0.047) at a Bonferroni-corrected level of significance. The functional network analysis further indicates this different way of supplying energy contributes to the different effects of acupuncture and sham acupuncture. Our findings reveal novel metabolic evidence for the specific effect of acupuncture in relation to sham acupuncture. This metabolic evidence could enlighten a brand new direction into acupuncture analgesia mechanism, which in turn would pose fresh challenges for future acupuncture research.

Statistical inferences of differences and correlations in the seismic frequencies of large-scale fault zones in Western Sichuan, China - Yuan Xue; Dan Hu; Junreng Ge; Xinyu Yao; Mingyue Dai; Bingyan Fan; Yu Ming; Muchen Lin (Journal of Seismology, 2025)

A novel PADI6 splice-site variant induces non-canonical GC-AG splicing and embryonic arrest in humans - Huiling Hu; Jiaqi Sun; Fei Meng; Fei Gong; Ge Lin; Lizhi Leng; Wei Zheng (Functional & Integrative Genomics, 2025)

Microalgae-based removal of pharmaceutically active compounds (PhACs) from wastewater: Mechanisms and applications - Ye Lin; Xue Pu; Jingyuan Xia; Xiyang Lu; Heyang Hu; Jiawei Bai; Fuyuan Guo; Shijian Ge; Shuang Qiu (Algal Research, 2025)

PM2.5 and NO2 exposure during pregnancy and measures of fetal size and attained size at birth - Nafisa Nawal Islam; Sally W. Thurston; Donald Harrington; Yihui Ge; Samuel Weisenthal; Jessica Brunner; Richard K. Miller; Philip K. Hopke; Yan Lin; Emily S. Barrett; Thomas G. O’Connor; Junfeng Zhang; et al. (Air Quality, Atmosphere & Health, 2025)

Research on Acoustic-Electrical Integrated Technology in Geothermal Resource Exploration, Development and Monitoring - Feng Chu; Rui Xu; Rong-hua Zhang; Yi-guo Xue; Deng-rui Wu; Lin-zhi Lang; Shu-ge Liu; Jing-kai Qu (Applied Geophysics, 2025)

Amplified impacts of tropical cyclone-induced compound wind-rain hazards on high-speed rail passengers - Hui Zhang; Youquan Ge; Jiayi Lin; Min Xu; Min Ouyang (Transportation Research Part D: Transport and Environment, 2025)

Effects of miR-200b-3p and miR-424–5p regulating notch signaling pathway on atherosclerosis induced by PM2.5 in vitro - Tianyang Zhao; Xu Li; Zhili Ge; Jingjing Shi; Tianyou Wang; Jiaxin Zhang; Xinyu Zhang; Huibin Jiang; Liting Zhou; Lin Ye (Toxicology, 2025)

Rapid and efficient stem segment regeneration propagation system for Euonymus bungeanus - Kai-Ge Cui; Hao-Lin Wang; Wen-Yue Quan; Zhuo-Zhuo Ye; Cheng-Ri Zhao (South African Journal of Botany, 2025)

Geotechnical reconnaissance of Hualien Port after the 2024 ML 7.2 hualien earthquake - Hsuan-Chih Yang; Chun-Jia Huang; Yung-Yen Ko; Kuan-Yu Chen; Chi-Chin Tsai; Chun-Hung Lin; Yu Wei Hwang; Min-Chien Chu; Yu-Syuan Jhuo; Yu-Ting Hsueh; Shodai Okano; LeeYi Wang; et al. (Soil Dynamics and Earthquake Engineering, 2025)

Parental permethrin exposure disrupts offspring metabolism via microbiota–tryptophan axis and is rescued by Lactobacillus plantarum Y1 - Jie Lin; Zexiu Qi; Ge Wang; Jusheng Zheng; Leqi Cui; Ye Peng; Quancai Sun (Journal of Hazardous Materials, 2025)

Enhanced insecticidal activity and bioavailability of thiacloprid from pH-responsive porous MPN(Fe)@ZIF-8 nanocarrier - Miao Wang; Donghui Xu; Ying Zhang; Jie Zhou; Zhihao Lin; Yiming Zhao; Xin Ding; Bin Sheng; Xiaobin Wen; Xiao Song; Ge Chen; Xiaomin Xu; et al. (Journal of Cleaner Production, 2025)

Aridity modulates the contribution of plant and soil diversity to grassland stability - Jiahe Zheng; Yangjian Zhang; Yunlong He; Ruonan Shen; Xiaorong Lu; Shaopeng Li; Ge Hou; Lin Jiang; Juntao Zhu; Yann Hautier (Global and Planetary Change, 2025)

Ambient ozone exposure and course of non-communicable diseases among elderly individuals with hypertension, diabetes or dyslipidemia: Prospective cohort study in GOLD-Health - Zitong Zhuang; Jiamin Chen; Weiquan Lin; Ge Chen; Menghe Wang; Zhengmin Min Qian; Peng Hu; Zhonghua Ai; Cai Zhang; Maya Kavuri; Stephen Edward McMillin; Yingying Fang; et al. (Environmental Pollution, 2025)

Effects of angles of attack on vortex-induced vibrations of a central-slotted box girder: Physical mechanisms via simplified-vortex models - Shuaikuang Chen; Chuanxin Hu; Lin Zhao; Shengyuan Liu; Yaojun Ge (Engineering Structures, 2025)

Experimental study, finite element simulation and theoretical analysis on punching shear capacity of steel-ECC composite slabs - Youzhu Lin; Di Yao; Ge Gao; Tianfei Gu; Ming Sun; Jiachuan Yan (Engineering Structures, 2025)

Chlorine-anion doping enhances the metal-oxygen covalency of Bi0.5Sr0.5FeO3-δ air electrode: achieving superior catalytic activity for reversible solid oxide cells - Hui Ye; Zhipeng Miao; Yanfeng Fu; Pengkai Shan; Bin Qian; Lin Ge; Han Chen; Yifeng Zheng; Sheng Cui (Chemical Engineering Journal, 2025)

General strategy for efficient persistent RTP polymer over 3 s: luminophore with a moderate θn-π angle - Danman Guo; Tong Zou; Yiling Miao; Jinzheng Chen; Zhu Chen; Xiangyu Ge; Faxu Lin; Yi Zhang; Zhenguo Chi; Zhiyong Yang; Huahua Huang (Chemical Engineering Journal, 2025)

Co-encapsulation of an AKT Inhibitor Enhances the Tumor-cell Selectivity of STING Agonists in Co-delivery Liposomes - Ziyu Ge; Qiang Zhang; Yuming Wang; Lin Miao; Xinqi Wang; Ni Fan; LiLi Duan; Yunfei Li; Xue-Jie Qi (Pharmaceutical Research, 2025)

Utilizing UAV-based high-throughput phenotyping and machine learning to evaluate drought resistance in wheat germplasm - Xiaojing Zhu; Xin Liu; Qian Wu; Mengshi Liu; Xueli Hu; Hui Deng; Yun Zhang; Yunfeng Qu; Baoqi Wang; Xiaoman Gou; Qiongge Li; Changsheng Han; et al. (Computers and Electronics in Agriculture, 2025)

The role of endoplasmic reticulum stress in Atrazine-induced hepatic lipid accumulation - Honghao Qian; Shuping Ren; Haotang Zhao; Jingjing Shi; Zhili Ge; Jiaxin Zhang; Tianyou Wang; Xinyu Zhang; Huibin Jiang; Yuezhu Zhang; Lin Ye (Toxicology Letters, 2025)

A novel cotton miR7814 targeting GhCNL2 regulates plant defense against Verticillium dahliae infection - Lin Xu; Ye Tang; Ge Zhao; Zhennan Zhang; Xiaoqiong Zhang; Wenwen Liu; Qingzhong Peng; Jiahe Wu (Plant Science, 2025)

Hydrogel-engineered platforms for efficient solar interfacial evaporation: Current status and future directions - Junnan Jiang; Heyu Jin; Yao Lu; Xiaohua Liu; Hongyu Ge; Lin Mu (Journal of Water Process Engineering, 2025)

Assessment of environmental and health impacts during 3D printing of candidate polymeric materials for space additive manufacturing - Junling Li; Yi Liu; Chao Peng; Qifan Liu; Wei Zhao; Mingyuan Liu; Xinyu Du; Yongyin Yan; Yufei Song; Kaihui Xia; Chun Chen; Haijie Zhang; et al. (Journal of Hazardous Materials, 2025)

Mercapto-modified layered double hydroxide: High-efficiency emerging amendment for cadmium immobilization in cadmium-contaminated acidic and alkaline soil - Xusheng Gao; Xilin Chen; Yifei Shu; Kexin Chen; Ge Gao; Xiaomin Liu; Qingqing Huang; Lin Wang; Yuebing Sun; Yujie Zhao; Xuefeng Liang (Journal of Hazardous Materials, 2025)

Performance and mechanism study for 2-octanol oxidation by ozone in synergy with biochar supported manganese-based mullite catalysts - Lin Zhang; Huanzhen Zuo; Tong Wei; Wenming Pei; Xinsheng Zhu; Feng Ge; Kegui Zhang (Journal of Environmental Chemical Engineering, 2025)

Preparation of MCM-22/ZSM-5 core–shell structured zeolite for catalytic cracking of polyethylene to selectively produce paraxylene - Hucheng Ge; Yufei Gu; Feifei Liu; Yanmei Huang; Yuke Liu; Silin Wu; Yunshuang Hu; Zhixia Li; Hongfei Lin (Fuel, 2025)

Long-term gap regeneration processes in a primary temperate forest of Northeast China: Evidence from integrated multi-temporal remote sensing and field surveys - Danni Wu; Deliang Lu; Chunyu Zhu; Xiaowen Ge; Litao Lin; Tian Gao; Jiaojun Zhu (Forest Ecology and Management, 2025)

Smartphone-assisted ultrasensitive colorimetric strategy based on Cu-CN single-atom nanozyme for acrylamide detection in fried food - Jia Ge; Xiaoyu Sun; Xinxin Li; Yu Yang; Lin Zhang; Lingbo Qu; Zhaohui Li (Food Chemistry, 2025)

In vitro simulated digestion and fermentation characteristics of pumpkin polysaccharides and their effects on the human gut microbiota - Kejuan Li; Chun Wang; Jiajun Li; Hongyuan Cao; Qi Li; Lihong Ge; Yuanting Zhu; Yuzhi Miao; Chen Xia; Changbin Lin (Food Chemistry, 2025)

Genome-based screening and immunogenicity evaluation of outer membrane protein antigens for Vibrio harveyi subunit vaccine in pearl gentian grouper (Epinephelus lanceolatus × Epinephelus fuscoguttatus) - Fuyan Li; Hui Ge; Peng Lin; Yilei Wang; Yonghua Jiang; Ziping Zhang; Yun Chen; Jianjun Feng (Fish & Shellfish Immunology, 2025)

Vegetation-driven differences in soil CO2 emissions and carbon-sequestering microbiomes of estuarine salt marsh and mangrove wetlands - Lin Wang; Yangyang Xie; Weiqi Wang; Yuan Li; Ning Hou; Rongbin Yin; Zhaoliang Song; Jordi Sardans; Maoquan Ge; Yiyang Liao; Derrick Y.F. Lai; Josep Peñuelas (Environmental Research, 2025)

Differential electric field homogenization postponed dendrite formation of zinc anodes at limiting current for long-life aqueous zinc batteries - Yin Yang; Xin Chen; Jingying Li; Jia Yao; Yi Gan; Junjie Zheng; Luyang Ge; Lin Lv; Li Tao; Jun Zhang; Hanbin Wang; Hao Wang; et al. (Chemical Engineering Journal, 2025)

Development of a multifunctional and biocompatible hydrogel for flexible implantable sensors - Kaiqi Zhang; Huibiao You; Yuxi Liu; Fulei Lin; Yanan Li; Lina Jia; Jinxiao Bao; Xin Ge; Gaofei Pan; Huitao Yu; Ruiguang Xing (Chemical Engineering Journal, 2025)

Red blood cell-mimetic hollow covalent organic framework with oxygen-replenishing and cavitation-amplified for enhanced sonodynamic therapy of periodontitis - Yang Zhou; Qiyuan Pan; Ruolin Wang; Yan Ge; Xiao Zhang; Yifan Guo; Rongyin Sun; Xianglong Liu; Sainan Liu; Min Liu; Jun Lin (Chemical Engineering Journal, 2025)

Corrigendum to “Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices” [Chem. Eng. J. 510 (2025) 161390/CEJ 161390] - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

Organotins as inhibitors targeting human and rat steroid 5α-reductase 1: structure-activity relationship and docking analysis - Shufang Qi; Rong Cui; Wanyu Li; Jin Yang; Ke Zheng; Shaowei Wang; Ren-Shan Ge; Han Lin; Yiyan Wang (Chemico-Biological Interactions, 2025)

Chemotaxonomically significant phytochemicals with α-glucosidase and tyrosinase inhibitory activities from Chinese endemic plant Ophiorrhiza hunanica - Qing Bu; Qi-Bin Yang; Can-Qi Liu; Zeng-Yue Ge; Xiao-Wen Liao; Lei Wu; Lin-Fu Liang (Natural Product Research, 2025)

Nitrogen doping enhances PMS activation by MnFe2O4-NBC through generating active sites and establishing an internal electric field - Xiaoni Lin; Qiang Ge; Xianbo Zhou; Yan Wang; Congyun Zhu; Kuanyong Liu; Jinquan Wan (Journal of Water Process Engineering, 2025)

Metabolomic profiling unveils biochemical dynamics in spontaneously fermented grape leaf by-products: towards sustainable agricultural waste valorization - Jia-Lin Xing; Yun-Lu Song; Yan-Ge Li; Lu Yang; Ke-Ying Duan; Ding-Ding Zuo; Jing Zhang; Hai-Nan Liu; Tong-Lu Wei; Mao-Song Pei; Da-Long Guo (Food Bioscience, 2025)

Chitosan/kudzu-based packaging films synergistically reinforced by paeonol@ZIF-8 and Ag2CO3/Ag2O nano-heterojunctions for raspberry preservation - Xin Ding; Yiming Zhao; Xin Chen; Yanyan Huang; Zhihao Lin; Jing Wang; Ge Chen; Guangyang Liu; Xiaomin Xu; Bining Jiao; Xijuan Zhao; Donghui Xu (Food Packaging and Shelf Life, 2025)

Evolutionary characteristics of vortex drift patterns around a central-slotted box girder during torsional vortex-induced vibration and its physical mechanism - Chuanxin Hu; Shuaikuang Chen; Lin Zhao; Xianglong Wang; Shengyuan Liu; Yaojun Ge (Engineering Structures, 2025)

Seismic resilience realization for self-centering structures via deep reinforcement learning - Zhichao Lin; Longhe Xu; Xingsi Xie; Ge Zhang (Engineering Structures, 2025)

Efficient perfluorooctanoic acid degradation using by a vacuum ultraviolet-activated dithionite reduction system: Reactive species, process optimization, degradation pathways, and toxicity changes - Jinmin Su; Tao Lin; Yuchen Wang; Han Chen; Xinran Ge (Chemical Engineering Journal, 2025)

Highly efficient orange-red multiple resonance hot exciton fluorescence emitters based on indolo[2,3-b]pyrazine derivatives - Bohong Liu; Zhizhi Li; Deli Li; Lin Wu; Tao Wang; Denghui Liu; Shi-Jian Su; Wei Li; Ziyi Ge (Chemical Engineering Journal, 2025)

Properties of rich-Nae effect and reversible oxygen redox with a complete solid-solution sodium-storage behavior - Wei Zhao; Shao-Hua Luo; Yicheng Lin; Guodong Hao; Rui Huang; Pengyu Li; Ge Wang; Jun Cong; Shengxun Yan; Lixiong Qian (Chemical Engineering Journal, 2025)

Magnetic characteristics of sediments in the northern Yangtze River delta since MIS3 and their responses to palaeoenvironmental changes - Guiye Zhang; Longsheng Wang; Xiaohui Wang; Shouyun Hu; Mingming Ma; Jiawen Zhao; Yanjun Ge; Lin Zeng; Xianbin Liu; Chao Zhan; Qing Wang (CATENA, 2025)

A practice guideline for therapeutic drug monitoring of mycophenolic acid for solid organ transplants - Shuang Liu; Hongsheng Chen; Zaiwei Song; Qi Guo; Xianglin Zhang; Bingyi Shi; Suodi Zhai; Lingli Zhang; Liyan Miao; Liyan Cui; Xiao Chen; Yalin Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2025)
Mycophenolic acid (MPA), the active moiety of both mycophenolate mofetil (MMF) and enteric-coated mycophenolate sodium (EC-MPS), serves as a primary immunosuppressant for maintaining solid organ transplants. Therapeutic drug monitoring (TDM) enhances treatment outcomes through tailored approaches. This study aimed to develop an evidence-based guideline for MPA TDM, facilitating its rational application in clinical settings. The guideline plan was drawn from the Institute of Medicine and World Health Organization (WHO) guidelines. Using the Delphi method, clinical questions and outcome indicators were generated. Systematic reviews, Grading of Recommendations Assessment, Development, and Evaluation (GRADE) evidence quality evaluations, expert opinions, and patient values guided evidence-based suggestions for the guideline. External reviews further refined the recommendations. The guideline for the TDM of MPA (IPGRP-2020CN099) consists of four sections and 16 recommendations encompassing target populations, monitoring strategies, dosage regimens, and influencing factors. High-risk populations, timing of TDM, area under the curve (AUC) versus trough concentration ( C 0 ), target concentration ranges, monitoring frequency, and analytical methods are addressed. Formulation-specific recommendations, initial dosage regimens, populations with unique considerations, pharmacokinetic-informed dosing, body weight factors, pharmacogenetics, and drug–drug interactions are covered. The evidence-based guideline offers a comprehensive recommendation for solid organ transplant recipients undergoing MPA therapy, promoting standardization of MPA TDM, and enhancing treatment efficacy and safety.

Synthesis of ZIF-8 Coated MnO2 Functionalized Antibacterial Peptide Nanoparticles and Its Antibacterial and Wound-Healing Promotion Studies - Mengzhu Xiao; Yujia Wu; Wanzhen Li; Jun Wang; Weiwei Zhang; Lin Gui; Fei Ge (Current Microbiology, 2025)

Correction: Giant diatom blooms driven by deep water upwelling since late MIS3? Evidence from the rim of the Mariana Trench - Junyu Lin; Dong Xu; Yue Li; Liming Ye; Qian Ge; Yeping Bian; Xibin Han; Weiyan Zhang; Shenghui Cheng (Frontiers in Marine Science, 2025)

Integrative analysis of copper dysregulation and cuproptosis in postnatal hematopoiesis - Liyun Chen; Qian Wu; Chaohui Lin; Zijun Song; Yunxing Su; Chaodong Ge; Xue Wang; Hongbing Luo; Rong Wang; Yanfang Wang; Junxia Min; Fudi Wang (Science Bulletin, 2025)

A novel adaptive similarity-based ecological niche model for the endangered Yunnan snub-nosed monkey (Rhinopithecus bieti) using UAV LiDAR data - Guoshuai Hou; Xin Shen; Sang Ge; Yong Zhang; Lin Cao (Remote Sensing of Environment, 2025)

A new strategy for removing insecticide etoxazole from soil using a combination of a novel Paracoccus versutus Y4 and a fungal mycelium carrier - Man Xu; Xue Luo; Xin-Li Yan; Xiao-Yu Cai; Lin-Lin Wang; Feng Ge; Hong-Wei Wang (Journal of Hazardous Materials, 2025)

Passion fruit peel pectin improves glucose and lipid metabolism in high-fat diet-induced obesity through gut microbiota and insulin sensitivity regulation - Ying Ju; Liling Huang; Hailing Luo; Yongcai Huang; Xianya Huang; Ge Chen; Jie Gui; Shengli Lin; Xuzhou Liu; Liu Yang (Food Bioscience, 2025)

Synergistic effects of air pollution and artificial light at night on diabetes risk: A prospective cohort study - Desong Wen; Fei Lin; Chaowei Zhang; Ziyu Ge; Xiaohang Li; Zhenzhou Liu; Hanqing Zhao; Weimin Wang; Zhigang Chen; Guoan Zhao (Environmental Pollution, 2025)

GMNN mutations cause female infertility characterized by preimplantation embryo arrest through regulating DNA re-replication - Honghui Zhang; Wei Su; Xiaohong Jiang; Yang Wang; Bohan Yang; Xian Wan; Cheng Li; Shuai Zhao; Changlong Zhang; Shigang Zhao; Yuehong Bian; Mei Li; et al. (Science China Life Sciences, 2025)

hsa_circ_0099682 exacerbates the development of diabetic retinopathy by promoting pathological neoangiogenesis via the miR-125b-5p/HNRNPU axis - Ge Yang; Mei Xu; HongWei Zhang; Bo Zhang; YuLian Xie; YueHua Chen; Qin Hu; ZiYu Luo; Jie Lin; ZhengWen Qin (Journal of Molecular Histology, 2025)

Associations of Metal Mixtures with Lipid Profiles: Exploring the Mediating Role of Testosterone in a Cross-Sectional Study - Sencai Lin; Ying Yang; Junxiu He; Sihan Hu; Yu Bao; Xiaoting Ge; Xiaobo Yang (Biological Trace Element Research, 2025)

Combined exposure of sleep deprivation and environmental particulate matter drives aging in multiple systems - Lu Yu; Chihang Zhang; Biao Wu; Jianshu Guo; Dongxia Fan; Ge Wang; Wenqing Zhang; Lin Lin; Xinlei Xu; Xihao Du; Xiao-yong Zhang; Yuquan Xie; et al. (Journal of Hazardous Materials, 2025)

Experimental study on shear behavior of square RC columns wrapped with CFRP strips under lateral static and pendulum impact loadings - Tao Liu; Rong Ge; Feifan Feng; Lin Chen; Hong Hao (Engineering Structures, 2025)

Maternal transcription factor OTX2 directly induces SETD1A and promotes embryonic genome activation in human pre-implantation embryos - Tianlei Zhang; Ziyan Peng; Fei Meng; Zhuo Li; Junru Chen; Qinwei Zhou; Lizhi Leng; Hao Bo; Guangxiu Lu; Yun Deng; Feng Gu; Ge Lin (Science China Life Sciences, 2025)

Identification of Mood Disorders Causal Genes by Integrating the Brain Proteome and Transcriptome - Rong-kun Zhu; Hong-jian Zhou; Jun Shi; Ling Ge; Yi Lin; Wen-hao Yin; Hui Zeng; Xiong-wei Wang (Molecular Neurobiology, 2025)

Increasing importance of regional emission controls for further reduction of PM2.5 in Beijing - Lingkai Dong; Weili Lin; Zhiqiang Ma; Wei Wang; Lei Kong; Xiaobin Xu; Oliver Wild; Yuanlin Wang; Baozhu Ge; Zifa Wang (Urban Climate, 2025)

Design of GO@TiO2 and PDA@CNC decorated gelatin aerogel for efficient adsorption and photocatalytic degradation of organic pollutants - Chang Liu; Anrong Yao; Wei Li; Qian Xu; Lin Yang; Yeqian Ge; Jianwu Lan; Shaojian Lin; Jinghong Qiu (Journal of Water Process Engineering, 2025)

Inorganic arsenic in aquatic products in Shenzhen, China from 2018 to 2024: Levels, temporal variation and health risk assessment - Bo Fu; Kai Lin; Sisi Yu; Yiming Ge; Xinjie Li; Wenchao Zhu; Lei Tan; Rui Wang; Jixi Ou; Shaoyou Lu (Food and Chemical Toxicology, 2025)

State augmentation method for multimode nonstationary vibrations of long-span bridges under extreme winds - Simian Lei; Wei Cui; Luca Patruno; Stefano de Miranda; Lin Zhao; Yaojun Ge (Engineering Structures, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

HDAC9 Deficiency Upregulates cGMP-dependent Kinase II to Mitigate Neuronal Apoptosis in Ischemic Stroke - Haoran Lin; Yun Bei; Zexu Shen; Taofeng Wei; Yuyang Ge; Lingyan Yu; Huimin Xu; Wei He; Yunjian Dai; Difei Yao; Haibin Dai (Translational Stroke Research, 2025)

Giant diatom blooms driven by deep water upwelling since late MIS3? Evidence from the rim of the Mariana Trench - Junyu Lin; Dong Xu; Yue Li; Liming Ye; Qian Ge; Yeping Bian; Xibin Han; Weiyan Zhang; Shenghui Cheng (Frontiers in Marine Science, 2025)
Laminated Diatom Mats (LDMs) in the low-latitude Western Pacific provide key insights into global climate and carbon cycling. While Ethmodiscus rex ( E. rex ) LDMs research has advanced, two critical aspects remain to be elucidated: (1) the precise chronology of LDMs formation, and (2) its relationship with oceanic circulation patterns and associated nutrient flux variations. In this study, we employed AMS 14 C dating coupled with carbonate content variations to constrain the formation age of LDMs, complemented by comprehensive geochemical and clay mineral analyses of core E20, we found: (1) Diatom blooms occurred mainly from Last Glacial Maximum (LGM) to early Holocene; (2) Sediments are mostly volcanic, with increased material in E. rex layers suggesting stronger deep currents transported volcanic debris; (3) Blooms weren’t solely caused by Asian dust-derived nutrients. We propose deep current intensification and topographic upwelling drove diatom growth, highlighting deep ocean processes’ role in surface productivity and LDMs formation. This advances understanding of their climate and carbon cycle significance.

Dual pathways of carbon neutrality in urban green spaces: assessment and regulatory strategies - Yuan Feng; Chenyu Fang; Xiaoli Jia; Peihao Song; Lin Zhou; Xin Xu; Kun Wang; Ruizhen He; Nan Guo; Shidong Ge (Sustainable Cities and Society, 2025)

Aged microplastics-induced growth inhibition via DNA damage, GH/IGF-1 and HPT axes disruption in zebrafish larvae - Qing Ge; Tong Zheng; Ping Ding; Zhenyuan Li; Xihua Lin; Xintong Li; Miao He; Guocheng Hu (Science of The Total Environment, 2025)

Nighttime reactions of a series of unsaturated alcohols with NO3•: Kinetics, products and mechanisms study - Yanyong Xu; Shengrui Tong; Weiran Li; Meifang Chen; Lin Hu; Hailiang Zhang; Sufan Wang; Maofa Ge (Journal of Environmental Sciences, 2025)

Changes in quality, endogenous enzyme activities, and their relationships during post-harvest storage of Phlebopus portentosus- an edible fungus - Qinglong Kong; Songyi Lin; Ruixue Wang; Siqi Chen; Kailun Ge; Dong Chen (Food Chemistry, 2025)

Dynamics of chemical profile and microbial community in 3 consecutive years reveal Rhodococcus and Apiotrichum are potential microbes contributing to quality formation of Guang Chenpi - Fang Li; Kaiying Ge; Yi Lu; Hui Lin; Enwei Tian; Hua Li; Zhiye Yang; Zhi Chao (Food Chemistry, 2025)

Microbial strategies regulate organic carbon accumulation in saline paddy soils: A millennium chronosequence - Dan Cao; Xiangxiang Wang; Yi Miao; Chuanfa Wu; Haoqing Zhang; Shuang Wang; Feng Wang; Lin Chen; Chao Liang; Yakov Kuzyakov; Jianping Chen; Tida Ge; et al. (CATENA, 2025)

A state-of-the-art empirical round robin validation of heat, air and moisture (HAM) models - Xinyuan Dang; Ana Sofia Guimarães; Andreas Sarkany; Anssi Laukkarinen; Bingyu Xu; Bruno Vanderschelden; Carsten Rode; Changchang Xia; Chi Feng; Chris Whitman; Daan Deckers; Hanyu Yang; et al. (Building and Environment, 2025)

An improved U-Pb dating method for carbonates via LA-SF-ICP-MS mapping and its applications - Lili Gui; Xuesong Lu; Fangyue Wang; Can Ge; Lin Jiang; Shaobo Liu; Wuren Xie; Weiyan Chen; Junjia Fan; Hai Wu; Saijun Wu; Yingying Wang; et al. (Science China Earth Sciences, 2025)

Mitogenomic and Phylogenetic Analyses of Lysmata lipkei (Crustacea: Decapoda: Lysmatidae) - Xixi Zhang; Zhihuang Zhu; Jianxin Wang; Ge Shi; Qi Lin (Fishes, 2025)
This study aims to elucidate the characteristics of the mitogenome of Lysmata lipkei and investigate its phylogenetic relationships. Using both the Illumina NovaSeq 6000 (Illumina, Inc., San Diego, CA, USA) and PacBio Sequel II (Pacific Biosciences of California, Inc., Menlo Park, CA, USA) platforms, the complete mitogenome sequence of L. lipkei was determined. The mitogenome of L. lipkei was annotated, measuring 17,497 bp in length and comprising 13 protein-coding genes (PCGs), 2 ribosomal RNA genes (rRNAs), and 22 transfer RNA genes (tRNAs). The nucleotide composition of the genome exhibited an AT bias of 63.4%. Among the PCGs, the most frequently used codon was UUA. All tRNAs, except for trnD, which lacks the TψC loop, were capable of forming the typical cloverleaf structure. Phylogenetic trees for Caridea were constructed using Bayesian Inference (BI) and Maximum Likelihood (ML) methods based on the nucleotide sequences of the 13 PCGs. Both methods yielded consistent topological structures, with L. lipkei showing the closest phylogenetic relationship to L. kuekenthali. Additionally, Lysmatidae, Thoridae, and Hippolytidae formed a monophyletic clade. This research not only filled the gap in mitogenome data for Lysmatidae but also provided novel molecular insights into Caridean phylogenetics.

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Long-term exposure to fine particulate matter constituents and the prognosis of oral cancer patients: A prospective study in Southeastern China - Peng Hu; Liling Shen; Ge Chen; Weiyi Yang; Yanmei Ji; Baochang He; Hualiang Lin (Journal of Hazardous Materials, 2025)

Microencapsulation of Pickering nanoemulsions containing walnut oil stabilized using soy protein–curcumin composite nanoparticles: Fabrication and evaluation of a novel plant-based milk substitute - Chenxing Du; Hanwen Hu; Ge Zhu; Zhangqun Duan; Yizhong Shen; Lin Lin; Jianfeng Lu; Zhi Zheng (Food Chemistry, 2025)

Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

Retraction notice to “Valorization of tropical fruits waste for production of commercial biorefinery products – A review” [Bioresour. Technol. 374 (2023) 128793] - Zheli Ding; Yu Ge; Taner Sar; Vinay Kumar; Sharareh Harirchi; Parameswaran Binod; Ranjna Sirohi; Raveendran Sindhu; Peicong Wu; Fei Lin; Zengqiang Zhang; Mohammad J. Taherzadeh; et al. (Bioresource Technology, 2025)

Retraction notice to “Production of biochar from tropical fruit tree residues and ecofriendly applications – A review” [Bioresour. Technol. 376 (2023) 128903] - Zheli Ding; Yu Ge; Sarath C. Gowd; Ekta Singh; Vinay Kumar; Deepshi Chaurasia; Vikas Kumar; Karthik Rajendran; Preeti Chaturvedi Bhargava; Peicong Wu; Fei Lin; Sharareh Harirchi; et al. (Bioresource Technology, 2025)

Lifetime exposure to health-related air pollutants in the United Kingdom: A spatiotemporal evaluation (1930–2010) through WRF-CMAQ modeling - Ge Chen; Yiming Liu; Haofan Wang; Menghe Wang; Lan Chen; Hejun Hu; Shiyu Zhang; Baozhuo Ai; Miao Cai; Zilong Zhang; Qi Fan; Hualiang Lin (Atmospheric Environment, 2025)

Decade-long application of preimplantation genetic testing for DMD/BMD: analysis of five clinical strategies and embryo recombination patterns - Weili Wang; Jing Dai; Xiao Hu; Wenbin He; Yifan Gu; Zhenxing Wan; Yi Zhang; Keli Luo; Wen Li; Qianjun Zhang; Fei Gong; Guangxiu Lu; et al. (Human Genetics, 2025)

Association of Blood Metals and Metal Mixtures with the Myocardial Enzyme Profile: An Occupational Population-Based Study in China - Xiaoting Ge; Junxiu He; Yuan Zheng; Qiuyue Wang; Hong Cheng; Yu Bao; Sencai Lin; Xiaobo Yang (Biological Trace Element Research, 2025)

Analysis of Increased False-Positive ELISA Results for HIV in the Blood of Donors Infected with SARS-CoV-2 - H. Lin; Z. Wang; Q. Ren; Z. Cai; F. Ge; W. Yuan; T. Liao; Y. Wu; R. Peng; Y. Gu; Y. Kuang (Bulletin of Experimental Biology and Medicine, 2025)

The Influence of Heterogeneous Processes on the Physicochemical Properties of Atmospheric Aerosols - Maofa Ge; Shengrui Tong; Lin Du; Lingyan Wu; Ting Lei; Kun Li; Minglan Xu; Narcisse T. Tsona; Wenqian Zhang; Hailiang Zhang (Advances in Atmospheric Sciences, 2025)
With the rapid development of the world economy, complex air pollution has increasingly become a serious threat; for example, with haze events occurring frequently in various regions of the globe. Recent evidence has indicated that secondary aerosols play an important role in haze formation, and that heterogeneous processes are among the main forces driving their explosive growth. In this regard, this paper reviews recent advances in the understanding of the impact of heterogeneous processes on haze chemistry, including the impact on NO 2 chemistry, marine aerosols, and the hygroscopicity and optical properties of atmospheric aerosols. It is distinguished from past reviews on this topic by focusing mainly on new insights from the past five years. We summarize the main findings of the impacts of heterogeneous processes on NO 2 chemistry, marine aerosols, and the physicochemical properties of atmospheric aerosols, and propose several future research directions.

Redox condition changes in the Ross Sea, Antarctica, since the last glacial maximum - Yizhuo Wang; Yi Zhang; Xibin Han; Li Lin; Yukai Hong; Rui Han; Yun Liu; Pengyun Ma; Qian Ge; Xiaohu Li (Acta Oceanologica Sinica, 2025)

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

Burned-area sub-pixel mapping based on spatial–spectral information at super-pixel scale for multi-spectral image - Jun Du; Peng Wang; Shuanglin Zhao; Caiping Hu; Lin Ge; Xunqiang Gong (International Journal of Remote Sensing, 2025)

The Combined Effects of Cadmium and Microplastic Mixtures on the Digestion, Energy Metabolism, Oxidative Stress Regulation, Immune Function, and Metabolomes in the Pearl Oyster (Pinctada fucata martensii) - Jiaying Yao; Zixin Gao; Zhixiang Wang; Zhanbo Ge; Yujing Lin; Luomin Huang; Jiaen Liu; Heqi Zou; Chuangye Yang; Robert Mkuye; Yuewen Deng (Fishes, 2025)
The accumulation of cadmium (Cd) and microplastics (MPs) can have major deleterious effects on the health of marine ecosystems and organisms, including the pearl oyster Pinctada fucata martensii. Here, we characterized the effects of Cd and MPs on key biochemical parameters of P. f. martensii via an experiment with various treatments. Pearl oysters were exposed to either only Cd (5 or 50 μg/L), only MPs (5 mg/L), or both Cd and MPs for 2 d, and this was followed by a 5-day recovery period. Measurements of the activities of lipase, amylase, protease, T-ATPase, catalase, glutathione peroxidase, acid phosphatase, and alkaline phosphatase enzymes, as well as the malondialdehyde content in the hepatopancreas, were made at various time points during the experiment. Metabolomics analysis of the gills was also performed. Significant interactions between time and treatment on lipase, protease, and catalase activities were observed. However, no significant effect of time–treatment interactions on amylase and T-ATPase activities was observed. Enzyme activities varied among groups both during the exposure period (6 to 48 h) and the recovery period. The malondialdehyde content was also increased throughout the experiment. Pathway analysis indicated that the purine metabolism, glycerophospholipid metabolism, nucleotide metabolism, arachidonic acid metabolism, neuroactive ligand–receptor interaction, and linoleic acid metabolism pathways were the most commonly affected under different treatments. The findings of our study revealed the differential effects of exposure time and treatment on enzyme activities and metabolites and their respective pathways. Our findings enhance our understanding of the biochemical responses of the pearl oyster P. f. martensii to environmental stressors, particularly Cd and MPs.

Effects of melatonin on the pharmacokinetics and amino acid metabolism profile of vigabatrin in rats - Qiang Zheng; Song-Lin Xu; Xin-Lin Guo; Chuan-Yu Wang; Meng-Die Ma; Jin-Fang Ge (Toxicology and Applied Pharmacology, 2025)

NAT10 primes a post-transcriptional repertoire essential for the maintenance of spermatogonial homeostasis - Xiaoli Zhu; Caoling Xu; Xue Jiang; Jiaqi Zou; Wenqing Li; Xuemei Xing; Xiaoxiao Gao; Jiao Lei; Fei Meng; Xin Wang; Yuzhang Zhu; Yu Cheng; et al. (Science Bulletin, 2025)

Corrigendum to ‘Facile synthesis of flower-cluster ZIF nanocarriers: Performance in controlled release of thiamethoxam and insecticidal activity’ [Environ. Res. 268 (2025) 120753] - Xin Ding; Kexin Yang; Xin Yang; Jie Zhou; Miao Wang; Zhihao Lin; Yaowei Zhang; Donghui Xu; Bining Jiao; Ge Chen; Xiaomin Xu; Lin Qin; et al. (Environmental Research, 2025)

Facile synthesis of flower-cluster ZIF nanocarriers: Performance in controlled release of thiamethoxam and insecticidal activity - Xin Ding; Kexin Yang; Xin Yang; Jie Zhou; Miao Wang; Zhihao Lin; Yaowei Zhang; Donghui Xu; Bining Jiao; Ge Chen; Xiaomin Xu; Lin Qin; et al. (Environmental Research, 2025)

Interactive effects of air pollutants and viral exposure on daily influenza hospital visits in Mongolia - Yihui Ge; Yan Lin; Oyu Tsogtbayar; Ser-Od Khuyagaa; Eelin Khurelbaatar; Jargalsaikhan Galsuren; Lauren Prox; Shiyu Zhang; Robert M. Tighe; Gregory C. Gray; Junfeng Zhang; Daramragchaa Ulziimaa; et al. (Environmental Research, 2025)

Late Oligocene formation of the Qaidam Basin revealed by calcite U-Pb dating: Insights into the northward growth of Tibetan Plateau - Mengjia Ge; Lei Wu; Shitou Wu; Xuhang Li; Renjie Zhou; Xiubin Lin; Ancheng Xiao; Shufeng Yang; Hanlin Chen (Earth and Planetary Science Letters, 2025)

Improving the catalytic activity and sintering resistance of Ni-BaCe0.7Zr0.1Y0.1Yb0.1O3−δ cermet anode for ammonia-fueled protonic ceramic fuel cells via Cobalt addition - Bangze Wu; Xiaole Yu; Zenan Zhao; Bingyu He; Zhanheng Jin; Zhexiang Yu; Qing Ni; Shoucheng He; Han Chen; Yifeng Zheng; Sheng Cui; Lin Ge (Chemical Engineering Journal, 2025)

Biocompatible and stretchable chitosan piezoelectric gel with antibacterial capability and motion monitoring function for Achilles tendon rupture treatment - Zhencheng Xiong; Bingqing Lin; Cheng Huang; Ao Duan; Chaoyi Zhang; Guangliang Qiang; Wenzheng Liu; Renliang Zhao; Xiangtian Deng; Dong Wang; Zilu Ge; Guanglin Wang; et al. (Carbohydrate Polymers, 2025)

Heterogeneous Fenton-like catalysts of tetranitro iron phthalocyanine@Fe3O4@fly ash composites for fast decomposition of environmental contaminants - Dapeng Li; Peng Zhang; Yang Jin; Qing Li; Xinyuan Li; Ruirui Chang; Ruoxi Ma; Lin Yan; Suxiang Ge; Juntao Ma (Waste Disposal & Sustainable Energy, 2025)
Using fly ash (FA) solid wastes as economical carriers to construct Fenton-like catalytic composites with additional functions is more practical than the use of a single catalyst. Understanding the structure and properties of catalysts and carriers is vital to improve performance. Tetranitro iron phthalocyanine (TNFePc) is a highly active molecular catalyst, whose immobilization and Fenton-like heterogeneous catalysis remain unclear. In this study, magnetically recyclable composites of TNFePc@Fe 3 O 4 @FA were successfully fabricated. Further, Fe 3 O 4 nanocrystals decorated on FA surfaces could be used as special functional layer for composite recycling and simultaneous in situ TNFePc synthesis. Peroxides of H 2 O 2 , KHSO 5 , and tert-butyl hydrogen could be effectively activated by composites and transformed into highly reactive radicals. Moreover, molecular oxygen could be activated as well. Model pollutants, methylene blue and oxytetracycline, could be synergistically degraded by the radical oxidation of superoxide, hydroxyl, alkoxy, and sulfate radicals and non-radical oxidation of high-valent iron-oxo species of TNPcFe IV =O. To the best of our knowledge, this is the first design of FA-based composites with dual function, Fenton-like heterogeneous catalysis and magnetic recyclability, for environmental decontamination. Graphical abstract

Correction to: Scorpion Venom Heat-Resistant Peptide is Neuroprotective Against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2025)

Effects of biochar and compost on the bioavailability of heavy metals in soil aggregates with varying particle sizes - Fanghong Li; Shilin Jiang; Ge Chen; Dan Wan; Liuqin He; Jiachao Zhang; Keqi Zhao; Hongli Huang; Lin Luo; Genyi Wu; Lihua Zhang (Journal of Soils and Sediments, 2025)

Revisiting the future changes in precipitation extremes over the Eastern Tibetan Plateau: from the thermodynamic–dynamic processes to model uncertainty - Kangning Wang; Quanliang Chen; Fei Ge; Zhiye Lin (Climate Dynamics, 2025)

Investigation on neutronics changes in tungsten granular blockage accident on VENUS-II light water reactor - Liang Chen; Wei Jiang; Zhao-Dong Xia; Fei Ma; Rui Yu; Hai-Yan Meng; Qi Zhou; Hong-Lin Ge; Yan-Bin Zhang; Xue-Ying Zhang (Annals of Nuclear Energy, 2025)

Toll-like receptors landscape in Takifugu fasciatus: Dynamic responses to Aeromonas hydrophila, poly I:C, and Ichthyophthirius multifiliis challenge - Ge Lin; Peng Chu; Xiang Gong; Yuxi Liu; Kai Zhang; Xianhui Ning; Tao Wang; Shaowu Yin; Jie Ji (Aquaculture, 2025)

Combined impacts of vertical greening and permeable pavement systems on street Canyons' microclimate in hot and humid regions in China - Haoxian Wang; Jiahong Zhao; Jiang Lu; Jian Ge; Guoquan Lv; Xiaoyu Luo; Haiqin Lin; Muye Gu (Urban Climate, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Plasma proteomics identifies proteins and pathways associated with incident depression in 46,165 adults - Jujiao Kang; Liu Yang; Tianye Jia; Wei Zhang; Lin-Bo Wang; Yu-Jie Zhao; Jia You; Yue-Ting Deng; Yi-Jun Ge; Wei-Shi Liu; Yi Zhang; Yi-Lin Chen; et al. (Science Bulletin, 2025)

Liquid-liquid phase separation of TRAF6 promotes anti-TB immunity - Yongjia Duan; Yuanna Cheng; Mingtong Ma; Liru Li; Shanshan Liu; Liru Guan; Jie Wang; Hongjie Liu; Xiaochen Huang; Jianxia Chen; Hua Yang; Baoxue Ge; et al. (Science Bulletin, 2025)

Moxifloxacin plus Cordyceps polysaccharide ameliorate intestinal barrier damage due to abdominal infection via anti-inflammation and immune regulation under simulated microgravity - Hong-Yun Nie; Jun Ge; Kai-Ge Liu; Yuan Yue; Hao Li; Hai-Guan Lin; Tao Zhang; Hong-Feng Yan; Bing-Xin Xu; Hong-Wei Sun; Jian-Wu Yang; Shao-Yan Si; et al. (Life Sciences in Space Research, 2025)

Comprehensive assessment of straw returning with organic fertilizer on paddy ecosystems: A study based on greenhouse gas emissions, C/N sequestration, and risk health - Keqi Zhao; Xichen Zhao; Liuqin He; Nanyi Wang; Ma Bai; Xiaobing Zhang; Ge Chen; Anwei Chen; Lin Luo; Jiachao Zhang (Environmental Research, 2025)

A trackable mitochondria-targeting nanosystem for mitochondrial redox and mitophagy regulation in diabetic retinopathy management - Yangxue Yao; Xiaoyu Lei; Xun Li; Yichen Ge; Yun Wang; Xin Qin; Yang Gao; Geru Zhang; Yunfeng Lin; Shaojingya Gao; Xiaoxiao Cai (Chemical Engineering Journal, 2025)

Engineered silicon-titania heterojunction elicits catalytic cancer cell death - Deliang Xu; Tingting Xu; Min Ge; Shibo Cao; Zhaoda Yu; Zhixin Chen; Ya-Xuan Zhu; Zhuang Liu; Ming Zong; Han Lin; Jianlin Shi (Chemical Engineering Journal, 2025)

Influences of permeable pavements with different hydraulic properties on evaporative cooling and outdoor thermal environment: Field experiments - Jiahong Zhao; Jiang Lu; Jian Ge; Yifan Fan; Haoxian Wang; Muye Gu; Yucong Xue; Yujie Zhao; Guoquan Lv; Haiqin Lin; Kang Zhao; Xiaoyu Luo (Building and Environment, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Impacts of Spartina alterniflora invasion on soil carbon components of particulate and mineral-associated organic matter and soil organic matter mineralization in estuarine wetlands - Lin Wang; Yuan Li; Jie Hei; Weiqi Wang; Jordi Sardans; Zhihao Zhang; Fanjiang Zeng; Maoquan Ge; Yiyang Liao; Yunying Fang; Tony Vancov; Jiawei Gan; et al. (Applied Soil Ecology, 2025)

Investigation of land subsidence in Guangdong Province, China, using PS-InSAR technique - Liangke Huang; Peijie Zhu; Tengxu Zhang; Lin He; Wenhao Wu; Zixuan Ge; Hui Ai (Advances in Space Research, 2025)

Earth's record-high greenness and its attributions in 2020 - Yulong Zhang; Jiafu Mao; Ge Sun; Qinfeng Guo; Jeffrey Atkins; Wenhong Li; Mingzhou Jin; Conghe Song; Jingfeng Xiao; Taehee Hwang; Tong Qiu; Lin Meng; et al. (Remote Sensing of Environment, 2025)

Isolation and characterization of high ammonium tolerant Fasciculochloris sp. HDMA-06 and its potential for nutrient removal and biodiesel production in simulated swine wastewater - Han Wang; Xinyi Wang; Jixin Liu; Yimeng Lin; Jingping Ge; Wenxiang Ping (Journal of Water Process Engineering, 2025)

Spatiotemporal distribution prediction for PM2.5 based on STXGBoost model and high-density monitoring sensors in Zhengzhou High Tech Zone, China - Shiqi Zhao; Hong Lin; Hongjun Wang; Gege Liu; Xiaoning Wang; Kailun Du; Ge Ren (Journal of Environmental Management, 2025)

The relationship between indoor airborne culturable bacteria with passenger flow in 132 traffic stations during 2019–2020, China - Li Li; Hang Du; Chong Meng; Lin Fan; Hang Liu; Xu Han; Tanxi Ge; Liqin Su; Xiaoyuan Yao; Xianliang Wang (Journal of Environmental Management, 2025)

Characteristic analysis and diagnosis method optimization of scroll compressor pressure pulsation signal under voltage fluctuation - Yanjie Zhao; Tonghe Zhang; Yongxing Song; Qiang Liu; Lin Liu; Ming Yu; Yi Ge (International Journal of Refrigeration, 2025)

Bilayer oriented nanofiber membrane for enhancing response deformation and stability of humidity-responsive actuator - Zhongqiu Cheng; Yiyang Hua; Desuo Zhang; Mengxuan Wang; Xin Ge; Yaxinru Shen; Bing Zhao; Ning Qi; Hong Lin (Chemical Engineering Journal, 2025)

Photothermal-thermoelectric synergy coupling localized surface plasmon resonance for enhanced flexible photoelectrochemical sensor performance - Mengqi Chen; Hui Tian; Ling Qi; Yuying Zhang; Hongmei Yang; Shenguang Ge; Lina Zhang; Yan Zhang; Lin Li; Kang Cui; Jinghua Yu (Chemical Engineering Journal, 2025)

Preparation of a novel organic-inorganic composite sludge bioflocculant (SBF) from dewatered sludge as raw material: Characteristics, flocculation mechanism and application for domestic sewage - Jingyun Ge; Hongyu Tian; Lin Li; Yunping Han; Jianwei Liu (Bioresource Technology, 2025)

Spatiotemporal distribution patterns of large and medium-sized mammals in a biodiversity hotspot: mplications for conservation - Wenqiang Hu; Xueyou Li; Kenneth Otieno Onditi; Hongjiao Wang; Wenyu Song; Zhechang Hu; Changzhe Pu; Mingjing Pu; Yun Xiong; Suhua Yang; Lin Zhu; Jianqiang Yin; et al. (Biological Conservation, 2025)

Deciphering the key drivers of oxidative potential during ammonium nitrate-mediated aqueous-phase photoreaction of methoxyphenols - Racliffe Weng Seng Lai; Tian Qiu; Xuyang Zhang; Yalin Wang; Tianwei Hao; Xinlei Ge; Lin Du; Mingjin Tang; Ka In Hoi; Kai Meng Mok; Yong Jie Li (Atmospheric Environment, 2025)

Effect of different Hydrilla verticillata harvesting intensities on Vallisneria natans: Implications for restoring and managing submerged macrophytes - Xiaowen Lin; Xiaodong Wu; Daoya Liu; Xuguang Ge; Liang Chen; Zhenni Gao; Shixing Song; Chenxin Zhong; Zian Xiang (Plant and Soil, 2025)

Treadmill Exercise Enhances Post-Stroke Functional Recovery in Mice via the CX3CL1/CX3CR1 Signaling Pathway - Yangyang Ge; Xiaoke Dou; Pu Chen; Jiayi Chen; Maosha Dai; Shanglong Yao; Yun Lin (Molecular Neurobiology, 2025)

Correction: Projected changes in precipitation extremes over Southeast Asia: unraveling the roles of thermodynamic and dynamic contributions - Zhiye Lin; Fei Ge; Quanliang Chen; Klaus Fraedrich; Zhengrui Jin (Climate Dynamics, 2025)

Projected changes in precipitation extremes over Southeast Asia: unraveling the roles of thermodynamic and dynamic contributions - Zhiye Lin; Fei Ge; Quanliang Chen; Klaus Fraedrich; Zhengrui Jin (Climate Dynamics, 2025)

Cross-sectional and Longitudinal Associations Between Metal Mixtures and Serum C3, C4: Result from the Manganese‑exposed Workers Healthy Cohort - Sencai Lin; Junxiu He; Yinghua Zhou; Yu Bao; Xiuming Feng; Hong Cheng; Haiqing Cai; Sihan Hu; Lin Wang; Yuan Zheng; Mengdi Zhang; Qinghua Fan; et al. (Biological Trace Element Research, 2025)

Endoplasmic reticulum stress and Ca2+ dysregulation in response to ammonia nitrogen exposure could be alleviated by dietary fermented mulberry leaf meal in Megalobrama amblycephala - Wenqiang Jiang; Linjie Qian; Qiaoqiao Mu; Yan Lin; Siyue Lu; Zhengyan Gu; Huaishun Shen; Xianping Ge; Linghong Miao (Aquaculture, 2024)

Fertilizer reduction and biochar amendment promote soil mineral-associated organic carbon, bacterial activity, and enzyme activity in a jasmine garden in southeast China - Fajun Yang; Weiqi Wang; Ziwei Wu; Jiahao Peng; Hongda Xu; Maoquan Ge; Shaoying Lin; Yu Zeng; Jordi Sardans; Chun Wang; Josep Peñuelas (Science of The Total Environment, 2024)

Spatiotemporal evolution of land use efficiency in 357 cities across mainland China from 2000 to 2020 based on SDG 11.3.1 - Min Huang; Fen Liu; Daohong Gong; Hui Lin; Yong Chen; Bisong Hu; Yong Ge; Changjiang Xiao (Science of The Total Environment, 2024)

Facile formation of van der Waals metal contact with III-nitride semiconductors - Xiyu Sun; Danhao Wang; Xiaojing Wu; Jiahao Zhang; Yangjian Lin; Dongyang Luo; Fang Li; Haochen Zhang; Wei Chen; Xin Liu; Yang Kang; Huabin Yu; et al. (Science Bulletin, 2024)

Association between pyrrolizidine alkaloids exposure and risk of abnormal serum indices—Insights from a descriptive cross-sectional study in Yunnan Province - Xiaoxiang Sun; Zhengyuan Xie; Zheng He; Yisheng He; Zigao Zhao; Xuerong Yan; Xiangjing Song; Zijie Chen; Tao Wang; Quanrui Yue; Yiming Chen; Hanfeng Ye; et al. (Journal of Hazardous Materials, 2024)

m6A RNA methyltransferase METTL16 induces Cr(VI) carcinogenesis and lung cancer development through glutamine biosynthesis and GLUL expression - Yun-Xia Xie; Lin Wang; Zhi-Hao Zhou; Wen-Jing Liu; Wei Wang; Jing-Hua Yang; Ming-Liang He; Jian-Ge Qiu; Bing-Hua Jiang (Journal of Hazardous Materials, 2024)

Excellent antibiotic degradation through PMS activation via bio derived Fe-Mn oxides with tunable defect concentration: Synergy between singlet oxygen oxidation and electron transfer - Kai Teng; Jiajie Wu; Yuxi Chen; Lin Ge; Guang Li; Yuning Fan; Qing Qu; Lei Li (Journal of Environmental Chemical Engineering, 2024)

Air-sea CO2 exchange in the western Pacific influenced by monsoon and giant diatom (Ethmodiscus rex) blooms during the last deglaciation - Huaineng Tang; Haoran Ye; Wenqing Yang; Yikang Huang; Tiantai Sun; Yangyuan Ge; Hongxin Zhang; Yuqing Sun; Shanying Lin; Zhonghui Liu; Wenhua Li; Zhouqing Xie (Journal of Asian Earth Sciences, 2024)

Site selection and effects of background towers on urban CO2 estimates: A case study from central downtown Zhengzhou in China - Ge Ren; Kailun Du; Anna Karion; Shiqi Zhao; Israel Lopez-Coto; Xiaoning Wang; James Whetstone; Hong Lin (Environmental Research, 2024)

Eco-friendly nanotechnology in rheumatoid arthritis: ANFIS-XGBoost enhanced layered nanomaterials - Zhiyong Zhang; Mingtao Ye; Yisu Ge; Mohamed Gamal Elsehrawy; Xiaotian Pan; Nermeen Abdullah; Samia Elattar; Ehab El Sayed Massoud; Suxian Lin (Environmental Research, 2024)

Solvent-free green synthesis of anion exchange membranes via photo-polymerization for efficient desalination by electrodialysis - Xuehui Ge; Huanhuan Zhang; Yafei Cheng; Haiyang Shao; Lei Yuan; Senbin Shen; Guixiang Wang; Chenxiao Jiang; Xiaocheng Lin (Desalination, 2024)

Spatial heterogeneity of volatile organic compound pollution in a typical industrial park based on multi-point online monitoring: Pollution characteristics, health risks, and priority-controlled species - Mengjuan Han; Ge Ren; Xinna Zhao; Xiaodong Zhang; Hong Lin; Dan Liu; Lei Wang (Atmospheric Environment, 2024)

Numerical investigation of resistance components distribution for lateral loaded offshore wind turbine monopile - Ge Wang; Chencong Liao; Lulu Zhang; Jiangqin Lin; Guanlin Ye; Zechao Zhang (Marine Georesources & Geotechnology, 2024)

Preparation and Characterization of a Novel Ca-Fe-Si-S Composite for the Simultaneous Stabilization of Heavy Metals in Arsenic Slag - Ge Zhang; Huifen Yang; Xingjie Lin; Yu Miao; Chi Zhang; Fangze Li; Zhikun Pang; Xin Xin (Water, Air, & Soil Pollution, 2024)

Soil bacterial and protist communities from loquat orchards drive nutrient cycling and fruit yield - Li Wang; Jianhong Ji; Fei Zhou; Bibo Wu; Yingying Zhong; Lin Qi; Miao Wang; Yuping Wu; Xintao Cui; Tida Ge; Zhenke Zhu (Soil Ecology Letters, 2024)

Risk substance identification of asphalt VOCs integrating machine learning and network pharmacology - Lei Ge; Jue Li; Ziyang Lin; Xinqiang Zhang; Yongsheng Yao; Gang Cheng; Yifa Jiang (Transportation Research Part D: Transport and Environment, 2024)

Structural determinants of parabens in inhibiting human and rat gonadal 3β-hydroxysteroid dehydrogenase - Chentao Ding; He Zhu; Yunbing Tang; Yingfen Ying; Yang Zhu; Han Lin; Ren-Shan Ge; Huitao Li (Toxicology and Applied Pharmacology, 2024)

Associations of ambient air pollution with incidence and dynamic progression of atrial fibrillation - Junguo Zhang; Linna Luo; Ge Chen; Baozhuo Ai; Gan Wu; Yanhui Gao; Gregory Y.H. Lip; Hualiang Lin; Yangxin Chen (Science of The Total Environment, 2024)

Unveiling the pathogenic and multidrug-resistant profiles of Vibrio alfacsensis: A potential identified threat in turbot (Scophthalmus maximus) aquaculture - Ren-Ge Hu; Lei Yang; Li-Yan Wang; Yu-Lin Yang; Hong-Jin Li; Bin-Tong Yang; Yuan-Huan Kang; Zhen-Lin Liang; Wei Cong (Journal of Hazardous Materials, 2024)

A conical spiral methanol steam reforming reactor for spectral splitting-based concentrating photovoltaic-thermochemical hybrid production - Riyi Lin; Jinyu Li; Yi Ge; Yiya Wang; Pengyu Chen; Huanan Li; Qiwei Dong; Ruiqi Liu; Chenxing Huang; Xinwei Wang; Zhengda Yang (Journal of Cleaner Production, 2024)

Tracking paddy rice acreage, flooding impacts, and mitigations during El Niño flooding events using Sentinel-1/2 imagery and cloud computing - Ruoqi Liu; Jinwei Dong; Yong Ge; Hui Lin; Xianghong Che; Yuanyuan Di; Xi Chen; Shuhua Qi; Mingjun Ding; Xiangming Xiao; Geli Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

In vitro cytotoxicity assessment of carbonaceous gels for bone marrow mesenchymal stem cells - Kaixuan Li; Peng Ge; Xi-Lin Wu; Cailiang Shen (Food and Chemical Toxicology, 2024)

Short term air pollution exposure during pregnancy and associations with maternal immune markers - C.S. Yount; K. Scheible; S.W. Thurston; X. Qiu; Y. Ge; P.K. Hopke; Y. Lin; R.K. Miller; S.K. Murphy; J. Brunner; E. Barrett; T.G. O'Connor; et al. (Environmental Research, 2024)

Mitigation mechanism of torsional vortex-induced vibrations using aerodynamic countermeasures: Case study on a typical closed-box girder - Chuanxin Hu; Lin Zhao; Xulong Guan; Yaojun Ge (Engineering Structures, 2024)

Preparation of polyethylene based composite nanofiltration membrane and its application in removal of heavy metals for water purification - Lin Wang; Guiru Zhu; Haochen Ge; Yunbo Tong; Lingling Li; Ziqi Wang; Congjie Gao (Desalination, 2024)

Anionic and cationic co-doping to enhance the oxygen transport property of Bi0.5Sr0.5FeO3-δ as a high-performance air electrode for reversible solid oxide cells - Hui Ye; Yixuan Feng; Pengkai Shan; Bin Qian; Lin Ge; Han Chen; Yifeng Zheng (Chemical Engineering Journal, 2024)

On the properties of lower mid-latitudes ionospheric scintillation observed over Chengdu, China - Shucan Ge; Hailong Li; Song Zhang; Mengyan Zhu; Jinghua Li; Bin Xu; Tong Xu; Shuji Sun; Lin Meng; Jian Wu (Advances in Space Research, 2024)

Spatial and temporal distribution patterns of atmospheric PM2.5 and water-soluble inorganic ions in Shenzhen, China from 2016 to 2021 - Yuli Lin; Liuyi Yin; Xiaoheng Li; Yiming Ge; Zhihui Guo; Hongmei Qiu; Jiajia Ji; Shaoyou Lu (Chemosphere, 2024)

Evaluation and analysis of long-term MODIS MAIAC aerosol products in China - Ge Huang; Xin Su; Lunche Wang; Yi Wang; Mengdan Cao; Lin Wang; Xiaoyu Ma; Yueji Zhao; Leiku Yang (Science of The Total Environment, 2024)

Prediction of As and Cd dissolution in various soils under flooding condition - Jingwen Ge; Song Wu; Haotian Wu; Jianyu Lin; Yijun Cai; Dongmei Zhou; Xueyuan Gu (Science of The Total Environment, 2024)

Reduction in polycyclic aromatic hydrocarbon exposure in Beijing following China’s clean air actions - Yan Lin; Xiaodi Shi; Xinghua Qiu; Xing Jiang; Jinming Liu; Peiwen Zhong; Yihui Ge; Chi-Hong Tseng; Junfeng (Jim) Zhang; Tong Zhu; Jesus A Araujo; Yifang Zhu (Science Bulletin, 2024)

Synthesis of a novel double Z-scheme BiVO4/Cu2O/g-C3N4 sonocatalyst and research on sonocatalytic degradation of tetracycline - Yang-Cheng Liu; Ying-Di Ge; Hui-Li An; Wan-Ting Ju; Xin-Yi Zhou; Mei-Yi Xing; Yang Wang; Lin Zhang; Xin Wang; Liang Xu (Journal of Environmental Chemical Engineering, 2024)

Insight into electricity production performance from dried waste activated sludge in dual chamber microbial fuel cells: Influencing factors, neural network modelling and microbial community analysis - Lin Wei; Ziyue Li; Tianqiu Hong; Yiming Tang; Ying Ge; Dongdong Ji; Qiang Zhang; Lei Luo; Jianyu Kong; Xiaoke Ding (Journal of Environmental Chemical Engineering, 2024)

Catalytic combustion of light hydrocarbons over Pd − Pt/Al2O3: The hidden Pt1 active sites - Ziran Ma; Jiali Zhou; Jing Lin; Gongjin Yang; Shuang Liu; Ge Li (Fuel, 2024)

Optimization framework for daylight and thermal environment of retractable roof natatoriums based on generative adversarial network and genetic algorithm - Zhongqi Yu; Xinyi Ge; Zhaoxiang Fan; Yihang Zhou; Dawei Lin (Energy and Buildings, 2024)

Synergistic strategy via modulated energy filtering and hierarchical defects evolution for high performance GeTe thermoelectrics - Ge Fu; Shangchao Lin; Yixuan Liu; Jie Xiao; Changying Zhao (Chemical Engineering Journal, 2024)

Study of the electrospun PVDF fibrous membrane in capturing particulate matters in smoke by the synergy between GO and CNWs - Xiuling Lin; Jieqi Zhang; Ge Meng; Chao Zhang; Chen Yu (Chemical Engineering Journal, 2024)

Local defect structure design enhanced energy storage performance in lead-free antiferroelectric ceramics - Peixuan Li; Simin Wang; Jin Qian; Guanglong Ge; Luomeng Tang; Jinfeng Lin; Weiwei Yang; Jimin Lin; Weikang Lin; Bo Shen; Jiwei Zhai (Chemical Engineering Journal, 2024)

Developing fine-tuned MOF membranes for highly efficient separation and adsorption of chemical pollutant in water - Jiatong Han; Donghui Xu; Yanyan Huang; Yuwei Hua; Xin Ding; Zhihao Lin; Jie Zhou; Huan Lin; Ge Chen; Jing Wang; Xiaomin Xu; Jia Liu; et al. (Chemical Engineering Journal, 2024)

First wetland mapping at 10-m spatial resolution in South America using multi-source and multi-feature remote sensing data - Weiwei Sun; Gang Yang; Yuling Huang; Dehua Mao; Ke Huang; Lin Zhu; Xiangchao Meng; Tian Feng; Chao Chen; Yong Ge (Science China Earth Sciences, 2024)

Pollution Characteristics and Risk Assessment of Heavy Metals in Dujiangyan Irrigation District, China - Yang Qiao; Hongling Yin; Shuyu Lin; Xiaoke Guo; Hui Zhang; Geng Ge; Yuxiang Lu (International Journal of Environmental Research, 2024)

Toll-like receptor expression in Pacific white shrimp (Litopenaeus vannamei) reveals differential responses after fungal (Fusarium solani) infection - Yusuf Jibril Habib; Chengjie Yao; Haifu Wan; Jiaming Lin; Hui Ge; Akram Ismael Shehata; Mayada Alhoshy; Muhammad Mohsin; Yilei Wang; Ziping Zhang (Aquaculture International, 2024)

TNF-α and RPLP0 drive the apoptosis of endothelial cells and increase susceptibility to high-altitude pulmonary edema - Yi-Ling Ge; Pei-Jie Li; Ying-Rui Bu; Bin Zhang; Jin Xu; Si-Yuan He; Qing-Lin Cao; Yun-Gang Bai; Jin Ma; Lin Zhang; Jie Zhou; Man-Jiang Xie (Apoptosis, 2024)
High-altitude pulmonary edema (HAPE) is a fatal threat for sojourners who ascend rapidly without sufficient acclimatization. Acclimatized sojourners and adapted natives are both insensitive to HAPE but have different physiological traits and molecular bases. In this study, based on GSE52209, the gene expression profiles of HAPE patients were compared with those of acclimatized sojourners and adapted natives, with the common and divergent differentially expressed genes (DEGs) and their hub genes identified, respectively. Bioinformatic methodologies for functional enrichment analysis, immune infiltration, diagnostic model construction, competing endogenous RNA (ceRNA) analysis and drug prediction were performed to detect potential biological functions and molecular mechanisms. Next, an array of in vivo experiments in a HAPE rat model and in vitro experiments in HUVECs were conducted to verify the results of the bioinformatic analysis. The enriched pathways of DEGs and immune landscapes for HAPE were significantly different between sojourners and natives, and the common DEGs were enriched mainly in the pathways of development and immunity. Nomograms revealed that the upregulation of TNF-α and downregulation of RPLP0 exhibited high diagnostic efficiency for HAPE in both sojourners and natives, which was further validated in the HAPE rat model. The addition of TNF-α and RPLP0 knockdown activated apoptosis signaling in endothelial cells (ECs) and enhanced endothelial permeability. In conclusion, TNF-α and RPLP0 are shared biomarkers and molecular bases for HAPE susceptibility during the acclimatization/adaptation/maladaptation processes in sojourners and natives, inspiring new ideas for predicting and treating HAPE.

Controlled experiments fail to capture plant phenological response to chilling temperature - Huanjiong Wang; Shaozhi Lin; Junhu Dai; Quansheng Ge (Global Ecology and Biogeography, 2024)
Aim Controlled experiments are increasingly important for investigating how and to what degree plant phenology responds to global climate change. Current experiments underline that chilling and forcing temperatures are two major environmental cues shaping the budburst date of temperate species, but whether experiments could reflect the observed responses to chilling has rarely been examined. Location Europe and North America. Time periods 1951–2021. Major taxa studied Temperate trees and shrubs. Methods Using an experimental database of budburst dates for 50 species derived from previous literature and observational data of the same species at 12,579 stations in Europe and 1469 stations in the USA, we compared the response of forcing requirement (FR) of the budburst date to chilling accumulation (CA) between observations and experiments using a common measure of FR and CA. Results The median, variance and probability distribution of CA‐FR curves differed significantly between experiments and observations in most cases. The distinction in chilling effects between experiments and observations could be attributed to the difference in thermal space, heat stress, genetic variation among provenances, different forcing treatments adopted and plant materials used in the experiments. Main conclusions Our results suggest that the uncertainty of phenological models based solely on the experimental data needs to be re‐evaluated when predicting future spring phenological responses across broad spatial scales.

Improving the sustainability of milk production across different climate regions in China - Zhaoping Wu; Yuanyuan Du; Guofu Yang; Linshan Lin; Xiaoyu Hou; Yandong Tan; Xing Fan; Yuan Ren; Bijie Wu; Shun Liu; Scott X. Chang; Wanhong Sun; et al. (Sustainable Production and Consumption, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Paospora carinifang n. gen., n. sp. (Microsporidia: Spragueidae), a parasite of the ridgetail white prawn, Palaemon carinicauda - Yuan Wang; Ying Na; Yan-qing Huang; Jun-fang Zhou; Shou-hu Li; Quan-lin Liu; Le-tian Li; Yuan-ge Chen; Wei Tian; Hai Chi; Xin-cang Li; Wen-hong Fang (Journal of Invertebrate Pathology, 2024)

Mineralization and microbial utilization of poly(lactic acid) microplastic in soil - Yongxiang Yu; Shiying Lin; Binoy Sarkar; Juan Wang; Xinhui Liu; Danni Wang; Tida Ge; Yaying Li; Biao Zhu; Huaiying Yao (Journal of Hazardous Materials, 2024)

Systemic oxidative stress levels during the course of pregnancy: Associations with exposure to air pollutants - Xiangtian Wang; Yan Lin; Yihui Ge; Emily Craig; Xiaodong Liu; Richard K. Miller; Sally W. Thurston; Jessica Brunner; Emily S. Barrett; Thomas G. O'Connor; David Q. Rich; Junfeng (Jim) Zhang (Environmental Pollution, 2024)

Suppression of pathological neovascularization by anti-Flt1 peptide functionalized DNA tetrahedron - Bicai Tang; Yuting Yang; Yong Li; Yutian He; Yichen Ge; Yangxue Yao; Wenjuan Ma; Yunfeng Lin (Chemical Engineering Journal, 2024)

Spatio-temporal pattern analysis of coastal zone in Nansha based on remote sensing technology - Jun Huang; Xiaojuan Liu; Yan Lin; Lipeng Ge (Remote Sensing Applications: Society and Environment, 2024)

Optimization and mechanism of strengthened biological contact oxidation for rural domestic wastewater treatment - Yingfei Li; Shuhan Ge; Jialin Luan; Yanzhe Wang; Lin-Lan Zhuang; Jian Zhang (Journal of Water Process Engineering, 2024)

Metals/bisulfite system involved generation of 24-sulfonic-25-ene ginsenoside Rg1, a potential quality control marker for sulfur-fumigated ginseng - Hui Liu; Xiao-Qian Wu; Xiang-Ling Qin; Jin-Hao Zhu; Jin-Di Xu; Shan-Shan Zhou; Ming Kong; Hong Shen; Jie-Ge Huo; Song-Lin Li; He Zhu (Food Chemistry, 2024)

Tornado-induced instability assessment of super large hyperbolic reinforced concrete cooling towers - Lin Zhao; Xu Dong; Shikui Huang; Mao Chen; Yaojun Ge (Engineering Structures, 2024)

Dynamic adaptive hydrogel facilitates neuroregeneration in segmental nerve deficits via immunomodulation and mitochondrial homeostasis - Xiaozhong Yang; Jizhao Dong; Yunfeng Tang; Xiangtian Deng; Chen Liang; Juan Du; Zilu Ge; Dong Wang; Yifan Shen; Wei Lin; Tonghe Zhu; Renliang Zhao; et al. (Chemical Engineering Journal, 2024)

Photoelectric synaptic device based on Cu2ZnSnS4/ZnO heterojunction for non-volatile vision memory - Shuaifei Mao; Jiantong Ge; Lingling Zhang; Yannan Dai; Sheng Jiang; Yafei Chen; Chunli Jiang; Chunhua Luo; Bobo Tian; Hechun Lin; Hui Peng; Chun-Gang Duan (Chemical Engineering Journal, 2024)

Boost to early spring compound heatwaves over South Asia from anomalous Tibetan Plateau atmospheric heat source - Zhengrui Jin; Kang Xu; Fei Ge; Weiqiang Wang; Zhiye Lin (Atmospheric Research, 2024)

Improving Granulosa Cell Function in Premature Ovarian Failure with Umbilical Cord Mesenchymal Stromal Cell Exosome-Derived hsa_circ_0002021 - Ge Yang; Bo Zhang; Mei Xu; MingJun Wu; Jie Lin; ZiYu Luo; YueHua Chen; Qin Hu; GuoPing Huang; HaiYan Hu (Tissue Engineering and Regenerative Medicine, 2024)

CA1 Modulates the Osteogenic Differentiation of Dental Follicle Stem Cells by Activating the BMP Signaling Pathway In Vitro - Jin-ze Zhao; Ying-Ying Ge; Ling-fa Xue; Yao-xiang Xu; Jin Yue; Cong Li; Wen-lin Xiao (Tissue Engineering and Regenerative Medicine, 2024)

Correction to: The connection between six common air pollution particles and adult brain tumors: a meta-analysis of 26,217,930 individuals - Lu-Ting Shen; Meng-Wei Ge; Fei-Hong Hu; Yi-Jie Jia; Wen Tang; Wan-Qing Zhang; Dan-Yan Zhao; Wang-Qin Shen; Hong-Lin Chen (Environmental Science and Pollution Research, 2024)

Alleviation of arsenic stress in pakchoi by foliar spraying of engineered nanomaterials - Yaoyao Wang; Xingbei Chen; Lu Lin; Jingwen Ge; Yuhong Huang; Xueyuan Gu (Environmental Science and Pollution Research, 2024)

Sedimentary biogeochemical gradients across the Sunda Shelf in the South China Sea and correlations with satellite observations - Yuanfang Zhang; Lin Deng; Zaiming Ge; Lin Guo; Qian P. Li (Frontiers in Marine Science, 2024)
The sediment biogeochemistry of phosphorus (P) and biogenic silica (BSi) in the southern South China Sea shelf (SSCS) is inadequate understood. Here, we examine the spatial distributions of P species and BSi in surface sediments across the Sunda Shelf and explore their relationships with satellite data of sea surface chlorophyll-a (Chla), suspended particulate matter (SPM), particulate organic carbon, particulate inorganic carbon, primary production (PP), and phytoplankton functional types. The total sediment P (TSP), in the range from 283.94 to 579.94 μg/g dry sediment, was dominated by inorganic P with higher levels in stations outside the Lupar and Saribas estuaries. The TSP was composed of seven different P species including Ca-IP and Ca-OP (58%), Detr-P (15%), Exch-P (11%), Fe-IP (10%), Ref-P (4%) and Ads-IP (2%) based on a sequential extraction method. The concentrations of various sediment P species were found significantly correlated with satellite climatological SPM, diatom biomass, and monthly climatological pico-PP revealing the importance of biological production for the sediment P storage, whereas the sediment BSi concentration showed no correlations with any of the above satellite products. An elevated R 2 value in the regression of BSi with the in-situ depth-integrated Chla points to the need of developing satellite algorithms with vertical profiles from space. Finally, we argue that future studies of the SSCS sediment biogeochemistry may be benefited from data of hyperspectral and geostationary satellites.

East Asian Winter Monsoon and enhanced stratification in the western Pacific promoted giant marine diatom (Ethmodiscus rex) blooms during the last deglaciation - Huaineng Tang; Haoran Ye; Wenqing Yang; Yikang Huang; Tiantai Sun; Yangyuan Ge; Hongxin Zhang; Yuqing Sun; Shanying Lin; Zhonghui Liu; Wenhua Li; Zhouqing Xie (Quaternary Science Reviews, 2024)

Concentrations and influencing factors of 17 elements in placenta, cord blood, and maternal blood of women from an e-waste recycling area - Yacui Luo; Haijun Zhang; Fangzhong Gui; Jiayang Fang; Haijiang Lin; Danhong Qiu; Lingfei Ge; Qiong Wang; Peiwei Xu; Jun Tang (Journal of Trace Elements in Medicine and Biology, 2024)

Long-term exposure to ambient ozone and adult-onset asthma: A prospective cohort study - Jiayue Zhang; Baozhuo Ai; Yuming Guo; Lan Chen; Ge Chen; Haitao Li; Hualiang Lin; Zilong Zhang (Environmental Research, 2024)

Tuning multiple enzyme-like activities by metal doping for identification and quantitation of antioxidants in cosmetics - Sheng-Tao Wu; Hui-Qi Su; Kai-Lin Shen; Ying Li; Yi Ge; Xiu-Fang Cheng; Chang-Ming Nie; Cong-Hui Wang; Ying-Wu Lin (Chemical Engineering Journal, 2024)

Water addition but not reduction alters plant biomass–diversity relationship - Yan Yu; Josep Peñuelas; Jordi Sardans; Jiu‐ying Pei; Ge Li; Guo‐lin Liu; Jian‐Sheng Ye (Global Change Biology, 2024)
The relationship between plant aboveground biomass and diversity typically follows a unimodal pattern, showing a positive correlation in resource‐poor habitats and a negative correlation in resource‐rich environments. Precipitation is a crucial resource for both plant biomass and diversity in terrestrial ecosystems. However, the impact of precipitation changes on the relationship between plant biomass and diversity remains unclear. We conduct a water addition field experiment in a semiarid grassland and identify a unimodal relationship between plant biomass and species richness under ambient conditions. Water addition delays the declining phase of this unimodal curve and shift it upward compared to ambient conditions. Our meta‐analysis of water addition experiments conducted across major biomes worldwide (grassland, shrubland, desert, and forest) supports this finding, while water reduction does not alter the biomass–diversity relationship. Water addition increases biomass in all climate but only increases species richness in arid and semiarid climate. Similarly, water reduction decreases biomass in all climate but only reduces species richness in arid and semiarid climate. Species richness in dry subhumid and humid climate does not change significantly. Furthermore, our field experiment shows that water addition increases plant diversity while decreasing soil inorganic nitrogen levels. The increase in one resource, such as water, leads to the scarcity of another, such as nutrient, thus postponing the declining phase of the plant biomass–diversity relationship typically observed in resource‐rich habitats. Our research contributes to predicting the plant biomass–diversity relationship under changing precipitation conditions and highlights the complex interplay between water availability, nutrient level, and plant diversity.

Inhibitor of apoptosis stimulating protein of p53 protects against MPP+-induced neurotoxicity of dopaminergic neurons - Lei Chen; Fengju Duan; Fangfang Ge; Lu Tian; Yuanyuan Li; Ying Li; Qing Zhu; Qiong Zhou; Hong Lin (Metabolic Brain Disease, 2024)

Wogonin alleviates sepsis-induced acute lung injury by modulating macrophage polarization through the SIRT1-FOXO1 pathways - Jinlin Ge; Huanhuan Yang; Ningning Yu; Shengle Lin; Yufeng Zeng (Tissue and Cell, 2024)

Endocrine toxicity of atrazine and its underlying mechanisms - Haotang Zhao; Honghao Qian; Jianwei Cui; Zhili Ge; Jingjing Shi; Yingchao Huo; Yuezhu Zhang; Lin Ye (Toxicology, 2024)

Stratified burn severity assessment by integrating spaceborne spectral and waveform attributes in Great Xing'an Mountain - Simei Lin; Linyuan Li; Shangbo Liu; Ge Gao; Xun Zhao; Ling Chen; Jianbo Qi; Qin Shen; Huaguo Huang (Remote Sensing of Environment, 2024)

All-natural plant-based HIPE-gels simultaneously stabilizing with Quillaja saponin and soy protein isolate: Influence of environmental stresses on stability - Xiao-Wei Chen; Tian-Ge Wang; Wen-Jun Yin; Lin-Shang Zhang; Shang-De Sun (Food Hydrocolloids, 2024)

Toll-interacting protein is activated by the transcription factor GATA1 and Sp1 to negatively regulate NF-κB and MAPK pathways in the Japanese eel (Anguilla japonica) - Tianyu Wang; Hui Ge; Peng Lin; Yilei Wang; Xiaojian Lai; Pengyun Chen; Fuyan Li; Jianjun Feng (Fish & Shellfish Immunology, 2024)

Constructing blocked-nanolayer by surface charge inversion over anion exchange membrane for improved antifouling performance - Dan Lu; Hongyu Jin; Yunchen Mao; Yukun Qian; Ge Li; Jing Wang; Ying Mei; Zhikan Yao; Zhuofan Gao; Lin Zhang (Desalination, 2024)

Highly biologically functional magnesium silicate-coated 3D printed round pore-shaped titanium scaffold alters exosomal miRNA expression to promote osteogenic differentiation for bone defect repair - Xuwei Luo; Zhencheng Xiong; Dong Wang; Renliang Zhao; Xiangtian Deng; Ao Duan; Chaoyi Zhang; Wenzheng Liu; Zilu Ge; Zhen Zhang; Qian Fang; Dongqin Xiao; et al. (Chemical Engineering Journal, 2024)

Kinetics, products and mechanisms of unsaturated alcohols and NO3 radicals - Lin Hu; Shengrui Tong; Yanyong Xu; Hailiang Zhang; Meifang Chen; Xiang He; Maofa Ge (Atmospheric Environment, 2024)

Effect of High Magnesium and Astragaloside IV on Vascular Endothelial Cells - Hongfei Qi; Teng Ge; Kun Wang; Jing Wang; Lin Dang; Juane Li; Haifang Wang (Cell Biochemistry and Biophysics, 2024)

Enhanced lipid productivity of Monoraphidium strains in co-cultures and their potential for biodiesel production - Yimeng Lin; Jing Xu; Jixin Liu; Han Wang; Jingping Ge; Wenxiang Ping (Algal Research, 2024)

Expression characteristics and interference analysis of glucose-6-phosphate dehydrogenase reveal its importance in Pyropia yezoensis under salt stress - Li Huan; Mengmeng Shi; Guohong Lin; Baoyu Zhang; Xiujun Xie; Menglin Guo; Xi Qiang; Zhaojia Ge; Jianfeng Niu; Zhenbing Zheng; Xulei Wang; Guangce Wang (Algal Research, 2024)

The metabolic activation of pentachlorophenol to chloranil as a potent inhibitor of human and rat placental 3β-hydroxysteroid dehydrogenases - Weibing Zhang; Ming Su; Hao Lin; Chengshuang Pan; Yunbing Tang; Ren-shan Ge; Qianjin Fei (Toxicology Letters, 2024)

Differential inhibition of sildenafil and macitentan on saxagliptin metabolism - Ge-xin Dai; Wei Tan; Yuxin Shen; Dongdong Lin; Ren-ai Xu; Qianmeng Lin; Zhen Wei (Toxicology and Applied Pharmacology, 2024)

Highly modified cephalotane-type diterpenoids from Cephalotaxus fortunei var. alpina and C. sinensis - Zhan-Peng Ge; Jin-Biao Xu; Peng Zhao; Mai Xiang; Yu Zhou; Ze-Min Lin; Jian-Ping Zuo; Jin-Xin Zhao; Jian-Min Yue (Phytochemistry, 2024)

Investigation of dry environment construction Equipment's medium displacement system for submarine pipelines - Kaichuang Wang; Jiawang Chen; Jian Huang; Peiwen Lin; Jin Guo; Hai Zhu; Yuping Fang; Xuehua Chen; Guomin Cao; Wenbao Jia; Xu Gao; Han Ge (Ocean Engineering, 2024)

The effects of microgravity on stem cells and the new insights it brings to tissue engineering and regenerative medicine - Hong-Yun Nie; Jun Ge; Kai-Ge Liu; Yuan Yue; Hao Li; Hai-Guan Lin; Hong-Feng Yan; Tao Zhang; Hong-Wei Sun; Jian-Wu Yang; Jin-Lian Zhou; Yan Cui (Life Sciences in Space Research, 2024)

Insights into the microbiome and metabolome assembly during short-term storage of native grass hay - Qiang Si; Zhijun Wang; Lin Sun; Mingjian Liu; Wei Liu; Gentu Ge; Yushan Jia; Shuai Du (Journal of Stored Products Research, 2024)

Effects of inter-basin transfers on watershed hydrology and vegetation greening in a large inland river basin - Lin Wang; Wei Wei; Ge Sun; Bojie Fu; Liding Chen; Xiaoming Feng; Philippe Ciais; Bhaskar Mitra; Lixin Wang (Journal of Hydrology, 2024)

Changes in preferential flow caused by root effects in black locust plantations of different stand ages in the semi-arid region of the Loess Plateau - Lu Cai; Fei Wang; Yuanyuan Lin; Qi Long; Yulong Zhao; Jianqiao Han; Wenyan Ge; Hao Chen (Journal of Hydrology, 2024)

Long-term toxicity assessment of antibiotics against Vibrio fischeri: Test method optimization and mixture toxicity prediction - Shuhan Ge; Wanqing Tian; Ziyi Lou; Xiaoxiong Wang; Lin-Lan Zhuang; Jian Zhang (Journal of Hazardous Materials, 2024)

Causal association between long-term exposure to air pollution and incident Parkinson’s disease - Baozhuo Ai; Jiayue Zhang; Shiyu Zhang; Ge Chen; Fei Tian; Lan Chen; Haitao Li; Yuming Guo; Angela Jerath; Hualiang Lin; Zilong Zhang (Journal of Hazardous Materials, 2024)

Unraveling the ecological mechanisms of Aluminum on microbial community succession in epiphytic biofilms on Vallisneria natans leaves: Novel insights from microbial interactions - Xue Peng; Xiaowen Zhang; Zhuxi Li; Shuxian Zhang; Xinyi Zhang; Haokun Zhang; Qingwei Lin; Xia Li; Lu Zhang; Fangjie Ge; Zhenbin Wu; Biyun Liu (Journal of Hazardous Materials, 2024)

First retrieval of daily 160 m aerosol optical depth over urban areas using Gaofen-1/6 synergistic observations: Algorithm development and validation - Jiadan Dong; Tianhao Zhang; Lunche Wang; Zhengqiang Li; Man Sing Wong; Muhammad Bilal; Zhongmin Zhu; Feiyue Mao; Xinghui Xia; Ge Han; Qiangqiang Xu; Yu Gu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

DEHP induces apoptosis and autophagy of the thyroid via Rap1 signaling pathway: In vivo and in vitro study - Xu Li; Honghao Qian; Hui Ye; Haotang Zhao; Jianwei Cui; Xiaoqi Fang; Zhili Ge; Jingjing Shi; Wen Qi; Lin Ye (Food and Chemical Toxicology, 2024)

Bone tissue engineering based on sustained release of MiR29c-modified framework nucleic acids from an injectable hydrogel - Jiafei Sun; Yang Gao; Yangxue Yao; Yong Li; Maogeng Feng; Long Bai; Xingyu Chen; Yichen Ge; Yunfeng Lin; Xiaoxiao Cai (Chemical Engineering Journal, 2024)

Carbon-chain length determines the binding affinity and inhibitory strength of per- and polyfluoroalkyl substances on human and rat steroid 5α-reductase 1 activity - Rong Cui; Lei Ye; Xinyi Qiao; Shaowei Wang; Ke Zheng; Jin Yang; Ren-shan Ge; Han Lin; Yiyan Wang (Chemico-Biological Interactions, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

Effects of chemical oxygen demand and chloramphenicol on attached microalgae growth: Physicochemical properties and microscopic mass transfer in biofilm - Peihua Li; Yanan Yang; Lin-Lan Zhuang; Zhen Hu; Lijie Zhang; Shuhan Ge; Weiyi Qian; Wanqing Tian; Yinhu Wu; Hong-Ying Hu (Bioresource Technology, 2024)

Effects of significant emission changes on PM2.5 chemical composition and optical properties from 2019 to 2021 in a typical industrial city of eastern China - Xiangpeng Huang; Changping Li; Chao Pan; Yue'e Li; Wei Zheng; Guangwu Lin; Haiwei Li; Yunjiang Zhang; Junfeng Wang; Yali Lei; Jianhuai Ye; Xinlei Ge; et al. (Atmospheric Research, 2024)

Interdecadal change of Tibetan Plateau vortices during the past 4 decades and its possible mechanism - Zhiqiang Lin; Weidong Guo; Jun Ge; Xiuping Yao; Dongsheng Su (Climate Dynamics, 2024)
The Tibetan Plateau vortices (TPVs) are mesoscale weather systems active at the near-surface of the Tibetan Plateau (TP), which are one of the major precipitation-producing systems over the TP and its surrounding areas. TPVs mainly occur in the warm season from May to September. In this paper, we investigated the interdecadal change of TPVs in the warm seasons of 1979–2020 with the six widely used reanalysis datasets. A significant change of the TPVs frequency appears around the mid-1990s, associated with less TPVs during 1979–1995 and more TPVs during 1996–2020, which is constant among the multiple reanalysis datasets. The abrupt change of TPVs is caused by a transition of the Atlantic Multi-decadal Oscillation (AMO) from a cold phase to a warm phase in the mid-1990s. The shift of AMO leads to a silk-road pattern-like wave train and a spatially asymmetric change of tropospheric temperature. It modifies the intensity of the subtropical westerly jet and the TP heating, leading to the interdecadal change of TPV activities.

Residential differentiation characteristics based on “socio-spatial” coupling: A case study of Zhengzhou - Shuyun Hu; Zihan Zhang; Dazhuan Ge; Xiaobiao Lin; Yuqi Lu (Applied Geography, 2024)

The association between artificial light at night and gestational diabetes mellitus: A prospective cohort study from China - Junhao Liao; Chuan Yu; Jiarui Cai; Run Tian; Xingyue Li; Hong Wang; Lin Li; Guishuang Song; Leyao Fu; Xinxi Li; Qiaoyue Ge; Ling Zhang; et al. (Science of The Total Environment, 2024)

Single-cell profile reveals the landscape of cardiac immunity and identifies a cardio-protective Ym-1hi neutrophil in myocardial ischemia–reperfusion injury - Yalan Dong; Zhenyu Kang; Zili Zhang; Yongqiang Zhang; Haifeng Zhou; Yanfei Liu; Xinxin Shuai; Junyi Li; Liangqingqing Yin; Xunxun Wang; Yan Ma; Heng Fan; et al. (Science Bulletin, 2024)

Positive effects of biochar application and Rhizophagus irregularis inoculation on mycorrhizal colonization, rice seedlings and phosphorus cycling in paddy soils - Yixuan CHEN; Zhonghua WEN; Jun MENG; Zunqi LIU; Jialong WEI; Xiyu LIU; Ziyi GE; Wanning DAI; Li LIN; Wenfu CHEN (Pedosphere, 2024)

Letrozole induced a polycystic ovary syndrome model in zebrafish by interfering with the hypothalamic-pituitary-gonadal axis - Fucong Zhang; Chen Tang; Jingyi Wang; Tingting Lin; Wei Ge; Chengyong He; Chunyan Yang; Zhenghong Zuo (Environmental Pollution, 2024)

The fabrication of thin-film nanocomposite membrane for organic solvent forward osmosis via host-guest chemistry of α-cyclodextrin - Lin Wang; Fangkun Xiao; Haochen Ge; Yunbo Tong; Congjie Gao; Guiru Zhu (Desalination, 2024)

KOH-activated biochar and chitosan composites for efficient adsorption of industrial dye pollutants - Xu Su; Xuanming Wang; Ziyi Ge; Zhengrong Bao; Li Lin; Yixuan Chen; Wanning Dai; Yuanyuan Sun; Hechong Yuan; Wen Yang; Jun Meng; Hailong Wang; et al. (Chemical Engineering Journal, 2024)

Chitosan-derived carbon aerogel modified with lignin carbon quantum dots for efficient solar evaporation - Zichen Li; Dazhen Li; Shuxia Wei; Xin Jin; Zheng Zhang; Lin Liu; Yuanyuan Ge; Zhili Li (Chemical Engineering Journal, 2024)

Host-guest synergistic hydrogen bond triggered signal amplification for visualizing the plant hormone salicylic acid - A-Ling Tang; Li-Long Zhang; Shuai Tan; Ping Yang; Wei Niu; Mei-Hong Ge; Lin-Lin Yang; Pei-Yi Wang; Li-Wei Liu; Xiang Zhou; Song Yang (Chemical Engineering Journal, 2024)

Establishing a pulmonary aspergillus fumigatus infection diagnostic platform based on RPA-CRISPR-Cas12a - Chunhui Lin; Jing Zhou; Nana Gao; Runde Liu; Ge Li; Jinyu Wang; Guoping Lu; Jilu Shen (World Journal of Microbiology and Biotechnology, 2024)

CDC-like kinase 3 deficiency aggravates hypoxia-induced cardiomyocyte apoptosis through AKT signaling pathway - Xiue Ma; Liming Gao; Rucun Ge; Tianyou Yuan; Bowen Lin; Lixiao Zhen (In Vitro Cellular & Developmental Biology - Animal, 2024)

Ammoniated straw returning: A win-win strategy for increasing crop production and soil carbon sequestration - Jinchao Li; Yue Li; Nanping Lin; Yanxin Fang; Qin’ge Dong; Tibin Zhang; Kadambot H.M. Siddique; Naijiang Wang; Hao Feng (Agriculture, Ecosystems & Environment, 2024)

Multi-object detection and behavior tracking of sea cucumbers with skin ulceration syndrome based on deep learning - Fengli Ge; Kui Xuan; Peng Lou; Juan Li; Lingxu Jiang; Jiasheng Wang; Qi Lin (Frontiers in Marine Science, 2024)
Skin ulceration syndrome of sea cucumbers is one of the most serious diseases in intensive aquaculture, and it is the most effective way of preventing the spread of this disease to detect the abnormal behavior of sea cucumbers in time and take corresponding measures. However, the detection and tracking of multi-object is a hard problem in sea cucumber behavior analysis. To solve this problem, this paper first proposes a novel one-stage algorithm SUS-YOLOv5 for multi-object detection and tracking of sea cucumbers. The proposed SUS-YOLOv5 optimizes the maximum suppression algorithm in the overlapping region of the object detection box. Next, the SE-BiFPN feature fusion structure is proposed to enhance the transmission efficiency of feature information between deep and shallow layers of the network. Then, a MO-Tracking algorithm is proposed integrated with DeepSORT to achieve real-time multi-object tracking. Experimental results show that the mAP @0.5 and mAP @0.5:0.95 of the proposed object detector reach 95.40% and 83.80%, respectively, which are 3.30% and 4.10% higher than the original YOLOv5s. Compared with the traditional SSD, YOLOv3, and YOLOv4, the mAP of SUS-YOLOv5 is improved by 5.49%, 1.57%, and 3.76%, respectively. This research can realize the multi-object detection and tracking, which lays the foundation for the prediction of skin ulceration syndrome in sea cucumbers and has a certain practical application value for improving the intelligence level of aquaculture.

Research on anchoring force of the deep-sea stratum drilling robot - Peihao Zhang; Jiawang Chen; Yongqiang Ge; Xingshuang Lin; Xiaoling Le; Zixin Weng; Ziqiang Ren (Marine Georesources & Geotechnology, 2024)

Prediction of MSW pyrolysis products based on a deep artificial neural network - Yunfei Zang; Shaoheng Ge; Yu Lin; Lijie Yin; Dezhen Chen (Waste Management, 2024)

Characterization of key flavor substances and their microbial sources in traditional sour bamboo shoots - Hui Tang; Jin-Kui Ma; Lin Chen; Li-Wen Jiang; Lin-Zhi Kang; Ying-Yu Guo; Ge-Yang Men; Dan-Xia Nie; Rui-Min Zhong (Food Chemistry, 2024)

pH-responsive PVA/konjac glucomannan/functional liposome terpolymer composites: Spotlight on its structure-performance, functionality, barrier properties, controlled-release behavior, biodegradability, and its intelligent preservation role for food - Wei Liang; Xiangzhen Ge; Qian Lin; Li Niu; Wenqing Zhao; Xinyue Liu; Shuangfeng Guo; Marat Muratkhan; Wenhao Li (Food Packaging and Shelf Life, 2024)

Flutter control optimization for a 5000 m suspension bridge with active aerodynamic flaps: a CFD-enabled strategy - Zilong Wang; Lin Zhao; Yiheng Fu; Genshen Fang; Wei Cui; Ke Li; Yaojun Ge (Engineering Structures, 2024)

Spatio-temporal distribution of aerodynamic forces and their associated vortex drift patterns around a closed-box girder during torsional vortex-induced vibration - Chuanxin Hu; Lin Zhao; Xianglong Wang; Yaojun Ge (Engineering Structures, 2024)

Long-term hygrothermal performance assessment of wood-frame walls considering climate uncertainties using partial least squares (PLS) regression - Chetan Aggarwal; Lin Wang; Hua Ge; Maurice Defo; Michael Lacasse (Energy and Buildings, 2024)

Convergence or divergence? Unraveling the global development pattern of forest carbon sink - Jiamin Ge; Boqiang Lin (Environmental Impact Assessment Review, 2024)

Multiphase flow and reactor optimization of a 1MWth pilot-scale circulating fluidized bed for coal staged conversion - Yuxin Ge; Jiahui Yu; Junjie Lin; Shuai Wang; Kun Luo; Qinhui Wang; Jianren Fan (Chemical Engineering Journal, 2024)

Enlightening thermoelectric mastery: Bio-inspired cellulose gel containing eco-friendly deep eutectic solvents - Yuxi Chen; Gonghua Hong; Lei Li; Qing Qu; Guang Li; Jiajie Wu; Lin Ge (Chemical Engineering Journal, 2024)

Impact-induced fragmentation of coral reef limestone based on fractal theory - Yi Luo; Yueying Li; Hui Lin; Yongxiang Ge; Hangli Gong (Marine Geophysical Research, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

In-Line Inspection (ILI) Techniques for Subsea Pipelines: State-of-the-Art - Hai Zhu; Jiawang Chen; Yuan Lin; Jin Guo; Xu Gao; Yuanjie Chen; Yongqiang Ge; Wei Wang (Journal of Marine Science and Engineering, 2024)
Offshore oil and gas resources play a crucial role in supplementing the energy needs of human society. The crisscrossing subsea pipeline network, which serves as vital infrastructure for the storage and transportation of offshore oil and gas, requires regular inspection and maintenance to ensure safe operation and prevent ecological pollution. In-line inspection (ILI) techniques have been widely used in the detection and inspection of potential hazards within the pipeline network. This paper offers an overview of ILI techniques used in subsea pipelines, examining their advantages, limitations, applicable scenarios, and performance. It aims to provide valuable insights for the selection of ILI technologies in engineering and may be beneficial for those involved in pipeline integrity management and planning.

Effects of soil water content on Cd immobilization and uptake by leek with the combined application of biochar and organic fertilizer - Shuang Huang; Lei Xin; Zhuowen Meng; Haimeng Ge; Zhongbing Lin (Environmental Science and Pollution Research, 2024)

Improvement of non-specific immunity, intestinal health and microbiota of crucian carp (Carassius auratus) juvenile with dietary supplementation of Bacillus coagulans BC1 - Ren-Ge Hu; Bin-Tong Yang; Zi-Yan Zheng; Zhen-Lin Liang; Yuan-Huan Kang; Wei Cong (Aquaculture, 2024)

Simulated microgravity altered the gene expression profiles and inhibited the proliferation of Kupffer cells in the early phase by downregulating LMO2 and EZH2 - Jun Ge; Yuan Yue; Hong-Yun Nie; Kai-Ge Liu; Hao Li; Hai-Guan Lin; Tao Zhang; Hong-Feng Yan; Hong-Wei Sun; Jian-Wu Yang; Jin-Lian Zhou; Yan Cui (Life Sciences in Space Research, 2024)

Upcycling MSWI fly ash into green binders via flue gas-enhanced wet carbonation - Miao Lu; Weizhe Ge; Yan Xia; Chen Sun; Xiaoqing Lin; Daniel C.W. Tsang; Tung-Chai Ling; Yanjun Hu; Lei Wang; Jianhua Yan (Journal of Cleaner Production, 2024)

Self-assembly kieselguhr-based ZSM-5 for catalytic pyrolysis of mask waste to produce high value-added aromatics - Yufei Gu; Hucheng Ge; Yuke Liu; Qi Wei; Tianhua Gao; Hengshuo Gu; Hongbing Fu; Fuwei Li; Hongfei Lin; Lei Miao; Zhixia Li (Fuel, 2024)

Chalcones from plants cause toxicity by inhibiting human and rat 11β-hydroxysteroid dehydrogenase 2: 3D-quantitative structure-activity relationship (3D-QSAR) and in silico docking analysis - Hang Lin; Ming Su; Chao Wen; Yunbing Tang; Huitao Li; Yandan Wu; Ren-shan Ge; Xing-wang Li; Han Lin (Food and Chemical Toxicology, 2024)

The role of oxygen vacancy in CaO-Ca12Al14O33 materials derived from hydrocalumite for enhanced CO2 capture cyclic performance - Zheng Yuyuan; Ge Zhiwei; Sun Haocheng; Wang Liang; Zhang Shuang; Lin Xipeng; Chen Qicheng; Chen Haisheng (Chemical Engineering Journal, 2024)

Along-track Calibration of the Zhurong Rover Magnetometer - Hao Luo; Aimin Du; Yasong Ge; Ying Zhang; Haiying Li; Lin Tian; Kuixiang Zhang; Shuquan Sun; Lin Zhao; Zhi Li; Xiao Feng (Science China Earth Sciences, 2024)

Targeting Ferroptosis Promotes Functional Recovery by Mitigating White Matter Injury Following Acute Carbon Monoxide Poisoning - Shuhong Wang; Binyuan Xiong; Yin Tian; Quan Hu; Xuheng Jiang; Ji Zhang; Lin Chen; Ruilie Wang; Mo Li; Xin Zhou; Tianxi Zhang; Hongfei Ge; et al. (Molecular Neurobiology, 2024)

Multiple Pathways for the Enhancement of Wheat Growth by Chlorella vulgaris - Sheng-Nan Wang; Shu-Han Ge; Lin-Lan Zhuang; Jian Zhang (Journal of Plant Growth Regulation, 2024)

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

The Influence of Seamounts on the Enrichment of Rare Earth Elements in Sediments—A Case Study of the Marcus-Wake Seamounts in the Western Pacific Ocean - Tinglu Xiao; Dong Xu; Tao Deng; Junyu Lin; Liming Ye; Qian Ge; Xibin Han; Yanhui Dong; Fengyou Chu (Journal of Marine Science and Engineering, 2024)
Deep-sea sediments enriched in rare earth elements and yttrium (REY-rich sediments) are widely distributed on the deep-sea floor, and their formation mechanism remains elusive. Although studies have recognized the link between seamounts and REY-rich sediments, in-depth analysis of the specific roles and effects of seamounts in the formation of REY-rich sediments is lacking. In this study, we analyzed surface sediments from the Marcus-Wake Seamounts for grain size, geochemistry, and mineral composition and classified the samples into three types: samples with moderate REY content and dominated by terrestrial detritus; samples with high REY and authigenic mineral content; and samples rich in CaCO3 but poor in REY. The REY in the sediments of the study area partly originate from Asian dust input and partly from seawater and/or pore water, and are mainly enriched in REY carrier particles including bioapatite fossils and micronodules. The amount of REY carrier particles influences the REY content in the sediments. The current field, primary productivity, weathering process, and depositional environment around seamounts are different from those of abyssal plains, which are conducive to the formation of REY-rich sediments. Strong bottom currents may exist in the southeastern direction of some large seamounts (e.g., Niulang Guyot), leading to the selective accumulation of REY-rich bioapatite fossils and micronodules, resulting in the formation of REY-rich sediments.

Bacteriophages: Vectors of or weapons against the transmission of antibiotic resistance genes in hospital wastewater systems? - Xinyi Shuai; Zhenchao Zhou; Xiaoliang Ba; Yanhan Lin; Zejun Lin; Zhe Liu; Xi Yu; Jinyu Zhou; Guangshu Zeng; Ziye Ge; Hong Chen (Water Research, 2024)

ATR induces hepatic lipid metabolism disorder in rats by activating IRE1α/XBP1 signaling pathway - Honghao Qian; Yaming Zhao; Yiming Wang; Haotang Zhao; Jianwei Cui; Ziyu Wang; Hui Ye; Xiaoqi Fang; Zhili Ge; Yuezhu Zhang; Lin Ye (Toxicology, 2024)

Impact of heat on emergency hospital admissions related to kidney diseases in Texas: Uncovering racial disparities - Chunyu Guo; Erjia Ge; Manzhu Yu; Changwei Li; Xiangqian Lao; Shuang Li; Jason Glaser; Yongqun He; Marina Almeida-Silva; Sisi Meng; Wei-Chung Su; Junfeng Zhang; et al. (Science of The Total Environment, 2024)

Insights into the influence and mechanism of biomass substrate and thermal conversion conditions on FeN doped biochar as a persulfate activator for sulfamethoxazole removal - Yining Lin; Qiang Ge; Jinquan Wan; Yan Wang; Congyun Zhu (Science of The Total Environment, 2024)

Soil microbial diversity and network complexity drive the ecosystem multifunctionality of temperate grasslands under changing precipitation - Changchun Zhai; Lili Han; Chao Xiong; Anhui Ge; Xiaojing Yue; Ying Li; Zhenxing Zhou; Jiayin Feng; Jingyi Ru; Jian Song; Lin Jiang; Yunfeng Yang; et al. (Science of The Total Environment, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Design of bifunctional ultrathin MnO2 nanofilm with laccase-like activity for sensing environmental pollutants containing phenol groups - Sheng-Tao Wu; Hui-Qi Su; Qian-Xiang Xiao; Zhi-Yu Qiu; Gang-Qiang Huang; Man-Ni He; Yi Ge; Cong-Hui Wang; Ying-Wu Lin (Journal of Hazardous Materials, 2024)

Indoor air quality of urban public transportation stations in China: Based on air quality evaluation indexes - Lin Fan; Xu Han; Li Li; Hang Liu; Tanxi Ge; Xinqi Wang; Qin Wang; Hang Du; Liqin Su; Xiaoyuan Yao; Xianliang Wang (Journal of Environmental Management, 2024)

Magnetic-encoded fluorescent nanospheres-based competitive immunoassay for near-simultaneous detection of four mycotoxins in wheat - Xueqi Lin; Rui Ge; Jie Wei; Tianhui Jiao; Qingmin Chen; Munetaka Oyama; Quansheng Chen; Xiaomei Chen (Food Chemistry, 2024)

Engineering of zeolitic imidazolate frameworks based on magnetic three-dimensional graphene as effective and reusable adsorbent to enhance the adsorption and removal of caffeine from tea samples - Yuwei Hua; Guangyang Liu; Zhihao Lin; Zhou Jie; Chenxi Zhao; Jiatong Han; Ge Chen; Linyun Li; Xiaodong Huang; Zhongxiao Liu; Jun Lv; Donghui Xu (Food Chemistry, 2024)

Effect of N/P ratio on attached microalgae growth and the differentiated metabolism along the depth of biofilm - Weiyi Qian; Yanan Yang; Sai Chou; Shuhan Ge; Peihua Li; Xiaoxiong Wang; Lin-Lan Zhuang; Jian Zhang (Environmental Research, 2024)

Exploring the therapeutic potential of layered double hydroxides and transition metal dichalcogenides through the convergence of rheumatology and nanotechnology using generative adversarial network - Suxian Lin; Weiwei Chen; Mohammed S. Alqahtani; Dalia H. Elkamchouchi; Yisu Ge; Yanjie Lu; Guodao Zhang; Mudan Wang (Environmental Research, 2024)

Cellulose nanocrystals-based fluorescent biocarrier binding GAPDH protein with high affinity in cancer-target doxorubicin delivery - Xiaoping Zhao; Qin Wang; Ning Wang; Ge Zhu; Jingzhi Ma; Ning Lin (Carbohydrate Polymers, 2024)

A quantitative study on the characteristics of desiccation cracks and their effect on the shear failure characteristics of granite red soil - Yue Zhang; Yimin Huang; Zumei Wang; Menglu Shi; Jinshi Lin; Fangshi Jiang; Hongli Ge; Yanhe Huang (Bulletin of Engineering Geology and the Environment, 2024)

Isolation and identification of Chlorella sorokiniana HDMA-16 and its cultivation potential in flax retting wastewater - Meiqi Wang; Jing Xu; Jialin Zou; Hongzhi Ling; Jingping Ge; Yimeng Lin; Wenxiang Ping (Algal Research, 2024)

Spatialized importance of key factors affecting park cooling intensity based on the park scale - Zhihua Liu; Lizhao Fu; Chaofan Wu; Zhenzhen Zhang; Zhaoyang Zhang; Xingwen Lin; Xuan Li; Yuhong Hu; Haixian Ge (Sustainable Cities and Society, 2023)

Preclinical evaluation of RQ3013, a broad-spectrum mRNA vaccine against SARS-CoV-2 variants - Shudan Tan; Jinghua Zhao; Xue Hu; Yufeng Li; Zihan Wu; Guoliang Lu; Zhaoli Yu; Binhe Du; Yan Liu; Li Li; Yuchen Chen; Ye Li; et al. (Science Bulletin, 2023)

pH-Responsive graphene oxide/poly (methacrylic acid) hybrid nanofiltration membrane performance for water treatment - Li-yue Sun; De-hao Yu; Zhao-ge Juan; Yao Wang; Yan-xin Wang; Matt J. Kipper; Lin-jun Huang; Jian-guo Tang (Journal of Environmental Chemical Engineering, 2023)

Composition engineering of carbon nanotubes supported Pt RhRu ultrafine nanocatalysts for ethanol electro-oxidation: Elucidating the role of trimetallic sites - Chang Liu; Xinwei Wen; Lin Ge; Yuxi Chen; Jiajie Wu; Qing Qu; Lei Li (Chemical Engineering Journal, 2023)

Associations of 10 trace element levels in the whole blood with risk of three types of obesity in the elderly - Rui Zhan; Lin Liu; Maoyuan Yang; Yating Ren; Zhihao Ge; Jun Shi; Ke Zhou; Jiebao Zhang; Hongjuan Cao; Linsheng Yang; Kaiyong Liu; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

Rapid Genotyping of Campylobacter coli Strains from Poultry Meat by PFGE, Sau-PCR, and fla-DGGE - Ge-Feng Yao; Yi-Lin Hu; Nian-Qing Kong; Jin-Hong Liu; Yong-Wen Luo; Chu-Yi Li; Shui-Lian Bi (Current Microbiology, 2023)

Determination of niclosamide and its two metabolites in fish by molecularly imprinted microsphere-based pseudo-ELISA - Hao Zhe Hou; Yan Su; Ge Lin Liu; Yao Jia Peng; Jian Ping Wang (Food Additives & Contaminants: Part A, 2023)

The effects of long-term exposure to air pollution on incident mental disorders among patients with prediabetes and diabetes: Findings from a large prospective cohort - Jin Feng; Miao Cai; Zhengmin (Min) Qian; Shiyu Zhang; Yin Yang; Stephen Edward McMillin; Ge Chen; Junjie Hua; Maya Tabet; Chongjian Wang; Xiaojie Wang; Hualiang Lin (Science of The Total Environment, 2023)

Dual roles of the Arabidopsis PEAT complex in histone H2A deubiquitination and H4K5 acetylation - Si-Yao Zheng; Bin-Bin Guan; Dan-Yang Yuan; Qiang-Qiang Zhao; Weiran Ge; Lian-Mei Tan; Shan-Shan Chen; Lin Li; She Chen; Rui-Ming Xu; Xin-Jian He (Molecular Plant, 2023)

Meta-analysis of microbial source tracking for the identification of fecal contamination in aquatic environments based on data-mining - Zejun Liu; Yingying Lin; Yanhong Ge; Ziyue Zhu; Jinlong Yuan; Qidong Yin; Bingjun Liu; Kai He; Maochuan Hu (Journal of Environmental Management, 2023)

Emissions from international airport and its impact on air quality: A case study of beijing daxing international airport (PKX), China - Ya-nan Wang; Chao Zou; Tian-ge Fang; Nai-xiu Sun; Xiao-yu Liang; Lin Wu; Hong-jun Mao (Environmental Pollution, 2023)

Surface plasmon resonance-enhanced cascaded sensitization effect of CuInSe2/Cu3(BTC)2/Y:ZnO photosensitive structures enabled lab-on-paper photoelectrochemical bioassay - Guofu Wang; Lin Li; Yuheng Li; Yuxin Hao; Qiuyi Li; Lina Zhang; Shenguang Ge; Peihua Zhu; Hongmei Yang; Jinghua Yu (Chemical Engineering Journal, 2023)

Generating high spatial resolution exposure estimates from sparse regulatory monitoring data - Yihui Ge; Zhenchun Yang; Yan Lin; Philip K. Hopke; Albert A. Presto; Meng Wang; David Q. Rich; Junfeng Zhang (Atmospheric Environment, 2023)

Homozygous variants in CDC23 cause female infertility characterized by oocyte maturation defects - Huizhen Fan; Zhou Zhou; Wei Zheng; Yichun Guan; Qingxia Meng; Wenjing Wang; Jie Dong; Liuxia Wan; Jiawei Zhu; Yang Zeng; Ruyi Liu; Hao Gu; et al. (Human Genetics, 2023)

The connection between six common air pollution particles and adult brain tumors: a meta-analysis of 26,217,930 individuals - Lu-Ting Shen; Meng-Wei Ge; Fei-Hong Hu; Yi-Jie Jia; Wen Tang; Wan-Qing Zhang; Dan-Yan Zhao; Wang-Qin Shen; Hong-Lin Chen (Environmental Science and Pollution Research, 2023)

Cost-effective one-spot hydrothermal synthesis of graphene oxide nanoparticles for wastewater remediation: AI-enhanced approach for transition metal oxides - Huang Zhongguan; Zhou Qiang; Lin Sen; Guodao Zhang; Ahmed Nadeem; Yisu Ge (Chemosphere, 2023)

Effects of dietary trimetlylamine oxide on the growth performance, feed utilization and appetite regulation of Chinese mitten crab (Eriocheir sinensis) - Mengge Li; Anran Wang; Xue Lin; Hanfeng Miao; Xuran Liu; Jie Xu; Xingkong Ma; Yingke Wu; Xiaojing Dong; Jiachun Ge; Shuyan Miao (Aquaculture, 2023)

Aged polycyclic aromatic hydrocarbons as stratigraphic marker in the Anthropocene: Evidence from Tibetan Lake sediments - Jun Li; Ruwen Chang; Xiyu Ban; Guo-Li Yuan; Xinyu Du; Ge Yin; Tian Lin (Water Research, 2023)

Novel and legacy brominated flame retardants in snakes and frogs: Tissue distribution, biomagnification, and maternal transfer - Guanzhen Sun; Xinyu Du; Yan Wu; Ge Yin; Luting Chen; Xiaojun Liu; Yihui Zhou; Yanling Qiu; Tian Lin (Science of The Total Environment, 2023)

Associations of Life’s Essential 8 and fine particulate matter pollution with the incidence of atrial fibrillation - Junguo Zhang; Ge Chen; Hui Xia; Xiaojie Wang; ChongJian Wang; Miao Cai; Yanhui Gao; Gregory Y.H. Lip; Hualiang Lin (Journal of Hazardous Materials, 2023)

Convergence of soil bacterial communities with time and reduction of bacterial interaction complexity in response to meso- and microplastic stress - Lin Yue; Yangbo Liu; Guanhui Li; Hui Deng; Yuanyuan Zhao; Dan Feng; Hongfei Sun; Huamei Yu; Chengjun Ge; Haiying Chen (Journal of Environmental Chemical Engineering, 2023)

Experimental study on Diels-Alder addition of conjugated dienes directly from cracking C5 fraction by continuous micro-channel reactors - Zehao Jing; Tingting Ge; Hui Guo; Yuchao Li; Zhou Li; Cuncun Zuo; Ming Wang; Haofei Huang; Lin Guo; Guangjun Cui (Fuel, 2023)

Emission characteristics of (halogenated) polycyclic aromatic hydrocarbons during printed circuit board combustion and estimated emission intensity of a typical e-waste dismantling site in South China - Xiang Ge; Muhammad Zaffar Hashmi; Shuo Lin; Zenghua Qi; Yingxin Yu; Taicheng An (Environmental Pollution, 2023)

Steel-concrete composite beams strengthened with NSM CFRP systems at the hogging-moment regions - Weikang Gong; Xinkai Li; Zengjun Ge; Huining Liu; Zhansheng Lin; Xiaoyang Liu; Guotao Yang (Engineering Structures, 2023)

Multi-scale domain and microstructure engineering for the high-energy-storage BCZT based lead-free relaxor ferroelectric ceramics - Jiayue Song; Fei Yan; Jinfeng Lin; Guanglong Ge; Cheng Shi; Jin Qian; Yali Hao; Yongqi Wei; Wu Yao (Chemical Engineering Journal, 2023)

Dual Förster resonance energy transfer effects enables high photocurrent density and high fill factor in ternary organic solar cells - Hongqian Wang; Daobin Yang; Pengfei Ding; Lin Xie; Zhenyu Chen; Shuncheng Yang; Pengyu Yan; Yuanyuan Meng; Jianqi Zhang; Zhixiang Wei; Ziyi Ge (Chemical Engineering Journal, 2023)

Size-dependent chemical composition of atmospheric nanoparticles in urban Beijing during springtime - Yan Chen; Chenjuan Deng; Ting Lei; Junling Li; Chaofan Lian; Yiran Li; Jun Zheng; Jun Zhao; Dongbin Wang; Zhijun Wu; Lin Wang; Lei Li; et al. (Atmospheric Environment, 2023)

Single-Cell RNA-seq Analysis of a Human Embryonic Stem Cell to Endothelial Cell System Based on Transcription Factor Overexpression - XiangWang Xu; JunRu Chen; Hao Zhao; YuZe Pi; Ge Lin; Liang Hu (Stem Cell Reviews and Reports, 2023)

Cascade signal amplification strategy by coupling chemical redox-cycling and Fenton-like reaction: Toward an ultrasensitive split-type fluorescent immunoassay - Lin-Ge Chen; Lu Sun; Ning-Ning Wu; Bei-Bei Tao; Hai-Bo Wang (Analytica Chimica Acta, 2023)

Associations of metal mixtures with thyroid function and potential interactions with iodine status: results from a cross-sectional study in MEWHC - Xiaoting Ge; Junxiu He; Sencai Lin; Yu Bao; Yuan Zheng; Hong Cheng; Haiqing Cai; Xiuming Feng; Wenjun Yang; Sihan Hu; Lin Wang; Qijing Liao; et al. (Environmental Science and Pollution Research, 2023)

A comprehensive investigation on source apportionment and multi-directional regional transport of volatile organic compounds and ozone in urban Zhengzhou - Xiaoxi Zeng; Mengjuan Han; Ge Ren; Gege Liu; Xiaoning Wang; Kailun Du; Xiaodong Zhang; Hong Lin (Chemosphere, 2023)

Efficacy of transplant insecticides against black cutworm Agrotis ipsilon (Lepidoptera: Noctuidae) in tobacco - Pingping Liu; Jingxin Zhang; Huifang Shen; Qiyun Yang; Xiaoming Pu; Dayuan Sun; Baiyi Ge; Birun Lin (Crop Protection, 2023)

Uncertainty propagation of turbulence parameters for typhoon and Non-typhoon winds in buffeting analysis of Long-span bridges - Zihang Liu; Genshen Fang; Lin Zhao; Yaojun Ge (Engineering Structures, 2023)

How to extend the lifetime of RO membrane? From the perspective of the end-of-life RO membrane autopsy - Jinyan Wang; Jingrun Xing; Ge Li; Zhikan Yao; Zhen Ni; Jing Wang; Songmiao Liang; Zhijun Zhou; Lin Zhang (Desalination, 2023)

A waste textiles-based multilayer composite fabric with superior electromagnetic shielding, infrared stealth and flame retardance for military applications - Yuhan Zhang; Guodong Shen; Su Shiung Lam; Sabah Ansar; Sang-Chul Jung; Shengbo Ge; Lin Hou; Zhengke Fan; Feng Wang; Wei Fan (Chemical Engineering Journal, 2023)

Development of Au8 nanocluster-based fluorescent strip immunosensor for sensitive detection of aflatoxin B1 - Zi-Hui Shao; Aoqiang Zhai; Yue Hua; Hui-Lin Mo; Fuwei Xie; Xueli Zhao; Ge Zhao; Shuang-Quan Zang (Analytica Chimica Acta, 2023)

Multiple genotypes infection and molecular characterization of Torque teno neovison virus: A novel Anelloviridae of mink in China - Weizhi Xin; Zhiyuan Guo; Lin Wang; Yifan Li; Haikun Shangguan; Kun Xue; Hongyan Chen; Hongliang Yang; Lili Zhao; Junwei Ge (Research in Veterinary Science, 2023)

Metagenome-based analysis of carbon-fixing microorganisms and their carbon-fixing pathways in deep-sea sediments of the southwestern Indian Ocean - Xiao-Lan Yue; Lin Xu; Li Cui; Ge-Yi Fu; Xue-Wei Xu (Marine Genomics, 2023)

Designing low-carbon cement-free binders for stabilization/solidification of MSWI fly ash - Chen Sun; Weizhe Ge; Yuying Zhang; Lei Wang; Yan Xia; Xiaoqing Lin; Qunxing Huang; Shengyong Lu; Daniel C.W. Tsang; Jianhua Yan (Journal of Environmental Management, 2023)

Hepatotoxicity screening and ranking of structurally different pyrrolizidine alkaloids in zebrafish - Yueyang Pan; Jiang Ma; Hui Zhao; Peter P. Fu; Ge Lin (Food and Chemical Toxicology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Understanding the effects of tree-crop intercropping systems on crop production in China by combining field experiments with a meta-analysis - Tao Yang; Xueying Ouyang; Bo Wang; Di Tian; Cheng Xu; Zeyang Lin; Xiaomin Ge; Luozhong Tang (Agricultural Systems, 2023)

A time-series analysis of short-term ambient ozone exposure and hospitalizations from acute myocardial infarction in Henan, China - Yulong Wei; Lin Fei; Yongbin Wang; Min Zhang; Zhigang Chen; Huige Guo; Shiqi Ge; Sen Zhu; Pingshuan Dong; Kan Yang; Na Xie; Guoan Zhao (Environmental Science and Pollution Research, 2023)
Epidemiological studies in recent years have identified an association between exposure to air pollutants and acute myocardial infarction (AMI); however, the association between short-term ozone (O 3 ) exposure and AMI hospitalization remains unclear, particularly in developing countries. Therefore, this study collected information on 24,489 AMI patients, including daily air pollutant and meteorological data in Henan, China, between 2016 and 2021. A distributed lagged nonlinear model combined with a Poisson regression model was used to estimate the nonlinear lagged effect of O 3 on AMI hospitalizations. We also quantified the effects of O 3 on the number of AMI hospitalizations, hospitalization days, and hospitalization costs. The results showed that single- and dual-pollution models of O 3 at lag0, lag1, and lag (01–07) were risk factors for AMI hospitalizations, with the most significant effect at lag03 (RR = 1.132, 95% CI:1.083–1.182). Further studies showed that males, younger people (15–64 years), warm seasons, and long sunshine duration were more susceptible to O 3 . Hospitalizations attributable to O 3 during the study period accounted for 11.66% of the total hospitalizations, corresponding to 2856 patients, 33,492 hospital days, and 90 million RMB. Maintaining O 3 at 10–130 µg/m 3 can prevent hundreds of AMI hospitalizations and save millions of RMB per year in Henan, China. In conclusion, we found that short-term exposure to O 3 was significantly associated with an increased risk of hospitalization for AMI in Henan, China, and that further reductions in ambient O 3 levels may have substantial health and economic benefits for patients and local healthcare facilities. Graphical Abstract

Advances in preparation, interaction and stimulus responsiveness of protein-based nanodelivery systems - Qianzhu Lin; Shengju Ge; David Julian McClements; Xiaojing Li; Zhengyu Jin; Aiquan Jiao; Jinpeng Wang; Jie Long; Xueming Xu; Chao Qiu (Critical Reviews in Food Science and Nutrition, 2023)

Two new isoflavones from the barks of Dalbergia hancei Benth - Xiao-Mei Li; Nao Pang; Ya-Feng Wang; Rui-Jie He; Li Ge; Bing-Yuan Yang; Ke-Di Yang; Yong-Lin Huang (Natural Product Research, 2023)

Spatiotemporal dynamics of near-surface ozone concentration and potential source areas in northern China during 2015—2020 - Kang Ma; Yuesheng Lin; Fengman Fang; Huarong Tan; Jingwen Li; Lei Ge; Fei Wang; Youru Yao (Environmental Science and Pollution Research, 2023)

A stabilizing benders decomposition method for the accessibility-oriented charging station location problem - Maocan Song; Lin Cheng; Huimin Ge; Yan Li; Chao Sun (Sustainable Cities and Society, 2023)

Obstacle avoidance based on double closed loop control of autonomous underwater vehicle for submarine cable laying - Wei-ran Wang; Zhe-hao Su; Hui-lin Ge; Xiao-Qiang Dai; Zhi-yu Zhu; Jie Yao; Qing-jun Zeng (Ocean Engineering, 2023)

Experimental evaluation of dimension-stable synthetic fibre rope under investigation of spooling test on the multilayer winch drum - Haoran Ye; Wenhua Li; Hongxin Zhang; Shanying Lin; Dinghua Zhang; Yangyuan Ge; Zehua Li (Ocean Engineering, 2023)

Coupling activation and curing to tune the permselectivity of poly(piperazine amide) nanofiltration membranes - Dongsheng Zhao; Jiyu Song; Yiwen Zhang; Zhiquan Lin; Bo He; Nanfu Qiao; Kangping Huang; Wei Zhang; Shuang Ge; Yuying Li; B. Larry Li; Kang Xie; et al. (Journal of Water Process Engineering, 2023)

Effective adsorption and removal of malachite green and Pb2+ from aqueous samples and fruit juices by pollen–inspired magnetic hydroxyapatite nanoparticles/hydrogel beads - Yuwei Hua; Donghui Xu; Zhongxiao Liu; Jie Zhou; Jiatong Han; Zhihao Lin; Dan Xu; Ge Chen; Xiaodong Huang; Jing Chen; Jun Lv; Guangyang Liu (Journal of Cleaner Production, 2023)

Aroma correlation assisted volatilome coupled network analysis strategy to unveil main aroma-active volatiles of Rosa roxburghii - Ya-Hui Ge; Xue Li; Mingzheng Huang; Zhengxu Huang; Manman Wu; Baoqing Sun; Lishuang Wang; Jian-Lin Wu; Na Li (Food Research International, 2023)

Emission and gas-particle partitioning characteristics of atmospheric halogenated and organophosphorus flame retardants in decabromodiphenyl ethane-manufacturing functional areas - Helong Ren; Xiang Ge; Zenghua Qi; Qinhao Lin; Guofeng Shen; Yingxin Yu; Taicheng An (Environmental Pollution, 2023)

Conductive metal-organic frameworks with wheel-shaped metallomacrocycle subunits as high-performance supercapacitor electrodes - Yong Yan; Xihao Lin; Jingyuan Ge; Xinhua Li (Chemical Engineering Journal, 2023)

Phosphorus amendment alters soil arbuscular mycorrhizal fungal functional guild compositions in a subtropical forest - Quan-Cheng Wang; Sheng-Sheng Jin; Shanshan Liu; Ge Song; Chunjian Duan; Peng-Peng Lü; Pulak Maitra; Lin Xie; Yongxin Lin; Hang-Wei Hu; Ji-Zheng He; Yong Zheng (Journal of Soils and Sediments, 2023)

Benzophenone-type ultraviolet filters inhibit human and rat placental 3β-hydroxysteroid dehydrogenases: Structure-activity relationship and in silico docking analysis - Hao Lin; Shaowei Wang; Yunbing Tang; Zhiyan Hu; Xiaofang Chen; Huitao Li; Yang Zhu; Yiyan Wang; Yi Liu; Ren-shan Ge (Toxicology Letters, 2023)

Quantified trend of photosynthetic rate along the depth of microalgae biofilm - Lin-Lan Zhuang; Wanqing Tian; Yanan Yang; Shuhan Ge; Peihua Li; Shuo Sun; Jian Zhang; Shuang Liang (Science of The Total Environment, 2023)

Microplastics exacerbate co-occurrence and horizontal transfer of antibiotic resistance genes - Xi Yu; Zhen-Chao Zhou; Xin-yi Shuai; Ze-jun Lin; Zhe Liu; Jin-yu Zhou; Yan-han Lin; Guang-shu Zeng; Zi-ye Ge; Hong Chen (Journal of Hazardous Materials, 2023)

Ultrabright orange-yellow aggregation-induced emission nanoparticles for highly sensitive immunochromatographic quantification of ochratoxin A in corn - Guoxin Chen; Xirui Chen; Ge Xu; Xiaxia Wei; Xiangkai Lin; Yu Su; Yonghua Xiong; Xiaolin Huang (Food Chemistry, 2023)

Superior efficiency hydrogen peroxide production in acidic media through epoxy group adjacent to Co-O/C active centers on carbon black - Jili Yuan; Hao Yin; Xin Ge; Ronglan Pan; Caijuan Huang; Dechao Chen; Lin Hu; Haibo Xie (Chemical Engineering Journal, 2023)

Association between nitrogen dioxide concentration and hypertension hospitalization: A multicenter time-series analysis in Xinxiang, China - Shi-qi Ge; Yong-bin Wang; Fei Lin; Run-ran Miao; Kai Zhang; Li Li; Hui-ge Guo; Qian Wang; Li Zhang; Zhi-gang Chen; Guo-an Zhao (Atmospheric Pollution Research, 2023)

Deletion of the cheZ gene results in the loss of swimming ability and the decrease of adhesion ability to Caco-2 cells in Escherichia coli Nissle 1917 - Bingming Ou; Haihui Lv; Hua Ge; Dexiang Fu; Xin Lin; Saiqiao Huang; Xiaojie Chen; Yufu Liu; Sainan Li; Wenhua Liu; Lihua Huang; Ying Yang; et al. (Folia Microbiologica, 2023)

Transcriptome analysis reveals the feeding response and oxidative stress in juvenile Micropterus salmoides fed a low-fish-meal diet with enzyme-hydrolysed intestinal mucosa protein substitution - Heng Yu; Xianping Ge; Lin Zhang; Xiaoru Chen; Mingchun Ren; Hualiang Liang (Aquaculture, 2023)

Coordination environment dependent stability of Cu-based MOFs towards selective adsorption desulfurization - Canyang Zhang; Xiangdong Xue; Jiangtao Liu; Jing Lin; Xiaowei Zhang; Jitti Kasemchainan; Hongyi Gao; Ge Wang; Xingtian Shu (Chemical Engineering Journal, 2023)

RETRACTED: Production of biochar from tropical fruit tree residues and ecofriendly applications – A review - Zheli Ding; Yu Ge; Sarath C. Gowd; Ekta Singh; Vinay Kumar; Deepshi Chaurasia; Vikas Kumar; Karthik Rajendran; Preeti Chaturvedi Bhargava; Peicong Wu; Fei Lin; Sharareh Harirchi; et al. (Bioresource Technology, 2023)

Au/SiNCA-based SERS analysis coupled with machine learning for the early-stage diagnosis of cisplatin-induced liver injury - Shengjie Ge; Gaoyang Chen; Dawei Cao; Hechuan Lin; Ziyang Liu; Meng Yu; Shiyi Wang; Zhigang Wang; Ming Zhou (Analytica Chimica Acta, 2023)

Construction of ZnIn2S4/MOF-525 heterojunction system to enhance photocatalytic degradation of tetracycline - Xiansheng Zhang; Zhifeng Liu; Binbin Shao; Ting Wu; Yuan Pan; Songhao Luo; Miao He; Lin Ge; Jingwen Sun; Chunyun Cheng; Jian Huang (Environmental Science and Pollution Research, 2023)

A weighted contextual active fire detection algorithm based on Himawari-8 data - Han Zhang; Lin Sun; Chunkai Zheng; Shuai Ge; Jinpeng Chen; Jiayin Li (International Journal of Remote Sensing, 2023)

Surface wave exploration technology for the tunnel overlying strata with vehicle vibration source - Yuefeng Yan; Chengyu Sun; Tengfei Lin; Jiao Wang; Xixi Huang; Qixin Ge; Dayong Zhou (Tunnelling and Underground Space Technology, 2023)

New methods based on a genetic algorithm back propagation (GABP) neural network and general regression neural network (GRNN) for predicting the occurrence of trihalomethanes in tap water - Kangle Liu; Tao Lin; Tingting Zhong; Xinran Ge; Fuchun Jiang; Xue Zhang (Science of The Total Environment, 2023)

Toward sustainable inland aquaculture: Coastal subsidence monitoring in Taiwan - Wei-Chia Hung; Cheinway Hwang; Luigi Tosi; Shao-Hung Lin; Pei-Ching Tsai; Yi-An Chen; Wei-Ji Wang; En-Cheng Li; Sihao Ge (Remote Sensing Applications: Society and Environment, 2023)

Antioxidant soy peptide can inhibit xanthine oxidase activity and improve LO2 cell damage - Yifei Dong; Na Sun; Qi Ge; Renzhi Lv; Songyi Lin (Food Bioscience, 2023)

RETRACTED: Valorization of tropical fruits waste for production of commercial biorefinery products – A review - Zheli Ding; Yu Ge; Taner Sar; Vinay Kumar; Sharareh Harirchi; Parameswaran Binod; Ranjna Sirohi; Raveendran Sindhu; Peicong Wu; Fei Lin; Zengqiang Zhang; Mohammad J. Taherzadeh; et al. (Bioresource Technology, 2023)

Surface patterns of mortar plates influence Spirulina platensis biofilm attached cultivation: Experiment and modeling - Yongqiang Wang; Lu Li; Danyue Zhao; Wenjun Zhou; Lin Chen; Ge Su; Zhaohui Zhang; Tianzhong Liu (Algal Research, 2023)

Dispersal limitation and host selection drive geo-specific and plant-specific differentiation of soil bacterial communities in the Tibetan alpine ecosystem - Sai Qu; Congcong Shen; Lin Zhang; Jichen Wang; Li-Mei Zhang; Baodong Chen; Guo-Xin Sun; Yuan Ge (Science of The Total Environment, 2023)

Explication on distribution patterns of volatile organic compounds in petro-chemistry and oil refineries of China using a species-transport model and health risk assessment - Ting Zhang; Wei Kang; Xiang Ge; Qinhao Lin; Qiang Chen; Yingxin Yu; Taicheng An (Science of The Total Environment, 2023)

Validation and calibration of partitioned integral ocean wave parameters from co-polarized synthetic aperture radar data - Xuan Wang; Xinle Wang; Lin Ge (Remote Sensing of Environment, 2023)

Accelerated removal of five pesticide residues in three vegetables with ozone microbubbles - Xiaohan Li; Chengcheng Liu; Fengmao Liu; Xianzhao Zhang; Qingrong Peng; Ge Wu; Jin Lin; Zhanping Zhao (Food Chemistry, 2023)

Metal-organic framework nanocrystals enabled efficient and durable two-step perovskite photovoltaics - Xiao Liang; Kang Zhou; Dawei Duan; Fei Wang; Chuangye Ge; Xianfang Zhou; Mingjian Yuan; Yumeng Shi; Haoran Lin; Quanyao Zhu; Gang Li; Hanlin Hu (Chemical Engineering Journal, 2023)

Response characteristics of antibiotic resistance genes and bacterial communities during agricultural waste composting: Focusing on biogas residue combined with biochar amendments - Yuewei He; Xiaowei Yin; Fanghong Li; Bo Wu; Ling Zhu; Dabing Ge; Nanyi Wang; Anwei Chen; Lihua Zhang; Binghua Yan; Hongli Huang; Lin Luo; et al. (Bioresource Technology, 2023)

Extreme wind speed prediction in mountainous area with mixed wind climates - Teng Ma; Wei Cui; Lin Zhao; Ding Yejun; Fang Genshen; Yaojun Ge (Stochastic Environmental Research and Risk Assessment, 2023)

Advantages of aggregation-induced luminescence microspheres compared with fluorescent microspheres in immunochromatography assay with sandwich format - Xiaxia Wei; Xirui Chen; Zilong Liu; Ge Xu; Guoxin Chen; Xiangkai Lin; Wenchao Zhan; Xiaolin Huang; Yonghua Xiong (Analytica Chimica Acta, 2023)

Enhanced Lipid Productivity in Low-Starch Mutant of Monoraphidium sp. for Biodiesel Production - Yimeng Lin; Yunye Zhang; Yang Fan; Chang Li; Hongzhi Ling; Wenxiang Ping; Jingping Ge (BioEnergy Research, 2023)

Targeting erythrocyte-mediated hypoxia to alleviate lung injury induced by pyrrolizidine alkaloids - Zijing Song; Wei Lian; Yisheng He; Chunyuan Zhang; Ge Lin (Archives of Toxicology, 2023)

Similarity Study of Electromagnetic and Underwater Acoustic Scattering by Three-Dimensional Targets in Unbounded Space - Jie Wang; Hai Lin; Huaihai Guo; Qi Zhang; Junxiang Ge (Journal of Marine Science and Engineering, 2023)
The characterization of targets by electromagnetic (EM) scattering and underwater acoustic scattering is an important object of research in these two related fields. However, there are some difficulties in the simulation and measurement of the scattering by large targets. Consequently, a similarity study between acoustic and EM scattering may help to share results between one domain and the other and even provide a general reference method for the simulation of scattering characteristics in both fields. Based on the method of physical optics, the similarity between the EM scattering of conductors and the acoustic scattering of soft/hard targets and the similarity between the EM scattering of dielectrics and the acoustic scattering of elastics are studied. In particular, we derive how to transfer quantities from one domain into another so that similar scattering patterns arise. Then, according to these transfer rules, the EM scattering and acoustic scattering of three typical targets with different types of boundaries were simulated and measured, and the simulated EM scattering and acoustic scattering curves were found to be in perfect agreement, with correlation coefficients above 0.93. The correlation coefficients between the electromagnetic and acoustic scattering patterns were above 0.98, 0.91, and 0.65 for three typical targets. The simulated and measured scattering results verify the proposed similarity theory of EM and acoustic scattering, including the transfer from one domain into the other and the conditions of EM and acoustic scattering, and illustrate that the acoustic scattering characteristic of the target can be simulated using the EM scattering based on the derived conditions and vice versa.

Improving the genome and proteome annotations of the marine model diatom Thalassiosira pseudonana using a proteogenomics strategy - Xiao-Huang Chen; Ming-Kun Yang; Yuan-Yuan Li; Zhang-Xian Xie; Shu-Feng Zhang; Mats Töpel; Shady A. Amin; Lin Lin; Feng Ge; Da-Zhi Wang (Marine Life Science & Technology, 2023)
Diatoms are unicellular eukaryotic phytoplankton that account for approximately 20% of global carbon fixation and 40% of marine primary productivity; thus, they are essential for global carbon biogeochemical cycling and climate. The availability of ten diatom genome sequences has facilitated evolutionary, biological and ecological research over the past decade; however, a complimentary map of the diatom proteome with direct measurements of proteins and peptides is still lacking. Here, we present a proteome map of the model marine diatom Thalassiosira pseudonana using high-resolution mass spectrometry combined with a proteogenomic strategy. In-depth proteomic profiling of three different growth phases and three nutrient-deficient samples identified 9526 proteins, accounting for ~ 81% of the predicted protein-coding genes. Proteogenomic analysis identified 1235 novel genes, 975 revised genes, 104 splice variants and 234 single amino acid variants. Furthermore, our quantitative proteomic analysis experimentally demonstrated that a considerable number of novel genes were differentially translated under different nutrient conditions. These findings substantially improve the genome annotation of T. pseudonana and provide insights into new biological functions of diatoms. This relatively comprehensive diatom proteome catalog will complement available diatom genome and transcriptome data to advance biological and ecological research of marine diatoms.

Optimization and mechanism of coupling process between algal ponds and constructed wetlands for wastewater polishing and nutrient recovery - Pengfei Yang; Shuhan Ge; Zhiqiang Liu; Lin-Lan Zhuang; Weijiang Li; Chao Liu; Jian Zhang (Journal of Cleaner Production, 2023)

Solvent-free oxidation of toluene to benzaldehyde using electron-rich Au clusters confined in Silicalite-1 - He Huang; Huahua Fan; Yuzhen Ge; Wanyue Ye; Yingcen Liu; Caicheng Song; Hua Lin; Xiaotong Zhang; Bing Li; Xiaowa Nie; Shufen Zhang; Rongwen Lu (Chemical Engineering Journal, 2023)

Synergistically enhanced structural, thermal and interfacial stability of K0.45MnO2 via tailoring the local structure for high-energy and high-power potassium-ion batteries - Yan Huang; Xinyuan Zhang; Hezhe Lin; Zhixuan Wei; Yi Zeng; Xin Ge; Wei Zhang; Xiaoqi Wang; Xu Jin; Ze Xiang Shen; Fei Du (Chemical Engineering Journal, 2023)

Temperature and Humidity Effects on the Dynamic Stiffness of a Polyester Mooring Rope - Wenhua Li; Xiongyan Liu; Gen Li; Shanying Lin; Hangyu Li; Yangyuan Ge (Journal of Marine Science and Engineering, 2023)
In this paper, the nonlinear stiffness of a polyester rope under dynamic loads at different temperatures was experimentally investigated. The effects and evolution of the average load, load period and load amplitude on dynamic stiffness were studied. The experimental results show that the dynamic stiffness at 30 °C was greater than that at 20 °C and 40 °C. This is because the dynamic stiffness reduced as the temperature and humidity increased, while in the closed thermostat, humidity decreased with an increase in temperature. In response to this phenomenon, a new set of empirical equations was proposed to consider temperature, humidity, and dynamic load based on the existing empirical formulas, by combining the experimental results. A set of experiments was conducted at 25 °C to verify the accuracy and applicability of the formula. The experimental results and the predicted results are in good agreement.

The hybrid Pelteobagrus fulvidraco (♀) × Leiocassis longirostris (♂) exhibits improved trait on hypoxia-tolerance - Hongyu Wang; Ge Lin; Jie Zhou; Yongqin Zong; Xianhui Ning; Tao Wang; Shaowu Yin; Kai Zhang; Jie Ji (Aquaculture, 2023)

Screening of microalgae species and evaluation of algal-lipid stimulation strategies for biodiesel production - Yanan Yang; Shuhan Ge; Yitong Pan; Weiyi Qian; Shengnan Wang; Jian Zhang; Lin-Lan Zhuang (Science of The Total Environment, 2023)

Application of carbon aerogel-based materials in persulfate activation for water treatment: A review - Binbin Shao; Yuantao Xu; Zhifeng Liu; Ting Wu; Yuan Pan; Xiansheng Zhang; Miao He; Lin Ge; Yue Lu; Yang Liu; Weimin Zeng; Lin Tang (Journal of Cleaner Production, 2023)

Measurement of atmospheric nanoparticles: Bridging the gap between gas-phase molecules and larger particles - Chao Peng; Chenjuan Deng; Ting Lei; Jun Zheng; Jun Zhao; Dongbin Wang; Zhijun Wu; Lin Wang; Yan Chen; Mingyuan Liu; Jingkun Jiang; Anpei Ye; et al. (Journal of Environmental Sciences, 2023)

Atmospheric chemistry of nitrous acid and its effects on hydroxyl radical and ozone at the urban area of Beijing in early spring 2021 - Wenqian Zhang; Shengrui Tong; Deng Lin; Fangjie Li; Xinran Zhang; Lili Wang; Dongsheng Ji; Guiqian Tang; Zirui Liu; Bo Hu; Maofa Ge (Environmental Pollution, 2023)

Towards carbon neutrality: How much do forest carbon sinks cost in China? - Jiamin Ge; Zuopeng (Justin) Zhang; Boqiang Lin (Environmental Impact Assessment Review, 2023)

Disinfection byproducts formation from emerging organic micropollutants during chlorine-based disinfection processes - Binbin Shao; Leyuan Shen; Zhifeng Liu; Lin Tang; Xiaofei Tan; Dongbo Wang; Weimin Zeng; Ting Wu; Yuan Pan; Xiansheng Zhang; Lin Ge; Miao He (Chemical Engineering Journal, 2023)

Aberrant Topological Properties of Brain Functional Network in Children with Obstructive Sleep Apnea Derived from Resting-State fMRI - Tingting Ji; Xuemin Ren; Ting Long; Xiaodan Li; Lin Mei; Wentong Ge; Jie Zhang; Shengcai Wang; Yongli Guo; Zhifei Xu; Yun Peng; Jiangang Liu; et al. (Brain Topography, 2023)

Isoflurane Preconditioning May Attenuate Cardiomyocyte Injury Induced by Hypoxia/Reoxygenation Possibly by Regulating miR-363-3p - Yanhu Ge; Chengbin Wang; Boqun Cui; Yaguang Liu; Duomao Lin; Liang Zhang; Liyun Zhao; Jun Ma (Neurotoxicity Research, 2022)

Transplantation of Nasal Olfactory Mucosa Mesenchymal Stem Cells Benefits Alzheimer’s Disease - Chun-Gu Hong; Meng-Lu Chen; Ran Duan; Xin Wang; Zhi-Lin Pang; Li-Te Ge; Ming Lu; Hui Xie; Zheng-Zhao Liu (Molecular Neurobiology, 2022)

Genomic Analysis and Molecular Characteristics in Carbapenem-Resistant Klebsiella pneumoniae Strains - Suying Zhao; Xingyi Qiu; Yiting Tan; Min Xu; Xiaotong Xu; Yulai Ge; Huiling Cao; Min Li; Yuxin Lin; Zhan Zhang; Lei Li; Qian Wu (Current Microbiology, 2022)

c-Myc plays a critical role in the antileukemic activity of the Mcl-1-selective inhibitor AZD5991 in acute myeloid leukemia - Shuang Liu; Xinan Qiao; Shuangshuang Wu; Yuqinq Gai; Yongwei Su; Holly Edwards; Yue Wang; Hai Lin; Jeffrey W. Taub; Guan Wang; Yubin Ge (Apoptosis, 2022)

Development of a pressure-retaining separation and transfer system for sediment and overlying seawater - Jin Guo; Qixiao Zhou; Yongqiang Ge; Haonan Li; Qiaoling Gao; Ying Wang; Yuan Lin; Jiawang Chen (Frontiers in Marine Science, 2022)
Methane leakage at the interface between sediment and overlying seawater is an important basis for gas hydrate exploration. Therefore, a transfer device with working pressure of 30MPa and corresponding scheme are proposed to separate and transfer the sediment and overlying water inside the sampler under the condition of pressure-retaining. Based on the pressure relief valve with adjustable threshold pressure, the device transfers the overlying water by compressing the internal volume and transfers the sediment by secondary sampling. The performance of transfer device is studied by simulation and experiment. Based on the coupled Eulerian-Lagrangian approach in the Abaqus, the secondary sampling was investigated, and the penetration resistance and coring rate of the secondary sampling tube are 141N and 86.2%, respectively. By using the hydraulic simulation software AMESim, the pressure fluctuation caused by the movement of the mechanism during the transfer process was studied, and the pressure fluctuation amplitude is within 0.89 MPa. Furthermore, the laboratory transfer tests were carried out under high pressure conditions, and meantime, the simulation results are verified. Under the working condition of 30MPa, the device can maintain a pressure loss of no more than 8.0% (2.4MPa) within two hours, maintain pressure fluctuations during the transfer process within 4.8% (1.44MPa), and ensure that the pressure in the culture kettle decreases by 4.7% relative to the pressure in the sampler after the transfer, which shows the feasibility of the device application.

Microfossil evidence of rice cultivation on the Southeast China Coast 7500 years ago - Xinxin Zuo; Jinqi Dai; Wei Wu; Jianhui Jin; Wei Ge; Yinping Wang; Lin Ren; Yingjun Lin; Yaoyao Pei; Hui Xie (Science China Earth Sciences, 2022)

Comprehensive comparison of the prognostic value of systemic inflammation biomarkers for cancer cachexia: a multicenter prospective study - Hailun Xie; Guotian Ruan; Lishuang Wei; Heyang Zhang; Yizhong Ge; Qi Zhang; Shiqi Lin; Mengmeng Song; Xi Zhang; Xiaoyue Liu; Ming Yang; Meng Tang; et al. (Inflammation Research, 2022)

Effect of gravel content on the detachment of colluvial deposits in Benggang - Li-ting Zhang; Fang Shuai; Li-bo Chen; Yan-he Huang; Jin-shi Lin; Yue Zhang; Hong-li Ge; Fang-shi Jiang (Journal of Mountain Science, 2022)

Temperature has a strong impact on the abundance and community structure of comammox Nitrospira in an Ultisol - Mengmeng Feng; Zi-Yang He; Jianbo Fan; An-Hui Ge; Shengsheng Jin; Yongxin Lin; Ji-Zheng He (Journal of Soils and Sediments, 2022)

How Frequently Will the Persistent Heavy Rainfall over the Middle and Lower Yangtze River Basin in Summer 2020 Happen under Global Warming? - Zi-An Ge; Lin Chen; Tim Li; Lu Wang (Advances in Atmospheric Sciences, 2022)

Novel Self-Assembled Micelles With Increased Tumor Penetration and Anti-Tumor Efficiency Against Breast Cancer - Yani Yang; Yuezhu Zhao; Jie Liu; Chen Ge; Weiwei Zhang; Yue Zhang; Junji Wang; Guohao Sun; Xiujun Lin; Xiaohong Lu; Xiang Tang; Jun He; et al. (Pharmaceutical Research, 2022)

Identification and validation of suitable reference genes for quantitative real-time PCR studies in Adiantum reniforme var. sinense - Qi Fu; Lin Xiang; Kai-ge Zhao; Long-qing Chen (Journal of Plant Biochemistry and Biotechnology, 2022)

Green finance, technological progress, and ecological performance—evidence from 30 Provinces in China - Lin Ge; Haoxiang Zhao; Junyao Yang; Jingyue Yu; Taiyi He (Environmental Science and Pollution Research, 2022)

A strategy for establishing an efficient somatic embryo regeneration system in Castanea mollissima Blume - Xiao-wei Li; Zhi-lin Sun; Yue-rong Gao; Jing-yi Ge; Yu-zhen Tian; Bing Liu; Shi-kan Sun; Ke-feng Fang; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Production and Evaluation of a Novel Multi-Epitope Bivalent Vaccine Against Echinococcus multilocaularis Metacestode - Runle Li; Mingyuan Xin; Kunmei Liu; Bingwen Hu; Jingwei Ma; Pei Zhou; Lin Feng; Mingquan Pang; Ri-li Ge; Haining Fan; Le Guo; Feng Tang (International Journal of Peptide Research and Therapeutics, 2022)

Gestational exposure to PCB-118 impairs placental angiogenesis and fetal growth - Caiyun Ge; Ting Geng; Lin Cheng; Yuanzhen Zhang (Environmental Science and Pollution Research, 2022)

Mapping and characterization of the Rx3 gene for resistance to Xanthomonas euvesicatoria pv. euvesicatoria race T1 in tomato - Ge Meng; Yao Xiao; Aitong Li; Zilin Qian; Yinge Xie; Luyao Yang; Huabing Lin; Wencai Yang (Theoretical and Applied Genetics, 2022)

Nanosecond pulsed electric fields prime mesenchymal stem cells to peptide ghrelin and enhance chondrogenesis and osteochondral defect repair in vivo - Kejia Li; Litong Fan; Jianjing Lin; Boon Chin Heng; Zhantao Deng; Qiujian Zheng; Jue Zhang; Yangzi Jiang; Zigang Ge (Science China Life Sciences, 2022)

Ultrasound-induced biophysical effects in controlled drug delivery - Lulu Zhang; Zhuohua Lin; Lan Zeng; Fan Zhang; Lihong Sun; Suhui Sun; Ping Wang; Menghong Xu; Jinxia Zhang; Xiaolong Liang; Huiyu Ge (Science China Life Sciences, 2022)

Synthesis of Silver- and Strontium-Substituted Hydroxyapatite with Combined Osteogenic and Antibacterial Activities - Yunfei Li; Wenying Wang; Jing Han; Zirui Li; Qiuxiang Wang; Xue Lin; Kun Ge; Guoqiang Zhou (Biological Trace Element Research, 2022)

A Preliminary Study on Silver Isotopic Composition in Polymetallic Ore Deposits in Eastern China - Ge Dong; Hai-Zhen Wei; Yuanfeng Zhu; Xi Liu; Qi Guo; Wei Pu; Yibo Lin; Junlin Wang (Journal of Earth Science, 2022)

Fasting augments pyrrolizidine alkaloid-induced hepatotoxicity - Jiang Ma; Chunyuan Zhang; Yisheng He; Xinmeng Chen; Ge Lin (Archives of Toxicology, 2022)

Species Composition and Assemblages of Ichthyoplankton in Sansha Bay, Fujian Province, China - Yan Jiang; Bai-an Lin; Hao-yang He; Guang-mao Ding; Li-ting Yan; Ge Zhang; Min Liu; Lian-ming Zheng (Frontiers in Marine Science, 2021)
Sansha Bay (26.40−27.00°N, 119.50−120.20°E) is a typical semi-enclosed bay, located in northern Fujian Province, China, and adjacent to the East China Sea. The ichthyoplankton species composition and assemblage structure were investigated based on monthly sampling at 25 stations in April−September 2019, covering the important spring and summer spawning seasons in the region. Sampling was conducted in the first 3−5 days of the full moon or new moon phases using a standard plankton net through horizontal and vertical tows during daytime. In total, 25,819 ichthyoplankton samples were collected, of which 25,449 samples (i.e., 24,757 eggs and 692 larvae) were from horizontal tows. For horizontal tow samples, the ichthyoplankton were classified into 58 taxa in 15 orders and 23 families with a combination of external morphology and DNA barcoding analyses, from pelagic to demersal and benthic species. The dominant order was the Gobiiformes, including 23 species (39.7% of all species). The dominant taxa, in terms of relative abundance and frequency of occurrence, consisted of commercially important fishes, such as Setipinna tenuifilis (Valenciennes, 1848) (Engraulidae), Epinephelus akaara (Temminck and Schlegel, 1842) (Serraenidae), Collichthys lucidus (Richardson, 1844), Nibea albiflora (Richardson, 1846) (Sciaenidae), Acanthopagrus schlegelii (Bleeker, 1854), and Pagrus major (Temminck and Schlegel, 1843) (Sparidae), accounting for 78.9% of the horizontal tow samples. Low-valued and small-sized fishes, such as Stolephorus commersonnii Lacepède, 1803 (Engraulidae), Solea ovata Richardson, 1846 (Soleidae), Nuchequula nuchalis (Temminck and Schlegel, 1845), and Photopectoralis bindus (Valenciennes, 1835) (Leiognathidae), were also dominant species, accounting for 11.4% of the horizontal tow samples. The ichthyoplankton assemblage was categorized into five different temporal assemblages based on the cluster and nonmetric multidimensional scaling analysis, namely, April, May, June, July, and August−September (ANOSIM, Global R = 0.656, p < 0.01) with the highest density and richness of ichthyoplankton occurred in May. The spatial distribution pattern showed that the high density (ind./m 3 ) of ichthyoplankton occurred mainly in S12–S25 in Guanjingyang and along the Dongchong Peninsula coastline into Dongwuyang, while low density occurred mainly in S01–S11 in the northwest waters of Sandu Island (ANOVA, F = 8.270, p < 0.05). Temperature, salinity, and chlorophyll a were key factors structuring the ichthyoplankton assemblages in Sansha Bay. In addition, this study revealed the changes of the ichthyoplankton composition, density, and spatial distribution in Sansha Bay over the past three decades.

Future study for the urinary histidine adduct derived from pyrrolizidine alkaloids is warranted - Lin Zhu; Chunyuan Zhang; Jiang Ma; Yisheng He; Ge Lin (Archives of Toxicology, 2021)

Tibetan Plateau v ortex‐associated precipitation and its link with the Tibetan Plateau heating anomaly - Zhiqiang Lin; Weidong Guo; Xiuping Yao; Jun Du; Wenkai Li; Jun Ge (International Journal of Climatology, 2021)
The Tibetan Plateau (TP) is known as the Asian water tower that supplies fresh water for millions of people in Asia. The Tibetan Plateau vortices (TPVs) are one of the major precipitation‐producing weather systems over the TP. The characteristics of TPV‐associated precipitation from 1979 to 2017 are quantitatively analysed based on three daily precipitation datasets. The influence of TPVs on precipitation is more significant in the warm season (May–September) because the precipitation and TPV activities both peak in the warm season. The TPV‐associated precipitation (VAP) dominates the total precipitation over most of the TP in the warm season. The VAP contributes more than 50% of the total precipitation in the warm season over 30% of the area over the TP, particularly in the central TP, while the VAP accounts for more than 25% of the total precipitation in the cold season over about 20% of the area over the TP. Therefore, TPVs are the major systems to produce precipitation on the TP in the warm season, and they are also important in the cold season in certain regions. The interannual variation of VAP is mainly determined by the number, rather than the precipitation intensity, of TPVs. Furthermore, the heating anomaly caused by the TP thermodynamic effect is an influential factor of VAP. Stronger (weaker) TP heating and resulting ascending motion strengthen (attenuate) the convergence near the TP surface and the divergence in the upper troposphere. The thermal adaption‐associated circulation generates more (less) TPVs and VAP.

Developing urinary pyrrole–amino acid adducts as non-invasive biomarkers for identifying pyrrolizidine alkaloids-induced liver injury in human - Lin Zhu; Chunyuan Zhang; Wei Zhang; Qingsu Xia; Jiang Ma; Xin He; Yisheng He; Peter P. Fu; Wei Jia; Yuzheng Zhuge; Ge Lin (Archives of Toxicology, 2021)

Interaction between β-lactam antibiotic and phosphorus-accumulating organisms - Rong Huang; Jing Lan; Chaoguo Zhan; Yanhui Ge; Lin Zhao (Environmental Science and Pollution Research, 2021)

Refractory organic compounds in coal chemical wastewater treatment by catalytic ozonation using Mn-Cu-Ce/Al2O3 - Kang-He Zhao; Yu-Long Ma; Feng Lin; Shao-Ying Ge; Li Zhu (Environmental Science and Pollution Research, 2021)

Genetic changes and evolutionary analysis of canine circovirus - Lin Wang; Yifan li; Zhiyuan Guo; Ying Yi; Han Zhang; Haikun Shangguan; Chengshi Huang; Junwei Ge (Archives of Virology, 2021)

Aestuariibaculum sediminum sp. nov., a marine bacterium isolated from a tidal flat in Zhoushan - Zhi-Cheng Wu; Xin-Yin Zhang; Cong Sun; Lin Xu; Ge-Yi Fu; Xue-Wei Xu (Archives of Microbiology, 2021)

Characteristics of dissolved organic matter in lakes with different eutrophic levels in southeastern Hubei Province, China - Weixiang Ren; Xiaodong Wu; Xuguang Ge; Guiying Lin; Mengdie Zhou; Zijie Long; Xinhui Yu; Wei Tian (Journal of Oceanology and Limnology, 2021)

Seismic performance of precast bridge columns connected with grouted corrugated-metal duct through biaxial quasi-static experiment and modeling - Xia Zhanghua; Lin Shangshun; He Yongbo; Ge Jiping; Sun Jinlei (Earthquake Engineering and Engineering Vibration, 2021)

The influence of surfactant on the wettability of coal dust and dust reduction efficiency - Lin Yang; Shaocheng Ge; Zhihui Huang; Deji Jing; Xi Chen (Arabian Journal of Geosciences, 2021)

Anthropogenic Effects on Biogenic Secondary Organic Aerosol Formation - Li Xu; Lin Du; Narcisse T. Tsona; Maofa Ge (Advances in Atmospheric Sciences, 2021)

Precise Control and Experimental Evaluation of a Novel Endoscopic Suturing Device for Large Perforations - Liaoyuan Ai; Chengli Song; Shuchen Ge; Shiju Yan; Lin Mao; Alfred Cuschieri (Journal of Medical and Biological Engineering, 2021)

Biosynthesis and preparation of phycoerythrobilin in recombinant Escherichia coli - Wenjun Li; Chengbo Ma; Baosheng Ge; Fan Zang; Song Qin; Jian Lin (Journal of Applied Phycology, 2021)

Metabolism-mediated cytotoxicity and genotoxicity of pyrrolizidine alkaloids - Yisheng He; Lin Zhu; Jiang Ma; Ge Lin (Archives of Toxicology, 2021)

Ring distribution patterns—diversification or speciation? Comparative phylogeography of two small mammals in the mountains surrounding the Sichuan Basin - Yanqun Wang; Anderson Feijó; Jilong Cheng; Lin Xia; Zhixin Wen; Deyan Ge; Jian Sun; Liang Lu; Song Li; Qisen Yang (Molecular Ecology, 2021)
Studying the genetic differentiation in a unique geographical area contributes to understanding the process of speciation. Here, we explore the spatial genetic structure and underlying formation mechanism of two congeneric small mammal species ( Apodemus draco and A. chevrieri ), which are mainly distributed in the mountains surrounding the lowland Sichuan Basin, southwest China. We applied a set of comparative phylogeographical analyses to determine their genetic diversification patterns, combining mitochondrial ( Cytb and COI ) and nuclear (microsatellite loci) markers, with dense sampling throughout the range (411 A . draco from 21 sites and 191 A . chevrieri from 22 sites). Moreover, we performed three complementary statistical methods to investigate the correlation between genotype and geographical and environmental components, and predicted the potential suitable distributional range under the present and historical climate conditions. Our results suggest that both species have experienced allopatric differentiation and admixture in historical periods, resulting in a ring‐shape diversification, under the barrier effect of the Sichuan Basin. We infer that the tectonic events of the Qinghai–Tibetan Plateau and climatic oscillations during the Quaternary played an important role on the genetic divergence of the two species by providing environmental heterogeneity and geographical variation. Our study reveals a case of two sympatric small mammals following a ring‐shaped diversification pattern and provides insight into the process of differentiation.

Identification and functional characterization of a new flavonoid synthase gene MdFLS1 from apple - Pan Li; Kang Lei; Lin Liu; Guizhi Zhang; Hongjuan Ge; Chengchao Zheng; Huairui Shu; Shizhong Zhang; Lusha Ji (Planta, 2021)

Estimation of the appropriate sampling interval for rock joints roughness using laser scanning - Yunfeng Ge; Zishan Lin; Huiming Tang; Binbin Zhao (Bulletin of Engineering Geology and the Environment, 2021)

Phylogeny and taxonomy of two new Alternaria (Ascomycota: Pleosporaceae) species in section Gypsophilae from China - Lin He; Hong Cheng; Aye Aye Htun; Hui Ge; Zhen Zhou Xia; Jian Wei Guo; Jian Xin Deng; Tao Du (Mycological Progress, 2021)

Molecular cloning and functional characterization of the hypoxia-inducible factor-1α in bighead carp (Aristichthys nobilis) - Yan Lin; Ling-Hong Miao; Bo Liu; Bing-Wen Xi; Liang-Kun Pan; Xian-Ping Ge (Fish Physiology and Biochemistry, 2021)

Air-pollutant mass concentration changes during COVID-19 pandemic in Shanghai, China - Zhi Niu; Tingting Hu; Lin Kong; Wenqi Zhang; Pinhua Rao; Dafeng Ge; Mengge Zhou; Yuseng Duan (Air Quality, Atmosphere & Health, 2021)

Varying support for abundance‐centre and congeneric‐competition hypotheses along elevational transects of mammals - Zhixin Wen; Deyan Ge; Anderson Feijó; Yuanbao Du; Jilong Cheng; Jian Sun; Yanqun Wang; Lin Xia; Qisen Yang (Journal of Biogeography, 2021)
Aim Whether species are most abundant at their geographic range centre and increasingly rare towards range limits (the abundance‐centre hypothesis, ACH) has weak empirical support in birds along elevational gradients. This may be due to empirical limitations—most studies do not capture the multi‐faceted nature of elevational gradients or species interactions. We examine the ACH and an alternative that the abundance maximum of elevational sympatric congeners will occur at different elevations along a gradient (the congeneric‐competition hypothesis, CCH). Location Twelve elevational gradients in Central and Southwest China. Taxon Five small mammal species, including three congeneric species. Methods The ACH was tested by fitting abundance patterns to Huisman‐Olff‐Fresco (HOF) models and measuring the relative elevational distance between a species' abundance‐weighted range centre ( RC Abu ) and its elevational range centre. The CCH was tested by calculating the elevational overlap value of each congeneric pair and the relative elevational distance ( RC AbuDiff ) between the RC Abu s of congeners. Results Abundances of each species showed diverse patterns along different gradients. For all species, a unimodal symmetric pattern appeared at most once among the studied gradients and found in only four (8.7%) of the total cases. Most (90.9%) of the Apodemus congeneric pairs had a high elevational overlap (above 75%). For each of the three congeneric pairs, 40.0% to 50.0% of the cases showed RC AbuDiff values > 0.25, suggesting that the congeners’ RC Abu s were separated by at least one elevational climate zone. Main conclusions Species' elevational abundance patterns may vary among different elevational gradients in the same geographic region. The elevational abundance patterns of five mammalian species were rarely consistent with the ACH after the spatial variability of the patterns was considered. The abundance patterns of congeneric species showed moderate support for the CCH.

Simultaneously decreased temporal variability and enhanced variability-strength coupling of emotional network connectivities are related to positive symptoms in patients with schizophrenia - Yanjia Deng; Shuguang Han; Dongliang Cheng; Hui Li; Bin Zhang; Youyong Kong; Yong Lin; Yingjia Li; Ge Wen; Kai Liu (Brain Imaging and Behavior, 2021)

Transcriptome and Metabolome Analyses of Sea Cucumbers Apostichopus japonicus in Southern China During the Summer Aestivation Period - Qiuhua Yang; Xusheng Zhang; Zhen Lu; Ruifang Huang; Ngoc Tuan Tran; Jianshao Wu; Fuyuan Yang; Hui Ge; Chenhui Zhong; Qian Sun; Chen Zhou; Qi Lin (Journal of Ocean University of China, 2021)

Clinical application of pyrrole–hemoglobin adducts as a biomarker of pyrrolizidine alkaloid exposure in humans - Jiang Ma; Wei Zhang; Yisheng He; Lin Zhu; Chunyuan Zhang; Jia Liu; Yang Ye; Yuzheng Zhuge; Ge Lin (Archives of Toxicology, 2021)

Comparison of the Nutritional Quality of Three Edible Tissues from Precocious and Normal Adult Female Chinese Mitten Crabs ( Eriocheir sinensis ) - Huafeng Cheng; Haoran Wu; Feng Liang; Mengtian Ge; Shaotong Jiang; Lin Lin; Jianfeng Lu (Journal of Aquatic Food Product Technology, 2021)

Selenium Deficiency-Induced Damage and Altered Expression of Mitochondrial Biogenesis Markers in the Kidneys of Mice - Hehuan Lai; Tingting Nie; Yitong Zhang; Ying Chen; Jiaqi Tao; Tingting Lin; Tangdong Ge; Fenglan Li; Hui Li (Biological Trace Element Research, 2021)

Lung injury induced by pyrrolizidine alkaloids depends on metabolism by hepatic cytochrome P450s and blood transport of reactive metabolites - Yisheng He; Wei Lian; Liang Ding; Xiaoyu Fan; Jiang Ma; Qing-Yu Zhang; Xinxin Ding; Ge Lin (Archives of Toxicology, 2021)

Genetic variants in N6-methyladenosine are associated with bladder cancer risk in the Chinese population - Hanting Liu; Jingjing Gu; Yu Jin; Qi Yuan; Gaoxiang Ma; Mulong Du; Yuqiu Ge; Chao Qin; Qiang Lv; Guangbo Fu; Meilin Wang; Haiyan Chu; et al. (Archives of Toxicology, 2021)

Analysis of sediment deposition in Lushui Reservoir to guide dredging - Hua Ge; Lingling Zhu; Qiusheng Lin; Chunyan Deng (Arabian Journal of Geosciences, 2021)

Heterosis-associated genes confer high yield in super hybrid rice - Tianzi Lin; Cong Zhou; Gaoming Chen; Jun Yu; Wei Wu; Yuwei Ge; Xiaolan Liu; Jin Li; Xingzhou Jiang; Weijie Tang; Yunlu Tian; Zhigang Zhao; et al. (Theoretical and Applied Genetics, 2020)
Key message Heterosis QTLs, including qSS7 and qHD8, with dominance effects were identified through GBS and large-scale phenotyping of CSSLs and hybrid F 1 populations in a paddy field. Abstract Heterosis has contributed immensely to agricultural production, but its genetic basis is unclear. We evaluated dominance effects by creating two hybrid populations: a B-homo set with a homozygous background and heterozygous chromosomal segments and a B-heter set with a heterozygous background and homozygous segments. This was achieved by crossing a set of 156 backcrossed-derived chromosome segment substitution lines (CSSLs) with their recurrent parent (9311), the male parent of the first super-high-yield hybrid Liangyoupei9 (LYP9), and with the female parent (PA64s) of the hybrid. The CSSLs were subjected to a genotyping-by-sequencing analysis to develop a genetic map of segments introduced from the PA64s. We evaluated the heterotic effects on eight yield-related traits in the hybrid variety and F 1 populations in large-scale field experiments over 2 years. Using a linkage map consisting of high-density SNPs, we identified heterosis-associated genes in LYP9. Five candidate genes contributed to the high yield of LYP9, with qSS7 and qHD8 repeatedly detected in both B-hybrid populations. The heterozygous segments harboring qSS7 and qHD8 showed dominance effects that contributed to the heterosis of yield components in the hybrid rice variety Liangyoupei9.

Quantitative Determination of Glymphatic Flow Using Spectrophotofluorometry - Yu Zhang; Jian Song; Xu-Zhong He; Jian Xiong; Rong Xue; Jia-Hao Ge; Shi-Yu Lu; Die Hu; Guo-Xing Zhang; Guang-Yin Xu; Lin-Hui Wang (Neuroscience Bulletin, 2020)

Assessment of Applications of Design of Experiments in Pharmaceutical Development for Oral Solid Dosage Forms - Ge Bai; Zhijin Chen; Kimberly Raines; Hansong Chen; Kaushalkumar Dave; Ho-Pi Lin; Banu S. Zolnik (Journal of Pharmaceutical Innovation, 2020)

Cortical 3-hinges could serve as hubs in cortico-cortical connective network - Tuo Zhang; Xiao Li; Xi Jiang; Fangfei Ge; Shu Zhang; Lin Zhao; Huan Liu; Ying Huang; Xianqiao Wang; Jian Yang; Lei Guo; Xiaoping Hu; et al. (Brain Imaging and Behavior, 2020)
Mapping the relation between cortical convolution and structural/functional brain architectures could provide deep insights into the mechanisms of brain development, evolution and diseases. In our previous studies, we found a unique gyral folding pattern, termed a 3-hinge, which was defined as the conjunction of three gyral crests. The uniqueness of the 3-hinge was evidenced by its thicker cortex and stronger fiber connections than other gyral regions. However, the role that 3-hinges play in cortico-cortical connective architecture remains unclear. To this end, we conducted MRI studies by constructing structural cortico-cortical connective networks based on a fine-granular cortical parcellation, the parcels of which were automatically labeled as 3-hinge, 2-hinge (ordinary gyrus) or sulcus. On human brains, 3-hinges possess significantly higher degrees, strengths and betweennesses than 2-hinges, suggesting that 3-hinges could serve more like hubs in the cortico-cortical connective network. This hypothesis gains supports from human functional network analyses, in which 3-hinges are involved in more global functional networks than ordinary gyri. In addition, 3-hinges could serve as ‘connector’ hubs rather than ‘provincial’ hubs and they account for a dominant proportion of nodes in the high-level ‘backbone’ of the network. These structural results are reproduced on chimpanzee and macaque brains, while the roles of 3-hinges as hubs become more pronounced in higher order primates. Our new findings could provide a new window to the relation between cortical convolution, anatomical connection and brain function.

Nuclear Factor-κB Pathway Mediates the Molecular Pathogenesis of LMNA-Related Muscular Dystrophies - Yanbin Fan; Dandan Tan; Xu Zhang; Danyu Song; Xingzhi Chang; Shuang Wang; Hui Yan; Lin Ge; Haipo Yang; Carsten Bönnemann; Jingying Liu; Suxia Wang; et al. (Biochemical Genetics, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Complete Genome of Vibrio neocaledonicus CGJ02-2, An active Compounds Producing Bacterium Isolated from South China Sea - Lin Tan; Isabel Gómez-Betancur; Suxia Guo; Yu Ge; Jianping Zhao; Chang Chen; Nan Wang (Current Microbiology, 2020)

Negative effects of rare earth oxide nanoparticles of La2O3, Nd2O3, and Gd2O3 on the ammonia-oxidizing microorganisms - Yan Yue; Lin Qi; Yan Li; Jichen Wang; Congcong Shen; Yuan Ge (Journal of Soils and Sediments, 2020)

Investigation of the effects of nonstationary features on rock joint roughness using the laser scanning technique - Yunfeng Ge; Zishan Lin; Huiming Tang; Binbin Zhao; Hongzhi Chen; Zhiguo Xie; Bin Du (Bulletin of Engineering Geology and the Environment, 2020)

Shake table study on precast segmental concrete double-column piers - Xia Zhanghua; Ge Jiping; Lin Youqin; Qiu Faqiang (Earthquake Engineering and Engineering Vibration, 2020)

Evaluation of Shear Strength Parameters of Rocks by Preset Angle Shear, Direct Shear and Triaxial Compression Tests - Fengqiang Gong; Song Luo; Ge Lin; Xibing Li (Rock Mechanics and Rock Engineering, 2020)

Nanochemoprevention with therapeutic benefits: An updated review focused on epigallocatechin gallate delivery - Qiong-Qiong Yang; Xin-Lin Wei; Ya-Peng Fang; Ren-You Gan; Min Wang; Ying-Ying Ge; Dan Zhang; Li-Zeng Cheng; Harold Corke (Critical Reviews in Food Science and Nutrition, 2020)

Hydrogen sulfide is a crucial element of the antioxidant defense system in Glycine max–Sinorhizobium fredii symbiotic root nodules - Hang Zou; Ni-Na Zhang; Xue-Yuan Lin; Wei-Qin Zhang; Jian-Hua Zhang; Juan Chen; Ge-Hong Wei (Plant and Soil, 2020)

Comparative transcriptomic analysis of vascular endothelial cells after hypoxia/re-oxygenation induction based on microarray technology - Jia Xu; Jiu-kun Jiang; Xiao-lin Li; Xiao-peng Yu; Ying-ge Xu; Yuan-qiang Lu (Journal of Zhejiang University-SCIENCE B, 2020)

Responses of soil moisture to regional climate change over the Three Rivers Source Region on the Tibetan Plateau - Mingshan Deng; Xianhong Meng; Zhaoguo Li; Yaqiong Lyv; Huajin Lei; Lin Zhao; Shengnan Zhao; Jun Ge; Hui Jing (International Journal of Climatology, 2020)
In this study, soil moisture data from two reanalysis datasets (ERA‐Interim, ERA5), a satellite soil moisture product from the European Space Agency (ESA) and three assimilation datasets from the Global Land Data Assimilation System (GLDAS), that is, GLADS‐NOAH025, GLADS‐NOAH10, and GLDAS‐CLM were compared with the observed soil moisture data in Maqu and Maduo stations over the Three Rivers Source Region (TRSR) on the Tibetan Plateau in China. Comparative statistical parameters between the soil moisture observations and the products, including the root mean square error, correlation coefficient ( R ), and standard deviation ratio were calculated to evaluate the products in different seasons. It was found that most products overestimated the soil moisture values, among which GLADS‐NOAH025 had relatively good consistency with the observations in the surface soil layer (0–10 cm), whereas GLDAS‐CLM agreed well with the observations in the 10–40 cm layer. Both ERA5 and ERA‐interim soil moisture overestimated soil moisture at all levels. The responses of soil moisture to regional climate change over the TRSR were also investigated by using the GLDAS‐NOAH025 soil moisture product, the ESA soil moisture product, and the observations during the nonfreezing period. The results show that the trends of soil moisture are consistent with the precipitation changes in the main central part of the TRSR. A significant positive correlation was found between soil moisture and precipitation in most regions of the TRSR, which indicates that soil moisture increases with the increase of precipitation, except in the northwest TRSR, where the variation of soil moisture was possibly influenced by both the precipitation changes and the increase of evapotranspiration.

Scorpion Venom Heat-Resistant Peptide is Neuroprotective against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2020)

ABA and sucrose co-regulate strawberry fruit ripening and show inhibition of glycolysis - Ya Luo; Cong Ge; Yajie Ling; Fan Mo; Min Yang; Leiyu Jiang; Qing Chen; Yuanxiu Lin; Bo Sun; Yong Zhang; Yan Wang; Mengyao Li; et al. (Molecular Genetics and Genomics, 2020)

Biosynthesis of phycocyanobilin in recombinant Escherichia coli - Chengbo Ma; Wenjun Li; Baosheng Ge; Jian Lin; Song Qin (Journal of Oceanology and Limnology, 2020)

Novel mutations in SPEF2 causing different defects between flagella and cilia bridge: the phenotypic link between MMAF and PCD - Chaofeng Tu; Hongchuan Nie; Lanlan Meng; Weili Wang; Haiyu Li; Shimin Yuan; Dehua Cheng; Wenbin He; Gang Liu; Juan Du; Fei Gong; Guangxiu Lu; et al. (Human Genetics, 2020)

Methamphetamine-Induced Cognitive Deficits and Psychiatric Symptoms Are Associated with Serum Markers of Liver Damage - Tingting Zhao; Changping Zhai; Hongmei Song; Yanhai Wu; Chuanhui Ge; Yonglin Zhang; Hongxia Xu; Zhengsuo Chi; Hui Chu; Wei Shi; Xiaodong Cheng; Xin Li; et al. (Neurotoxicity Research, 2020)

Association between long-term occupational manganese exposure and bone quality among retired workers - Defu Li; Xiaoting Ge; Zhenfang Liu; Lulu Huang; Yanting Zhou; Peng Liu; Lian Qin; Suzhen Lin; Chaoqun Liu; Qingzhi Hou; Longman Li; Hong Cheng; et al. (Environmental Science and Pollution Research, 2020)

Bifidobacterium bifidum TMC3115 Can Characteristically Influence Glucose and Lipid Profile and Intestinal Microbiota in the Middle-Aged and Elderly - Ke Wang; Xiaohong Yu; Yi Li; Yun Guo; Lin Ge; Fangfang Pu; Xinying Ma; Wenjing Cui; Francesco Marrota; Fang He; Ming Li (Probiotics and Antimicrobial Proteins, 2019)

An extra insertion of tandem repeat sequence in African swine fever virus, China, 2019 - Shengqiang Ge; Yutian Liu; Lin Li; Qinghua Wang; Jinming Li; Weijie Ren; Chunju Liu; Jingyue Bao; Xiaodong Wu; Zhiliang Wang (Virus Genes, 2019)

Correlation between shear strength and soil physicochemical properties of different weathering profiles of the non-eroded and collapsing gully soils in southern China - Bifei Huang; Ming Qiu; Jinshi Lin; Jialin Chen; Fangshi Jiang; Ming-kuang Wang; Hongli Ge; Yanhe Huang (Journal of Soils and Sediments, 2019)

Pore size distribution and reservoir characterization: evaluation for the Eocene beach-bar sequence, Dongying Depression, China - Muhammad Aleem Zahid; Dong Chunmei; Alexandra N. Golab; Chengyan Lin; Xianguo Zhang; Xinmin Ge; Wu Songtao; Muhammad Jawad Munawar; Cunfei Ma; Lydia Knuefing (Arabian Journal of Geosciences, 2019)

Relationship between phenotype and genotype of 102 Chinese newborns with Prader–Willi syndrome - Meng-Meng Ge; Yan-Yan Gao; Bing-Bing Wu; Kai Yan; Qian Qin; HuiJun Wang; WenHao Zhou; Lin Yang (Molecular Biology Reports, 2019)

Coalescence Models Reveal the Rise of the White-Bellied Rat (Niviventer confucianus) Following the Loss of Asian Megafauna - Deyan Ge; Liang Lu; Alexei V. Abramov; Zhixin Wen; Jilong Cheng; Lin Xia; Alfried P. Vogler; Qisen Yang (Journal of Mammalian Evolution, 2019)

Cloud Radiative Feedbacks during the ENSO Cycle Simulated by CAMS-CSM - Lin Chen; Lijuan Hua; Xinyao Rong; Jian Li; Lu Wang; Guo Zhang; Ming Sun; Zi’an Ge (Journal of Meteorological Research, 2019)

Intestinal and hepatic biotransformation of pyrrolizidine alkaloid N-oxides to toxic pyrrolizidine alkaloids - Mengbi Yang; Jiang Ma; Jianqing Ruan; Yang Ye; Peter Pi-Cheng Fu; Ge Lin (Archives of Toxicology, 2019)

Phytochrome-interacting factor-like protein OsPIL15 integrates light and gravitropism to regulate tiller angle in rice - Chuanmiao Xie; Ge Zhang; Lin An; Xiaoying Chen; Rongxiang Fang (Planta, 2019)

Comparison of surface sensible and latent heat fluxes over the Tibetan Plateau from reanalysis and observations - Jin Xie; Ye Yu; Jiang-lin Li; Jun Ge; Chuan Liu (Meteorology and Atmospheric Physics, 2019)

Impact of Orogeny and Environmental Change on Genetic Divergence and Demographic History of Dipus sagitta (Dipodoidea, Dipodinae) since the Pliocene in Inland East Asia - Jilong Cheng; Xue Lv; Lin Xia; Deyan Ge; Qian Zhang; Liang Lu; Qisen Yang (Journal of Mammalian Evolution, 2019)

Evaluation of particulate matter deposition in the human respiratory tract during winter in Nanjing using size and chemically resolved ambient measurements - Xiaoyuan Liu; Dongyang Nie; Kai Zhang; Ziyao Wang; Xiaoqian Li; Zhihao Shi; Yiyi Wang; Lin Huang; Mindong Chen; Xinlei Ge; Qi Ying; Xingna Yu; et al. (Air Quality, Atmosphere & Health, 2019)

Agricultural Development and Implication for Wetlands Sustainability: A Case from Baoqing County, Northeast China - Chong Fang; Zhidan Wen; Lin Li; Jia Du; Ge Liu; Xiaodi Wang; Kaishan Song (Chinese Geographical Science, 2019)

In Vitro Evaluation of Probiotic Potential of Lactic Acid Bacteria Isolated from Yunnan De’ang Pickled Tea - Zhenhui Cao; Hongbin Pan; Shijun Li; Chongying Shi; Sifan Wang; Fuyi Wang; Pengfei Ye; Junjing Jia; Changrong Ge; Qiuye Lin; Zhiyong Zhao (Probiotics and Antimicrobial Proteins, 2019)

Expression of the intrarenal angiotensin receptor and the role of renin-angiotensin system inhibitors in IgA nephropathy - Zheng Zhang; Shi-min Jiang; Ye-ping Ma; Pei-lin Dai; Yi-ning Wang; Gu-ming Zou; Hong-mei Gao; Yue Yang; Wen-ge Li (Molecular and Cellular Biochemistry, 2019)

Relationships between body weight and other morphological traits in young sea cucumbers Apostichopus japonicas - Yaoyao Zhan; Weijie Zhang; Chen Ge; Kai Lin; Guang Li; Jian Song; Yaqing Chang (Journal of Oceanology and Limnology, 2019)

Clinical relationships between the rs2212020 and rs189897 polymorphisms of the ITGA9 gene and epithelial ovarian cancer - Jinyang Liu; Ting Liu; Lin Liang; Junyu He; Manying Zhang; Yanshan Ge; Shan Liao; Yanhong Zhou; Keqiang Zhang (Journal of Genetics, 2019)

Underestimated ecosystem carbon turnover time and sequestration under the steady state assumption: A perspective from long‐term data assimilation - Rong Ge; Honglin He; Xiaoli Ren; Li Zhang; Guirui Yu; T. Luke Smallman; Tao Zhou; Shi‐Yong Yu; Yiqi Luo; Zongqiang Xie; Silong Wang; Huimin Wang; et al. (Global Change Biology, 2019)
It is critical to accurately estimate carbon (C) turnover time as it dominates the uncertainty in ecosystem C sinks and their response to future climate change. In the absence of direct observations of ecosystem C losses, C turnover times are commonly estimated under the steady state assumption ( SSA ), which has been applied across a large range of temporal and spatial scales including many at which the validity of the assumption is likely to be violated. However, the errors associated with improperly applying SSA to estimate C turnover time and its covariance with climate as well as ecosystem C sequestrations have yet to be fully quantified. Here, we developed a novel model‐data fusion framework and systematically analyzed the SSA ‐induced biases using time‐series data collected from 10 permanent forest plots in the eastern China monsoon region. The results showed that (a) the SSA significantly underestimated mean turnover times ( MTT s) by 29%, thereby leading to a 4.83‐fold underestimation of the net ecosystem productivity ( NEP ) in these forest ecosystems, a major C sink globally; (b) the SSA ‐induced bias in MTT and NEP correlates negatively with forest age, which provides a significant caveat for applying the SSA to young‐aged ecosystems; and (c) the sensitivity of MTT to temperature and precipitation was 22% and 42% lower, respectively, under the SSA . Thus, under the expected climate change, spatiotemporal changes in MTT are likely to be underestimated, thereby resulting in large errors in the variability of predicted global NEP . With the development of observation technology and the accumulation of spatiotemporal data, we suggest estimating MTT s at the disequilibrium state via long‐term data assimilation, thereby effectively reducing the uncertainty in ecosystem C sequestration estimations and providing a better understanding of regional or global C cycle dynamics and C‐climate feedback.

Composition and antioxidant and antibacterial activities of essential oils from three yellow Camellia species - Li Ge; Binghui Lin; Jianguang Mo; Qiuhong Chen; Lin Su; Yuejuan Li; Kedi Yang (Trees, 2019)

Available soil nutrients and water content affect leaf nutrient concentrations and stoichiometry at different ages of Leucaena leucocephala forests in dry-hot valley - Yongming Lin; Aimin Chen; Siwei Yan; Loretta Rafay; Kun Du; Daojie Wang; Yonggang Ge; Jian Li (Journal of Soils and Sediments, 2019)

Novel biallelic PCNT deletion causing microcephalic osteodysplastic primordial dwarfism type II with congenital heart defect - Lanlan Meng; Chaofeng Tu; Guangxiu Lu; Ge Lin; Yueqiu Tan (Science China Life Sciences, 2019)

Evolutionary Genetics of Hypoxia and Cold Tolerance in Mammals - Kangli Zhu; Deyan Ge; Zhixin Wen; Lin Xia; Qisen Yang (Journal of Molecular Evolution, 2018)

Associations between ambient temperature and daily hospital admissions for rheumatic heart disease in Shanghai, China - Yihui Ge; Cong Liu; Yue Niu; Chen Chen; Weibing Wang; Zhijing Lin; Renjie Chen; Jing Cai; Haidong Kan (International Journal of Biometeorology, 2018)

White matter integrity correlates with residual consciousness in patients with severe brain injury - Lubin Wang; Yi Yang; Shanshan Chen; Mingmei Ge; Jianghong He; Zheng Yang; Pan Lin; Xinhuai Wu (Brain Imaging and Behavior, 2018)

Evaluating tacrolimus pharmacokinetic models in adult renal transplant recipients with different CYP3A5 genotypes - Can Hu; Wen-jun Yin; Dai-yang Li; Jun-jie Ding; Ling-yun Zhou; Jiang-lin Wang; Rong-rong Ma; Kun Liu; Ge Zhou; Xiao-cong Zuo (European Journal of Clinical Pharmacology, 2018)

The role of formation of pyrrole–ATP synthase subunit beta adduct in pyrrolizidine alkaloid-induced hepatotoxicity - Yao Lu; Jiang Ma; Zijing Song; Yang Ye; Peter P. Fu; Ge Lin (Archives of Toxicology, 2018)

Phylogeny and taxonomic reassessment of jerboa, Dipus (Rodentia, Dipodinae), in inland Asia - Jilong Cheng; Deyan Ge; Lin Xia; Zhixin Wen; Qian Zhang; Liang Lu; Qisen Yang (Zoologica Scripta, 2018)
Deserts and arid regions are perceived to have low biological and genetic diversity, which has partially influenced the identification of psammophilic species, especially taxonomic inferences based on morphology alone. Recent studies of Dipus sagitta have revealed clear, deep genetic divergence beyond the species level within this monotypic genus. To clarify the taxonomy of Dipus , we examined a morphometric dataset consisting of 191 voucher specimens covering nearly the entire distribution of the genus to explore skull variation using traditional morphological measurements and geometric morphometric analysis. Phylogenetic relationships within Dipus using two mitochondrial genes ( n = 383) and six nuclear genes ( n = 106) were assessed by Bayesian inference and maximum‐likelihood procedures. We used a “candidate species approach” with the divergent mt DNA phylogenetic groups and subspecies identified in previous studies as the starting point and analysed the candidates using five species delimitation methods and two validation methods. Our findings indicate that Dipus can be divided into four phylogenetic groups that include two species: the Deasyi group ( D. deasyi ), Sagitta group, Sowerbyi group and Turanicus group ( D. sagitta ). According to the morphological analyses and the examined specimens, pelage colour varies significantly with season and age, making it unsuitable as a diagnostic characteristic of the subspecies. Furthermore, measurements of body size and skull size require a large number of specimens to reach statistical significance and obtain reliable results. Geographical distributions should be considered first when identifying species or subspecies due to the disjunct habitats of Dipus . Our molecular analyses revealed the long‐neglected potential diversity in arid regions and improved the efficiency of species/subspecies identification. We also found that individuals from more humid areas or higher altitudes were larger, whereas individuals from drier areas possessed longer appendages and larger tympanic bulla.

Late Cretaceous basalts and rhyolites from Shimaoshan Group in eastern Fujian Province, SE China: age, petrogenesis, and tectonic implications - Xi-Yao Li; San-Zhong Li; Yan-Hui Suo; Li-Ming Dai; Ling-Li Guo; Feng-Jian Ge; Pei-Jun Lin (International Geology Review, 2018)

TMEM88 mediates inflammatory cytokines secretion by regulating JNK/P38 and canonical Wnt/β-catenin signaling pathway in LX-2 cells - Tao Xu; Lin-xin Pan; Yun-xuan Ge; Peng Li; Xiao-ming Meng; Cheng Huang; Jun Li (Inflammopharmacology, 2018)

A unique genetic lineage at the southern coast of China in the agar-producing Gracilaria vermiculophylla (Gracilariales, Florideophyceae) - Zi-Min Hu; Ruo-Yu Liu; Jie Zhang; De-Lin Duan; Gao-Ge Wang; Wen-Hong Li (Algae, 2018)

Study on the Clinical Features and Prognosis of Penicilliosis marneffei Without Human Immunodeficiency Virus Infection - Ying-ge Wang; Jin-mei Cheng; Hai-bo Ding; Xi Lin; Guo-hao Chen; Mei Zhou; Sheng-nan Ye (Mycopathologia, 2018)

Lithospheric thermal evolution and dynamic mechanism of destruction of the North China Craton - Zian Li; Lu Zhang; Ge Lin; Chongbin Zhao; Yingjie Liang (International Journal of Earth Sciences, 2018)

Effect of nitrite exposure on oxygen-carrying capacity and gene expression of NF-κB/HIF-1α pathway in gill of bighead carp (Aristichthys nobilis) - Yan Lin; Ling-Hong Miao; Wu-Xiao Zhang; Wen-Jing Pan; Hua-Liang Liang; Xian-Ping Ge; Yan-Shun Xu; Bo Liu; Ming-Chun Ren; Qun-Lan Zhou; Si-Lei Xia (Aquaculture International, 2018)

CXCL5 regulation of proliferation and migration in human non-small cell lung cancer cells - Lin Wang; Lin Shi; Jie Gu; Cheng Zhan; Junjie Xi; Jianyong Ding; Di Ge (Journal of Physiology and Biochemistry, 2018)

Climatology and seasonality of upper ocean salinity: a three-dimensional view from argo floats - Ge Chen; Lin Peng; Chunyong Ma (Climate Dynamics, 2018)

ALDH2 genes are negatively correlated with natural deastringency in Chinese PCNA persimmon (Diospyros kaki Thunb.) - Jun-Chi Xu; Jin-Ge Ding; Jian-Ping Gan; Rong-Li Mo; Li-Qing Xu; Qing-Lin Zhang; Zheng-Rong Luo (Tree Genetics & Genomes, 2017)

Establishing a Forecast Mathematical Model of Sugarcane Yield and Brix Reduction Based on the Extent of Pokkah Boeng Disease - Ze-ping Wang; Lu Liu; Yu-chi Deng; Yi-jie Li; Ge-min Zhang; Shan-hai Lin; Tie-guang He (Sugar Tech, 2017)

Bioinformatic prediction and analysis of glucolipid metabolic regulation by miR-34a in Megalobrama amblycephala - Ling-Hong Miao; Wen-Jing Pan; Yan Lin; Xian-Ping Ge; Bo Liu; Ming-Chun Ren; Qun-Lan Zhou (Genes & Genomics, 2017)

First evidence of pyrrolizidine alkaloid N-oxide-induced hepatic sinusoidal obstruction syndrome in humans - Mengbi Yang; Jianqing Ruan; Hong Gao; Na Li; Jiang Ma; Junyi Xue; Yang Ye; Peter Pi-Cheng Fu; Jiyao Wang; Ge Lin (Archives of Toxicology, 2017)

Development and application of a tyrosinase-based time-temperature indicator (TTI) for determining the quality of turbot sashimi - Fengjuan Xu; Lei Ge; Zhenxing Li; Hong Lin; Xiangzhao Mao (Journal of Ocean University of China, 2017)

Adsorption-Desorption Characteristics of Nonylphenol on Two Different Origins of Black Carbon - Guanghuan Cheng; Mingyang Sun; Xinlei Ge; Yang Ou; Xinhua Xu; Qi Lin; Liping Lou (Water, Air, & Soil Pollution, 2017)

Simulating climate change impacts and potential adaptations on rice yields in the Sichuan Basin, China - Che-Chen Xu; Wen-Xiang Wu; Quan-Sheng Ge; Yang Zhou; Yu-Mei Lin; Ya-Mei Li (Mitigation and Adaptation Strategies for Global Change, 2017)

Association of MMP-9 C-1562T polymorphism with risk of Henoch-Schönlein purpura nephritis in children of southeast China - Jinwen Xu; Liping Zhao; Hongxia Zhou; Tingting Ge; Lin Zhang (Genes & Genomics, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Effects of pre-pregnancy body mass index and gestational weight gain on neonatal birth weight - Meng-kai Du; Li-ya Ge; Meng-lin Zhou; Jun Ying; Fan Qu; Min-yue Dong; Dan-qing Chen (Journal of Zhejiang University-SCIENCE B, 2017)

Branched polymeric prodrug/programmed cell death 4 complexes for combinational cancer therapy - Yu-Jing He; Lei Xing; Peng-Fei Cui; Jia-Liang Zhang; Jian-Bin Qiao; Cheng-Qiong Luo; Ge Jiang; Hu-Lin Jiang (Journal of Pharmaceutical Investigation, 2017)

Whole transcriptome analysis of three leaf stages in two cultivars and one of their F1 hybrid of Camellia sinensis L. with differing EGCG content - Jinke Lin; Iain W. Wilson; Guoping Ge; Guiling Sun; Fuliang Xie; Yanfang Yang; Liangyu Wu; Baohong Zhang; Jianqiang Wu; Yue Zhang; Deyou Qiu (Tree Genetics & Genomes, 2017)

Antimicrobial mechanism of the major active essential oil compounds and their structure–activity relationship - Xian Hui; Ge Yan; Fang-Lin Tian; Heng Li; Wen-Yun Gao (Medicinal Chemistry Research, 2017)

The long persistence of pyrrolizidine alkaloid-derived DNA adducts in vivo: kinetic study following single and multiple exposures in male ICR mice - Lin Zhu; Junyi Xue; Qingsu Xia; Peter P. Fu; Ge Lin (Archives of Toxicology, 2017)

HuR mediates motility of human bone marrow-derived mesenchymal stem cells triggered by sphingosine 1-phosphate in liver fibrosis - Na Chang; Jingjing Ge; Lei Xiu; Zhongxin Zhao; Xianghui Duan; Lei Tian; Jieshi Xie; Lin Yang; Liying Li (Journal of Molecular Medicine, 2017)

The interdecadal change of the leading mode of the winter precipitation over China - Jingwen Ge; Xiaojing Jia; Hai Lin (Climate Dynamics, 2016)

Illicit drugs and their metabolites in 36 rivers that drain into the Bohai Sea and north Yellow Sea, north China - De-Gao Wang; Qiu-Da Zheng; Xiao-Ping Wang; Juan Du; Chong-Guo Tian; Zhuang Wang; Lin-Ke Ge (Environmental Science and Pollution Research, 2016)

Multiscale partitioning of small mammal β‐diversity provides novel insights into the Quaternary faunal history of Qinghai–Tibetan Plateau and Hengduan Mountains - Zhixin Wen; Qisen Yang; Qing Quan; Lin Xia; Deyan Ge; Xue Lv (Journal of Biogeography, 2016)
Aim To assess the validity of four hypothesized drivers (Quaternary climate, niche conservatism, contemporary climate, spatial configuration) of small mammal beta diversity in the Qinghai–Tibetan Plateau ( QTP ) and the Hengduan Mountains ( HDM ). Location QTP and HDM of China. Methods We partitioned the beta diversity of small mammals in QTP and HDM into the spatial turnover and nestedness components at the regional (longitudinal/latitudinal zones) and grid (1° × 1°) scales. Regional beta diversity was evaluated by calculating the multiple‐site dissimilarities and the distance‐dissimilarity relationships. We examined the relative effects of geographical distance, environmental difference, habitat diversity, geographical isolation and Quaternary climate stability on the beta diversity patterns. Results The overall beta diversity in all longitudinal/latitudinal zones of both regions was primarily driven by spatial turnover, longitudinal nestedness patterns were almost non‐existent in QTP . Turnover was stronger in the latitudinal direction of QTP and in the longitudinal direction of HDM , which corresponded to the general topography of each region. At the grid scale, higher turnover was primarily concentrated in mountainous areas. Turnover was highly correlated with geographical distance and environmental difference in both regions, and geographical isolation was another strong predictor of turnover in HDM . Habitat diversity independently explained most of the variation in nestedness of HDM . Main conclusions Spatial turnover is the primary cause of the small mammal beta diversity in QTP and HDM . Three non‐exclusive mechanisms including the historic effect of past glaciation, contemporary climate and spatial configuration of the landscape might act in combination to shape the beta diversity patterns in QTP and HDM , particularly the directional patterns. Our results challenge the prevailing view that the current distribution of QTP fauna is primarily explained by westward post‐glacial recolonization, and support the alternative idea that QTP retained considerable refugia and even centres of origin during the Quaternary glaciations.

Genetic Variants of VEGF (rs201963 and rs3025039) and KDR (rs7667298, rs2305948, and rs1870377) Are Associated with Glioma Risk in a Han Chinese Population: a Case-Control Study - Jiannan Zhang; Jian Yang; Yuqing Chen; Qin Mao; Shanquan Li; Wenhao Xiong; Yingying Lin; Jie Chen; Jianwei Ge (Molecular Neurobiology, 2016)

Comprehensive analysis of tropomyosin isoforms in skeletal muscles by top-down proteomics - Yutong Jin; Ying Peng; Ziqing Lin; Yi-Chen Chen; Liming Wei; Timothy A. Hacker; Lars Larsson; Ying Ge (Journal of Muscle Research and Cell Motility, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

The complete mitochondrial genome of fall armyworm Spodoptera frugiperda (Lepidoptera:Noctuidae) - Qiu-Ning Liu; Xin-Yue Chai; Dan-Dan Bian; Bao-Ming Ge; Chun-Lin Zhou; Bo-Ping Tang (Genes & Genomics, 2016)

Cross-spectral recognition method of bridge deck aerodynamic admittance function - Lin Zhao; Yaojun Ge (Earthquake Engineering and Engineering Vibration, 2015)

Molecular phylogeny and the underestimated species diversity of the endemic white‐bellied rat (Rodentia: Muridae: Niviventer ) in Southeast Asia and China - Liang Lu; Deyan Ge; Douglas Chesters; Simon Y. W. Ho; Ying Ma; Guichang Li; Zhixin Wen; Yongjie Wu; Jun Wang; Lin Xia; Jingli Liu; Tianyu Guo; et al. (Zoologica Scripta, 2015)
The white‐bellied rat, Niviventer , is a genus endemic to Southeast Asia and China. However, the interspecific phylogenetic relationships and species diversity of this genus remain poorly understood. In the present study, single and multi‐locus analyses were performed. Phylogenetic reconstruction on Cytochrome b (512 individuals, including data from Genbank) revealed five major clades with approximately 35 operational taxonomic units ( OTU s), a number twice the existing taxonomy. The first clade ( N . langbianis species group) was the earliest diverged. The second clade ( N. fulvescens species group) diverged in Southeast Asia, the south and lower altitude regions of the Hengduan Mountains, and Southeast China. The third clade (the N. eha species group) is endemic to high altitudes in Northwest Yunnan and the central region of Himalaya. The fourth clade (the N. andersoni species group), is mainly confined to alpine regions of the Hengduan Mountains. The fifth clade ( N . confucianus species group) is mainly distributed in the north and higher altitude regions of eastern Himalaya, the Hengduan Mountains and Taiwan, with the complex also invading central and northern China. Results from the combined dataset of four genes (Cytochrome b, Cytochrome oxidase subunit I, the D‐loop sequence of the mitochondrial genome and the first exon of the nuclear interphotoreceptor retinoid binding protein) for 82 representative individuals from China generally coincide with the result of the single gene, with 12 OTU s identified. These results provide a preliminary framework for the existing classification of this highly diversified genus. The divergence time of Niviventer based on the four gene topology was dated to the late Miocene ~6.41 Ma. Significant differences were detected in the general body form changes among these units based on voucher specimens. Moreover, geometric morphometric analysis of the cranium shape of voucher specimens indicated significant differences among five major species groups. Shape divergence of the cranium among several OTU s within the N. confucinaus complex is also significant. Our results provide further evidence for rapid and highly underestimated diversification of Niviventer both in genetics and morphology.

Patients with type 2 diabetes exhibit cognitive impairment with changes of metabolite concentration in the left hippocampus - Yue Wang; Xiao-yun Xu; Chun-hua Feng; Yuan-ling Li; Xia Ge; Gen-lin Zong; Yi-bin Wang; Bo Feng; Peng Zhang (Metabolic Brain Disease, 2015)

Correlation analysis of gene polymorphisms and β-lactam allergy - Jing Li; Xin-yue Liu; Lin-jing Li; Chong-ge You; Lei Shi; Shang-di Zhang; Qian Liu; Jun Wang; Ze-jing Liu; Ting-hong Lv (Journal of Zhejiang University-SCIENCE B, 2015)

Diaphorobacter ruginosibacter sp. nov., isolated from soybean root nodule, and emended description of the genus Diaphorobacter - Xiu Li Wei; Meng Sha Han; Cong Cong Xia; Shu Lan Ding; Lin Xu; Yan Bing Lin; Li Wang; Ge Hong Wei (Archives of Microbiology, 2015)

A fast-convergence POCS seismic denoising and reconstruction method - Zi-Jian Ge; Jing-Ye Li; Shu-Lin Pan; Xiao-Hong Chen (Applied Geophysics, 2015)

Arbuscular mycorrhizal symbiosis can mitigate the negative effects of night warming on physiological traits of Medicago truncatula L - Yajun Hu; Songlin Wu; Yuqing Sun; Tao Li; Xin Zhang; Caiyan Chen; Ge Lin; Baodong Chen (Mycorrhiza, 2015)

Spatiotemporal Dynamics of Salt Marsh Vegetation regulated by Plant Invasion and Abiotic Processes in the Yangtze Estuary: Observations with a Modeling Approach - Zhen-Ming Ge; Li-Quan Zhang; Lin Yuan (Estuaries and Coasts, 2015)

Trace levels of mitomycin C disrupt genomic integrity and lead to DNA damage response defect in long-term-cultured human embryonic stem cells - Di Zhou; Ge Lin; Si-Cong Zeng; Bo Xiong; Ping-Yuan Xie; De-Hua Cheng; Qing Zheng; Qi Ouyang; Xiao-Ying Zhou; Wei-Ling Tang; Yi Sun; Guang-Ying Lu; et al. (Archives of Toxicology, 2015)

Relative importance of an arbuscular mycorrhizal fungus (Rhizophagus intraradices) and root hairs in plant drought tolerance - Tao Li; Ge Lin; Xin Zhang; Yongliang Chen; Shubin Zhang; Baodong Chen (Mycorrhiza, 2014)

miR-210 over-expression enhances mesenchymal stem cell survival in an oxidative stress environment through antioxidation and c-Met pathway activation - JianFeng Xu; ZheYong Huang; Li Lin; MingQiang Fu; YanHua Gao; YunLi Shen; YunZeng Zou; AiJun Sun; JuYing Qian; JunBo Ge (Science China Life Sciences, 2014)

A Clinical Study of Patients with Coronary Heart Disease Complicated with Hypertriglyceridemic Waist Phenotype - Rui-feng Yang; Zhi Lin; Xiao-yong Liu; Ge Zhang (Cell Biochemistry and Biophysics, 2014)

Beclin-1-mediated autophagy protects spinal cord neurons against mechanical injury-induced apoptosis - Zhen-Yu Wang; Jian-Hua Lin; Akram Muharram; Wen-Ge Liu (Apoptosis, 2014)

CD14 −159C/T polymorphism contributes to the susceptibility to tuberculosis: evidence from pooled 1,700 cases and 1,816 controls - Ruifen Miao; Haibo Ge; Lin Xu; Fei Xu (Molecular Biology Reports, 2014)

Physiological and biochemical responses of Phoebe bournei seedlings to water stress and recovery - Yongjin Ge; Xiaoyong He; Junfeng Wang; Bo Jiang; Ronghua Ye; Xinchun Lin (Acta Physiologiae Plantarum, 2014)

Molecular basis for insecticide‐enhanced thermotolerance in the brown planthopper N ilaparvata lugens S tål ( H emiptera: D elphacidae) - Lin‐Quan Ge; Liu‐Juan Huang; Guo‐Qin Yang; Qi‐Sheng Song; David Stanley; G. M. Gurr; Jin‐Cai Wu (Molecular Ecology, 2013)
Climate change is likely to have marked ecological effects on terrestrial ecosystems, including the activities of insect pests. Most attention has focused on the increasing geographical ranges of pests; however, if extrinsic factors enhance their thermotolerance, populations may express increased voltinism and longer daily and annual activity periods. These changes in pest populations have the potential for severe consequences, including increased crop losses and decreased food security at the global level. The brown planthopper ( BPH ) Nilaparvata lugens Stål (Hemiptera: Delphacidae) is a serious pest of rice crops in temperate and tropical regions of Asia. It is often present in rice microclimates at temperatures close to its maximum thermotolerance. Recent BPH outbreaks in tropical Asia are considered to be associated with excess use of pesticides and increasing temperature. This study tested whether exposure to sublethal concentrations of triazophos (tzp), an insecticide widely used in Asian rice production, enhances thermotolerance of BPH . Tzp exposure (40 ppm at 40 °C) significantly decreased mortality (from 94% in controls to 50% at 48 h post‐treatment) and increased lethal mean time ( LT 50 ) of adults by 17.2 h. To investigate the underlying molecular mechanism of this tzp‐enhanced thermotolerance, we selected Hsp70 and Arginine kinase (Argk) for detailed study. Transcripts encoding both proteins in third‐instar nymphs and brachypterous adult females were up‐regulated, compared with controls, after exposure to tzp. RNA i silencing of both genes demonstrated that Hsp70 and Argk are essential for survival and tzp‐increased thermotolerance. We propose that tzp induces thermotolerance in BPH s by increasing the expression of genes that act in cell protection mechanisms. The significance of our proposal relates to the importance of understanding the influence of sublethal concentrations of insecticides on pest biology. In addition to its influence on thermotolerance, tzp also enhances BPH reproduction. We infer that exposure to a pesticide stressor can produce cross‐tolerance, that is, increased tolerance to one stressor also increases tolerance to other stressors, including temperature. Aside from needing a better understanding of these effects in nature and in other pest/cropping systems, we suggest that pest management programmes can be improved with better understanding of the influences of stressors, including increased environmental temperatures and sublethal concentrations of insecticides, on pest biology.

A geospatial web portal for sharing and analyzing greenhouse gas data derived from satellite remote sensing images - Hao Lin; Bailang Yu; Zuoqi Chen; Yingjie Hu; Yan Huang; Jianping Wu; Bin Wu; Rong Ge (Frontiers of Earth Science, 2013)

Fine mapping TaFLW1, a major QTL controlling flag leaf width in bread wheat (Triticum aestivum L.) - Shulin Xue; Feng Xu; Guoqiang Li; Yan Zhou; Musen Lin; Zhongxia Gao; Xiuhong Su; Xiaowu Xu; Ge Jiang; Shuang Zhang; Haiyan Jia; Zhongxin Kong; et al. (Theoretical and Applied Genetics, 2013)

A method to estimate concentrations of surface-level particulate matter using satellite-based aerosol optical thickness - JinHua Tao; MeiGen Zhang; LiangFu Chen; ZiFeng Wang; Lin Su; Cui Ge; Xiao Han; MingMin Zou (Science China Earth Sciences, 2013)

Salvianolic acid A, a polyphenolic derivative from Salvia miltiorrhiza bunge, as a multifunctional agent for the treatment of Alzheimer’s disease - Ying Ying Cao; Ling Wang; Hu Ge; Xi Lin Lu; Zhong Pei; Qiong Gu; Jun Xu (Molecular Diversity, 2013)

Decreased expression of the DBC2 gene and its clinicopathological significance in breast cancer: correlation with aberrant DNA methylation - Linlin Han; Lin Hou; Jinlian Song; Dongliang Lin; Li Wu; Yinlin Ge; Zhongliang Ma (Biotechnology Letters, 2013)

Cloning and functional analysis of putative malonyl-CoA:acyl-carrier protein transacylase gene from the docosahexaenoic acid-producer Schizochytrium sp. TIO1101 - Rubin Cheng; Yuqing Ge; Bo Yang; Xiaoming Zhong; Xiangzhi Lin; Zhen Huang (World Journal of Microbiology and Biotechnology, 2013)

The Evolution and Paleobiogeography of Flying Squirrels (Sciuridae, Pteromyini) in Response to Global Environmental Change - Xuefei Lu; Deyan Ge; Lin Xia; Zhaoqun Zhang; Song Li; Qisen Yang (Evolutionary Biology, 2013)

Tracing the Origin and Diversification of Dipodoidea (Order: Rodentia): Evidence from Fossil Record and Molecular Phylogeny - Qian Zhang; Lin Xia; Yuri Kimura; Georgy Shenbrot; Zhaoqun Zhang; Deyan Ge; Qisen Yang (Evolutionary Biology, 2013)

Rhizobium qilianshanense sp. nov., a novel species isolated from root nodule of Oxytropis ochrocephala Bunge in China - Lin Xu; Yong Zhang; Zheng Shan Deng; Liang Zhao; Xiu Li Wei; Ge Hong Wei (Antonie van Leeuwenhoek, 2013)

Cyclin D1 polymorphism and oral cancer: a meta-analysis - Wenjun Wang; Yuming Zhao; Jie Yang; Bichen Lin; Haiyong Gu; Xiaoqing Cao; Lihong Ge (Molecular Biology Reports, 2013)

Thaxtomin A-deficient endophytic Streptomyces sp. enhances plant disease resistance to pathogenic Streptomyces scabies - Lan Lin; Hui Ming Ge; Tong Yan; Yan Hua Qin; Ren Xiang Tan (Planta, 2012)

High density lipoprotein cholesterol promotes the proliferation of bone-derived mesenchymal stem cells via binding scavenger receptor-B type I and activation of PI3K/Akt, MAPK/ERK1/2 pathways - Jianfeng Xu; Juying Qian; Xinxing Xie; Li Lin; Jianying Ma; Zheyong Huang; Mingqiang Fu; Yunzeng Zou; Junbo Ge (Molecular and Cellular Biochemistry, 2012)

Molecular characterization and phylogenetic analysis of porcine epidemic diarrhea virus (PEDV) samples from field cases in Fujian, China - Xi Chen; Jinxian Yang; Fusong Yu; Junqing Ge; Tianlong Lin; Tieying Song (Virus Genes, 2012)

Influence of UGT genetic polymorphism on the interindividual variability in mitiglinide pharmacokinetic in Chinese - Jing-feng Xu; Zhan-qing Wang; Chen-xia Yan; Qian Xu; Lin Xu; Gang-tao Zhao; Yong-ge Yang (Medicinal Chemistry Research, 2012)

Efficacy of a Therapeutic Vaccine Using Mutated β-amyloid Sensitized Dendritic Cells in Alzheimer’s Mice - Zhongqiu Luo; Jialin Li; Neel R. Nabar; Xiaoyang Lin; Ge Bai; Jianfeng Cai; Shu-Feng Zhou; Chuanhai Cao; Jinhuan Wang (Journal of Neuroimmune Pharmacology, 2012)

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

Rhizobium helanshanense sp. nov., a bacterium that nodulates Sphaerophysa salsula (Pall.) DC. in China - Wei Qin; Zhen Shan Deng; Lin Xu; Na Na Wang; Ge Hong Wei (Archives of Microbiology, 2012)

Comparison of Intestinal Absorption and Disposition of Structurally Similar Bioactive Flavones in Radix Scutellariae - Chenrui Li; Li Zhang; Limin Zhou; Siu Kwan Wo; Ge Lin; Zhong Zuo (The AAPS Journal, 2012)

Developmental incompatibility of human parthenogenetic embryonic stem cells in mouse blastocysts - Lili Du; Xiaoming Xu; Xin Duan; Guangxiu Lu; Ge Lin (In Vitro Cellular & Developmental Biology - Animal, 2012)

Norcantharidin, a protective therapeutic agent in renal tubulointerstitial fibrosis - Ying Li; Yan Ge; Fu You Liu; You Ming Peng; Lin Sun; Jun Li; Qiong Chen; Yan Sun; Kun Ye (Molecular and Cellular Biochemistry, 2012)

Anti-tumor Effects of All-trans Retinoic Acid are Enhanced by Genistein - Ren-Jie Zhou; Xue-Qin Yang; Dong Wang; Qian Zhou; Lei Xia; Meng-Xia Li; Lin-Li Zeng; Ge Wang; Zhen-Zhou Yang (Cell Biochemistry and Biophysics, 2012)

First Isolation of Candida dubliniensis from Oral Cavities of Dermatological Patients in Nanjing, China - Yi P. Ge; Guo X. He; Tong Lin; Gui X. Lu; Yong N. Shen; Wei D. Liu (Mycopathologia, 2011)

Hepatic Metabolism and Disposition of Baicalein via the Coupling of Conjugation Enzymes and Transporters—In Vitro and In Vivo Evidences - Li Zhang; Chenrui Li; Ge Lin; Peter Krajcsi; Zhong Zuo (The AAPS Journal, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Rhizobium sphaerophysae sp. nov., a novel species isolated from root nodules of Sphaerophysa salsula in China - Lin Xu; Jian Feng Shi; Peng Zhao; Wei Min Chen; Wei Qin; Ming Tang; Ge Hong Wei (Antonie van Leeuwenhoek, 2011)

Temporal and spatial variability of chlorophyll a concentration in Lake Taihu using MODIS time-series data - Yuchao Zhang; Shan Lin; Xin Qian; Qin’geng Wang; Yu Qian; Jianping Liu; Yi Ge (Hydrobiologia, 2011)

The effect of depression on the thermal nociceptive thresholds in rats with spontaneous pain - Yuan-Lin Su; Ning Wang; Ge Gao; Jin-Yan Wang; Fei Luo (Neuroscience Bulletin, 2010)

Phylogeny of Salsoleae s.l. (Chenopodiaceae) based on DNA sequence data from ITS, psbB–psbH, and rbcL, with emphasis on taxa of northwestern China - Zhi-Bin Wen; Ming-Li Zhang; Ge-Lin Zhu; Stewart C. Sanderson (Plant Systematics and Evolution, 2010)

Detrital zircon and apatite fission track data in the Liaoxi basins: Implication to Meso-Cenozoic thermo-tectonic evolution of the northern margin of the North China Craton - Yi Yan; Xiaoqiong Hu; Ge Lin; Weiliang Liu; Zhengjiang Song (Journal of Earth System Science, 2010)

Expression of recombinant zebrafish follicle-stimulating hormone (FSH) in methylotropic yeast Pichia pastoris - Xiaobin Yu; Sze-Wah Lin; Makito Kobayashi; Wei Ge (Fish Physiology and Biochemistry, 2010)

Establishment and maintenance of three Chinese human embryonic stem cell lines - Di Zhou; Ge Lin; Chang-Qing Xie; Bo Xiong; Xiao-Ying Zhou; Xiao-Bing Qian; Yi Liao; Guang-Xiu Lu (In Vitro Cellular & Developmental Biology - Animal, 2010)

Impact of female cigarette smoking on circulating B cells in vivo: the suppressed ICOSLG, TCF3, and VCAM1 gene functional network may inhibit normal cell function - Feng Pan; Tie-Lin Yang; Xiang-Ding Chen; Yuan Chen; Ge Gao; Yao-Zhong Liu; Yu-Fang Pei; Bao-Yong Sha; Yan Jiang; Chao Xu; Robert R. Recker; Hong-Wen Deng (Immunogenetics, 2010)

The polymorphisms of UCP1 genes associated with fat metabolism, obesity and diabetes - Jun-jing Jia; Yun-bo Tian; Zhen-hui Cao; Lin-li Tao; Xi Zhang; Si-zhen Gao; Chang-rong Ge; Qiu-Ye Lin; M. Jois (Molecular Biology Reports, 2010)

Effects of Neuregulin on Expression of MMP-9 and NSE in Brain of Ischemia/Reperfusion Rat - Qin Li; Rui Zhang; Yin-lin Ge; Yuan-wu Mei; Yun-liang Guo (Journal of Molecular Neuroscience, 2009)

Development of twelve polymorphic microsatellite loci in polyploid endangered Omphalogramma vincaeflora Franch. (Primulaceae) - Yuan Huang; Yong Li; Xiao Hu; Xue-Jun Ge; Chang-Qin Zhang; Chun-Lin Long (Conservation Genetics, 2009)

Borealin is differentially expressed in ES cells and is essential for the early development of embryonic cells - Qianjun Zhang; Ge Lin; Yifang Gu; Jianjun Peng; Zaoyan Nie; Yuelong Huang; Guangxiu Lu (Molecular Biology Reports, 2009)

Numerical analysis and simulation experiment of lithospheric thermal structures in the South China Sea and the Western Pacific - Ge Lin; Meili Peng; Chongbin Zhao; Lu Zhang; Desheng Zhang; Shilin Liu (Journal of Earth Science, 2009)

Denudation history of South China block and sediment supply to northern margin of the South China Sea - Yi Yan; Xiaoqiong Hu; Ge Lin; Bin Xia; Xiaoyong Li; Remesh Chandra Patel (Journal of Earth Science, 2009)

Ischemic preconditioning induces chaperone hsp70 expression and inhibits protein aggregation in the CA1 neurons of rats - Peng-Fei Ge; Tian-Fei Luo; Ji-Zhou Zhang; Da-Wei Chen; Yong-Xin Luan; Shuang-Lin Fu (Neuroscience Bulletin, 2008)

Overexpression of the trehalose-6-phosphate phosphatase gene OsTPP1 confers stress tolerance in rice and results in the activation of stress responsive genes - Liang-Fa Ge; Dai-Yin Chao; Min Shi; Mei-Zhen Zhu; Ji-Ping Gao; Hong-Xuan Lin (Planta, 2008)

Knocking down Wnt9a mRNA levels increases cellular proliferation - Yang Xiang; Ge Lin; Qianjun Zhang; Yueqiu Tan; Guangxiu Lu (Molecular Biology Reports, 2008)

Characterization of seven genomic and one dbEST-derived microsatellite loci in the river mangrove Aegiceras corniculatum (Myrsinaceae) - Guo-Qing Chen; Lin-Feng Li; Gang Hao; Su-Hua Shi; Xue-Jun Ge (Conservation Genetics, 2008)

Development of thirteen microsatellite loci for Impatiens lateristachys (Balsaminaceae) - Lin-Feng Li; Guo-Qing Chen; Yong-Ming Yuan; Xue-Jun Ge (Conservation Genetics, 2008)

Development of ten microsatellite loci for Gentiana crassicaulis (Gentianaceae) - Yong Li; Lin-Feng Li; Guo-Qing Chen; Xue-Jun Ge (Conservation Genetics, 2007)

Improved somatic embryo maturation in loblolly pine by monitoring ABA-responsive gene expression - Teresa Vales; Xiaorong Feng; Lin Ge; Nanfei Xu; John Cairney; Gerald S. Pullman; Gary F. Peter (Plant Cell Reports, 2007)

Involvement of UDP-Glucuronosyltransferases in the Extensive Liver and Intestinal First-Pass Metabolism of Flavonoid Baicalein - Li Zhang; Ge Lin; Zhong Zuo (Pharmaceutical Research, 2007)

Isolated and characterization of a cDNA encoding ethylene-responsive element binding protein (EREBP)/AP2-type protein, RCBF2, in Oryza sativa L. - Jin-Ge Liu; Zhen Zhang; Qiu-Lin Qin; Ri-He Peng; Ai-Sheng Xiong; Jian-Min Chen; Fang Xu; Hong Zhu; Quan-Hong Yao (Biotechnology Letters, 2006)

A tissue culture system for different germplasms of indica rice - Xiaojia Ge; Zhaohui Chu; Yongjun Lin; Shiping Wang (Plant Cell Reports, 2006)

Protoplast electrofusion between common wheat (Triticum aestivum L.) and Italian ryegrass (Lolium multiflorum Lam.) and regeneration of mature cybrids - T. M. Ge; X. H. Lin; F. L. Qin; S. W. Yu; Y. J. Yu (In Vitro Cellular & Developmental Biology - Plant, 2006)

Role of withdrawal in reinstatement of morphine-conditioned place preference - Lin Lu; Hai Chen; Wenjuan Su; Xin Ge; Wen Yue; Fen Su; Lan Ma (Psychopharmacology, 2005)

Role of Intestinal First-Pass Metabolism of Baicalein in its Absorption Process - Li Zhang; Ge Lin; Qi Chang; Zhong Zuo (Pharmaceutical Research, 2005)

Pilot-Scale Fermentation and Purification of the Recombinant Allophycocyanin Over-Expressed in Escherichia coli - Baosheng Ge; Zhihong Tang; Liping Lin; Yuhong Ren; Yu Yang; Song Qin (Biotechnology Letters, 2005)

Construction and characterization of a bacterial artificial chromosome library of marine macroalgaPorphyra yezoensis (Rhodophyta) - Dai Yong Deng; Ge Zhao; Jin Song Xuan; Ji Liang Yang; Lin De Duan; Man Li Weng; Bin Wang (Plant Molecular Biology Reporter, 2004)

Activin stimulates goldfish FSH biosynthesis by enhancing FSHβ promoter activity - Wei Ge; Nga-Ling Ko; Flora Yee-Man Pang; Me-Fong Chung; Sze-Wah Lin; Chi-Wai Yuen; Man-Tat Lau; Lin Liu; Young Chang Sohn; Makito Kobayashi; Katsumi Aida (Fish Physiology and Biochemistry, 2003)

Geochemical and Sm–Nd isotopic characteristics of metabasites from central Hainan Island, South China and their tectonic significance - Xian‐Hua Li; Hanwen Zhou; Sun‐Lin Chung; Shijiang Ding; Ying Liu; Chi‐Yu Lee; Wenchun Ge; Yeming Zhang; Renjie Zhang (Island Arc, 2002)
Major and trace elements and Sm–Nd isotopic data are presented for metabasites that are present as lenses within Paleozoic metasediments in the Chenxing and Bangxi regions, central Hainan Island, Southeast (SE) China. Most metabasites are metamorphosed cumulated gabbroic rocks tholeiitic in nature, and characterized by varying degrees of depletion in Th, Nb, Ta and light rare earth elements (LREE). Moreover, they show high positive ∈Nd(T) values of approximately +7, similar to those of mid‐ocean ridge basalts (MORB). A Sm–Nd isochron age of 333 ± 12 Ma obtained for the metabasites is interpreted as their crystallization age. The combined geochemical and Sm–Nd isotopic data suggest that the metabasites were generated by dynamic partial melting from a MORB‐like mantle source in an oceanic regime. These rocks probably represent remnants of fragmented oceanic crust of the eastern part of Paleo‐Tethys. They were obducted onto the continental crust as part of the ‘Shilu Mélange’ in earliest Mesozoic time when southern Hainan (part of the Indochina block) collided with northern Hainan (part of South China). Alternatively, they could be formed in a volcanic rifted passive margin at the sea‐floor spreading stage as part of MORB‐like seaward‐dipping reflector break‐up packages.

Allozyme variation and conservation genetics of common wild rice (Oryza rufipogon Griff.) in Yunnan, China - Lizhi Gao; Song Ge; Deyuan Hong; Rushun Lin; Guoda Tao; Zaifu Xu (Euphytica, 2002)

Reactivation of morphine conditioned place preference by drug priming: role of environmental cues and sensitization - Lin Lu; Nan-Jie Xu; Xin Ge; Wen Yue; Wen-Juan Su; Gang Pei; Lan Ma (Psychopharmacology, 2002)